RLX-2 ameliorates post-traumatic joint contracture by inhibiting the cGAS-STING signaling pathway - Jian-Jun Chen; Quan-Bing Zhang; Yan Wang; Chen Chen; Yi Liu; Zun-Yu Du; Xiu-Li Kan; Han Xiao; Xue-Ming Li; Run Zhang; De-Ting Zhu; Xian-Liang Rao; et al. (Tissue and Cell, 2027)

Lactate-enhanced production of a cyclic β-1,2-glucan in Acetobacter pasteurianus - Yong Chen; Yihang Qi; Zhongya Zhou; Xin Liu; Yaping Sun; Ting Liu; Mengru Wu; Hui Li; Jing-yi Zhao; Zijun Xiao (Food Microbiology, 2027)

Genome sequencing and transcriptome analysis of Corbicula fluminea reveal its genome evolution and the role of glutathione S-transferase and glutathione peroxidase families in salinity response - Ting Zhang; Yidong Liang; Junlei Ma; Jinshuo Liang; Yicheng Li; Yanfeng Zhou; Dongpo Xu (Aquaculture, 2027)

Integration of physiological, transcriptomic and metabolomic analyses reveals acute carbonate alkalinity stress responses in the gill of Asian clam (Corbicula fluminea) - Ting Zhang; Junlei Ma; Yidong Liang; Yicheng Li; Jinshuo Liang; Yanfeng Zhou; Dongpo Xu (Aquaculture, 2027)

Src interacts with TRAF5 and promotes NF-κB-associated antiviral responses against iridovirus in marine teleost - Lingfeng Guan; Yi Li; Ting Yu; Jiamei Long; Runchang Zhou; Zhifeng Chen; Hua Huang; Jinglin Tan; Min Yang; Shaowen Wang; Qiwei Qin (Fish & Shellfish Immunology, 2026)

Machine learning-assisted quorum sensing molecules regulate growth progression and bioactivity of an oxygenic photobiofilm for non-aeration greywater purification - Beibei Wu; Libo Xia; Qian Li; Xiaocai Cui; Ting Ran; Yangrui Huang; Yun Zhou (Bioresource Technology, 2026)

Astragaloside IV pretreatment enhances the therapeutic efficacy of bone marrow mesenchymal stem cells in murine fulminant hepatic failure - Ting-Ting Zhao; Wen-Qiang He; Rui-Zhi Shi; Bing-Yu Du; Mei-Mei Lan; Dan Zhou; Xiao-Qin Gao; Min Li; Jun-Feng Li; Li-Ting Zhang (Molecular Biology Reports, 2026)

Aerobic exercise improve physical endurance and muscle function by ameliorating oxidative stress and modulating mitochondrial dynamics in aged skeletal muscle - Fengting Zheng; Jiawei Zhou; Yangfan Cao; LuYi Lin; Wenxin Wang; Liang Zhang; Wei Li; Ting Li; Lifeng Wang (Journal of Physiology and Biochemistry, 2026)

Precise H2 supply enables quantitative control of on-demand deep nitrate removal while preserving denitrification completeness - Ge Yan; Zhen-Xiang Jiang; Jia-Le Wu; Ting Wang; Jun-Tong Hu; Li-Wen Qiu; Chen Zhou; Hongqiang Ren (Water Research, 2026)

Contrasting redox-related physiological responses associated with HaGATA23 and HaGATA36 during Orobanche cumana parasitism in sunflower (Helianthus annuus L.) - Yan Fu; Ting Zhou; Shuo Zhang; Shuowei Su; Lei Shen; Ying Li; Wenya Zhang; Ahsan Ayyaz; Hongju Sun; Ling Xu (Plant Science, 2026)

Isolation and food-relevant evaluation of a novel lytic Kayfunavirus phage vB-EcoP-B10 for controlling STEC on food-contact surfaces and in raw beef - Yuxin Mu; Min Li; Xiangqi Bai; Qianhong Li; Xiaodong Xia; Ting Zhou; Chunling Zhang; Ying Yu; Yanna Dai; Jifeng Pu; Hu Pan; Xin Wang (Food Research International, 2026)

Green deep eutectic solvent synthesis of ultrasmall BiOCl with Bi-S interfacial coordination bonds for visible-light-driven organic pollutant degradation and CO2 photoreduction - Jiahui Zhou; Ting Jiang; Yuansong Ding; Jawad Ahmad Jrar; Dayu Li; Kewang Zheng; Xiaozhi Wang; Yongcai Zhang; Jianhua Hou (Environmental Research, 2026)

Intermittent organophosphate pesticide exposure induces hepatic injury in goats with subclinical fatty liver via immune activation and energy metabolism reprogramming - Dechun Chen; Tianjun Yang; Ting Zhao; Anzhu Li; Qingjia Lin; Xinying Zhou; Huanrong Zhang; Jian Fu; Falong Yang; Haifeng Liu (Environmental Pollution, 2026)

A crystallinity-switch strategy for in-situ encapsulating Pd nanoclusters toward selective conversion of CO2 - Zhao-Cheng Shi; Jing Li; Xue-Feng Zhang; Ming-Ming Wu; Zhonggao Zhou; Meng-Tian Zhang; Chun-Ting He (Chemical Engineering Journal, 2026)

In situ formation of chemically integrated and mechanically interlocked interphases enables robust epoxy-copper adhesion - Ting Xin; Zeyu Zheng; Zuo Li; Yue Wu; Yang Liu; Binbin Zhou; Jibao Lu; Xiaoliang Zeng; Fan Yang; Gang Li; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

An ER-targeted electronic-switched cascade probe for synchronous dual-channel imaging of H2S and HClO during liver fibrosis - Jiaxue Yang; Yi Le; Na Wang; Beibei Wu; Yuyang Song; Ting Wang; Birong Yang; Fan Zhou; Li Liu (Analytica Chimica Acta, 2026)

Asynchronous recovery of hydrolytic and oxidative enzymes during wetland restoration - Xiangling Zhou; Ting Wang; Lifei Su; Siqi Zheng; Shijia Liu; Yi Liu; Wenhui Quan; Tingting Hu; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; et al. (Agriculture, Ecosystems & Environment, 2026)

Reshaping geochemical fate of gold-mining-derived arsenic in Jiehe River sediments from molecular to field scales via an innovative iron-based mineralization strategy - Weichen Luo; Ting Li; Yujun Zhou; Baoting Ding; Xin Du; Xuan Liu; Yongpeng Zhang; Zhaodi Wu; Jianru Liang; Shuqing Li; Jun Chen; Lixiang Zhou (Water Research, 2026)

Formation of post-traumatic and non-traumatic knee joint contracture: Role of macrophage polarization in joint capsule and skeletal muscle - Feng Wang; Fan Bai; Ting Zhou; He Liu; Ding-Jiang Wu; Yun Zhou; Wen Li (Tissue and Cell, 2026)

Quercetin alleviates Streptococcus agalactiae-induced mastitis in mice by inhibiting the NF-κB/NLRP3 signaling pathway and ferroptosis - Yaying Jia; Qi Sun; Ting Wu; Yueqing Xie; Hongsen Yu; Mingzhen Jiang; Xuhai Li; Zhengtao Yang; Ershun Zhou; Jingjing Wang (Research in Veterinary Science, 2026)

Kinetics and characterization of jarosite biosynthesis via Acidithiobacillus ferrooxidans: Elucidating its potential in acidic uranium tailings stabilization - Ling Xiao; Shangze Li; Jing Sun; Qian Li; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Qinghua Li (Minerals Engineering, 2026)

Evaluating the effectiveness of GSMaP precipitation product in capturing precipitation events - Chun Zhou; Li Zhou; Ting Chen; Juan Du; Jiajia Yue; Keying Liu; Tianqi Ao (Journal of Hydrology, 2026)

Synthesis and valorization of corn silk-derived carbon dots for antimicrobial fruit preservation - Yong-Ping Wen; Meng-Ting Wu; Kwang-Pyo Kim; Meng-Yi Chen; Jia-Hui Liu; Ya-Ping Li; An-Guo Wu; Xiang Li; Song-Zhi Xie; Die Gao; Jian-Ming Wu; Xiao-Gang Zhou (International Journal of Food Microbiology, 2026)

Antifungal activity of Hanseniaspora uvarum VOCs against Alternaria alternata and Botrytis cinerea in blueberry by disrupting growth metabolism - Xinyue Lv; Ting Yang; Yicai Jiang; Furong Yuan; Longwei Li; Yahan Zhou (Food Research International, 2026)

A novel perspective on the aging of raw Pu-erh tea: a comprehensive evaluation of the impact of different storage containers on flavor quality - Di Tian; Ting Wu; Linna Ma; Xiaohui Zhou; Chenyang Ma; Ning Chen; Haiyan Yi; Yapeng Liu; Yali Li; Yong-Quan Xu; Hongjie Zhou; Xiujuan Deng (Food Research International, 2026)

Dynamic characterization of volatile profiles and intelligent discrimination of raw Milk under frozen storage using non-targeted volatile metabolomics and machine learning - Ken Lu; Liqiong Niu; Ting Wen; Zhicong An; Chen Liu; Jiangfei Chai; Hongliang Li; Bei Zhou; Yongjing Bie; Chaokun Wei; Yan Ping Chen; Yuan Liu (Food Research International, 2026)

Beyond mortality: A multi-outcome assessment of health economic benefits from air pollution control in China - Hao-Wen Liao; Zhi-Ming Han; Guo-Ping Dong; Duo-Hong Chen; Min Xie; Jun Liu; Junyu Zheng; Yun-Ting Zhang; Haseeb Tufail Moryani; Muhammad Amjad; Yang Zhou; Wen-Wen Bao; et al. (Environmental Research, 2026)

Naturally occurring biopterin as a photosensitizer for enhanced photodegradation of sulfonamides in aquatic environments - Bing Li; Yu-Ze Han; Ye-Chao Tian; Xin Wang; Chi-Cheng Deng; Xiao-Ya Zhou; Shuo Zhang; Yan-Ting Zuo; Wen-Tao Li; Ai-Min Li (Environmental Pollution, 2026)

HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Solvent-resistant, alkali-recoverable, self-healing, shape-memory and conductive dynamic polymers from multicomponent bio-based monomers for self-sensing soft actuators - Shiyu Du; Zhijian Li; Ting Gan; Zhou Bai; Yuan Li; Yonglong Chen; Cuizhu Wang; Guodong Liu; Haiwei Wu; Hongwei Zhou; Hanbin Liu (Chemical Engineering Journal, 2026)

Spatiotemporal scaling of gully erosion susceptibility: Integrating seasonal dynamics across regional and watershed contexts - Yanyan Xu; Yanru Wen; Seyed Hamidreza Sadeghi; Tong Zhou; Jing Yang; Ting-yong Li; Bingxue Zhu; Wenbin Wu (CATENA, 2026)

Chemotaxonomic significance of dipeptides and flavonoids in the whole plants of Euphorbia dentata Michx - Ye Chang; Tian-Yi Chun; Xue Wen; Xiang-Ting He; Guo-Wei Zhang; Shuai Huang; Xian-Li Zhou (Biochemical Systematics and Ecology, 2026)

DNAzyme nanomotor-based logic biocomputing system for highly reliable intracellular microRNAs imaging and cancer cell identification - Xidong Li; Ting Huang; Lintao Wei; Wenfei Liao; Qianying Zhou; Mengxu Sun; Xun Fang; Jun Chen; Jin-Xiang Chen (Analytica Chimica Acta, 2026)

Coupling Coordination and Driving Mechanisms Between New-Type Urbanization and Ecosystem Service Value in the Beibu Gulf Urban Agglomeration - Qianxi Tan; Yijia Zhou; Ting Luo; Xiaoyue Li; Zhenzhen Li; Menglin Qin (International Journal of Environmental Research, 2026)

Single-cell multi-omics dissects transcript isoform and immune repertoire dynamics in human immunosenescence - Yuhui Zheng; Ze-Hui Ren; Yafei Yang; Wenteng Liu; Fupeng Li; Yajun Zuo; Tao Zeng; Xue Wang; Xiumei Lin; Xinyue Zhu; Baibing Guan; Wenwen Zhou; et al. (Science China Life Sciences, 2026)

Landscaping neurodevelopment of attention-deficit hyperactivity disorder - Ningning Liu; Yin-Shan Wang; Zi-Xuan Zhou; Peng Gao; Chongjing Luo; Xinyi Zhang; Ziqing Zhu; Yuan Gao; Fei Ren; Yan Zhu; Li-Zhen Chen; Haimei Li; et al. (Science Bulletin, 2026)

Cadmium induced ferroptosis of TM4 cells through PERK-ATF4-CHOP signaling pathway - Xuan Li; Juan Dai; Jiaoyang Wei; Yan He; Yue Han; Ting Zhou; Rui Li; Ling Zhang; Yuqin Shi (Reproductive Toxicology, 2026)

Systematic cadmium isotope fractionation between the organic and mineral fractions of soils - Jiawen Zhou; Tingting Mu; Ting Gao; Rebekah E.T. Moore; Mark Rehkämper; Yufang Sun; Zhen Zeng; Xinyang Li; Shijin Guo; Tong Zhou; Longhua Wu; Yongming Luo (Journal of Hazardous Materials, 2026)

Preparation of K2CO3-activated biochar from peanut shell and Chlorella for enhanced carbamazepine adsorption: Performance, mechanism, and reusability - Zhenzhen Li; Jiayu Wu; Ting Cheng; Liling Zhou; Yujia Yang (Journal of Environmental Management, 2026)

Integrating water use efficiency dynamics into ecological function zoning: Patterns, drivers, and trade-offs - Libin Zhang; Jiaxing Zhang; Qiang Ma; Jianzhu Li; Keke Zhou; Ting Zhang; Ping Feng (Environmental Research, 2026)

Ozone exposure and the risk of gestational hypertension in a northern Chinese city: Identifying the critical windows of exposure - Zhihua Gong; Pannan Li; Li Ma; Zhihong Li; Qinqin Tian; Ting Du; Yike Li; Yabin Hou; Yongnian Zhou; Guangke Li; Nan Sang (Environmental Pollution, 2026)

PFAS associated with dysglycemia and glucose trajectories: a prospective cohort study from the Isomers of C8 Health Project in China - Wen-Qi Yang; Yun-Ting Zhang; Wen-Yu Wang; Haseeb Tufail Moryani; Muhammad Amjad; Zeeshan Mohammed; Xuan Liu; Yan-Xu Chen; Kun Zhao; Chu Chu; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Co-exposure to PFAS, PFAS alternatives, and metals and liver function in Chinese adults - Shui-Yue Lu; Jing-Lin Zhang; Nuo Chen; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Xuan Liu; Yan-Xu Chen; Jia-Xin Zhou; Wen-Wen Bao; Yang Zhou; Li-Zi Lin; et al. (Environmental Pollution, 2026)

Efficient removal of acyclovir by UV/peracetic acid: A dual-function process for oxidation and disinfection - Zijun Dong; Feng Wang; Xiangsheng Chen; Jingyun Fang; Xuechuan Li; Ting Zhou (Chemical Engineering Journal, 2026)

Ultrasound-activated endoplasmic reticulum-targeting piezoelectric nanoagonist with auxiliary intrinsic efficacy reverses tumor immunosuppression via spatiotemporal ICD in ovarian cancer - Shuangshuang Cheng; Haojia Li; Yuwei Yao; Ting Zhou; Wan Shu; Jiarui Zhang; Tangansu Zhang; Guanglei Zhong; Guanxiao Chen; Xiaoyu Shen; Yingying Peng; Shuyang Yu; et al. (Chemical Engineering Journal, 2026)

Molybdenum-functionalized thiolated chitosan repurposes aqueous V(V) as an in situ PMS activator for simultaneous organic degradation and vanadium recovery - Yating Wu; Ting Xiang; Lei Zhang; Ping Gao; Lei Li; Chensi Shen; Fang Li; Juan Zhou (Chemical Engineering Journal, 2026)

Weight-optimized fusion of satellite precipitation over the Qinghai-Tibet Plateau: Comparison of machine learning approaches - Li Zhou; Chun Zhou; Zhongshun Gu; Yinan Guo; Ting Chen; Xiaojun Guo; Juan Du; Jiajia Yue; Keying Liu; Lingling Wu; Jingyuan Xue (Journal of Hydrology, 2026)

Temporal scale dictates the dominant driver of lake dynamics on the Tibetan Plateau - Ting Li; Yuanwei Wang; Lingxiao Wang; Lei Wang; Jing Zhou; Xiaoyu Guo; Jie Xu; Chenhao Chai; Zhaoyan Xie; Sichen Lin; Shiqi Ao; Xingjiao Zhang; et al. (Journal of Hydrology, 2026)

Time-dependent citrate-mediated precipitation inhibition in uranium column leaching: Mechanistic insights into pore evolution and uranium migration - Xiaowei Zhou; Jing Sun; Qian Li; Guangyue Li; Shangze Li; Ling Xiao; Hong Shu; Haiying Fu; Ting Li; Yongdong Wang; Zhao Cui; Guosen Xie (Journal of Hazardous Materials, 2026)

Atmospheric bulk deposition of microplastics in Jiuzhaigou World Natural Heritage Site: Tourism-associated divergence between particle number and polymer mass fluxes - Ting Liu; Yunqian Chen; Weiyang Xiao; Lv Zhou; Yutao Cao; Philip K. Hopke; Dongmei Liu; Jiangbin Shu; Hui Liu; Rongqiu Li; Xue Qiao (Journal of Hazardous Materials, 2026)

Wettability-switchable deep bed filtration for efficient oily wastewater treatment - Song Xichen; Yan Yaping; Zhang Tingting; Zhou Jianqiang; Wang Xiaojuan; Wang Zhezhe; Lin Jialong; Wang Ting; Song Xiaosan; Dai Liang; Wang Gang; Gao Suxia; et al. (Journal of Hazardous Materials, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Mechanistic insights into KOH-regulated biochar derived from waste Myriophyllum aquaticum biomass for 1O2-mediated degradation of 2,4,6-trichlorophenol - Guangya Zhou; Dong Zhang; Zhengzheng Lou; Miaomiao Zhao; Dihua Wu; Suling Zhang; Ying Pan; Ting Lü; Hongting Zhao; Jun Lin; Li Lu; Ming Zhang (Journal of Environmental Management, 2026)

Better representation of linear features in species distribution models: Mapping the distribution of the Scaly-sided Merganser (Mergus squamatus) - Yangsirui Zhang; Peizhong Liu; Lixing Gu; Li Wen; Ying He; Zijian Wang; Liangjun Zhou; Ting Lei; Cai Lu; Qing Zeng; Guangchun Lei (Journal of Environmental Management, 2026)

Associations between prenatal exposure to indoor air pollution and ambient particulate matter with infant growth - Jinlang Lyu; Tiantian Li; Shuang Zhou; Xin Yuan; Zheng Bao; Na Han; Gongbo Chen; Yuelong Ji; Qin Li; Jue Liu; Hui Wang; Jianlin Hu; et al. (Journal of Environmental Sciences, 2026)

Iodine vacancy-engineered BiOI steering selective singlet oxygen generation for high-flux antibiotic degradation with peroxyacetic acid activation - Yuchen Chu; Ting Zhou; Yuxi Zeng; Siying He; Jiawei Yue; Wenjun Wang; Yang Yang; Ziwei Wang; Fanzhi Qin; Hongda Liu; Xiaoming Li; Jie Liang; et al. (Chemical Engineering Journal, 2026)

Electron-networking Cu single atom-spurred Ru clusters for anion exchange membrane water electrolysis - Zihao Zhou; Rui Qin; Tingjie Mao; Pinlin Wang; Zhongliang Huang; Ting-shan Chan; Yu-cheng Huang; Zhiwei Hu; Xiaoqing Huang; Nanjun Chen; Yunhua Li (Chemical Engineering Journal, 2026)

Decoding immunotherapy resistance in multiple myeloma: genetic insights and approaches to counter resistance - Huan Li; Qi Xia; Mei Yu; Ying Lv; Jialing Xiao; Xiaoxin Guo; Kai Dong; Yu Zhou; Ling Zhong; Ting Wang; Weijia Wu; Chengzi Gan; et al. (Science China Life Sciences, 2026)

An overview of the formation mechanism characteristics of glacial lake outburst floods in Tibet, China - Jiankang Liu; Ruilin Xu; Linjun Zhou; Ting Yi; Jianxun Liu; Jiajia Zhang; Bo Gao; Yuanling Li; Hai Huang (Natural Hazards, 2026)

Reduced irrigation and phosphorus redistribution optimizes common vetch–mediated soil metabolic and microbial shifts suppress potato late blight - Ting Che; Shan Sun; Yilei Zhou; Chenxi Wu; Tingting Sun; Kangji Gao; Feng Hu; Huixin Li; Huijuan Zhang; Peiyi Zhao; Li Xu (Agriculture, Ecosystems & Environment, 2026)

Tumorigenesis of well-differentiated and dedifferentiated liposarcoma: 12q amplicon architecture, oncogenic cargo, and evolutionary progression - Aobo Zhuang; Xiao Zhou; Chengfei Xu; YangJu Chen; Xueling Wang; Runchun Li; Jiajing Hu; Yinxue Cheng; Yunyan Wan; Ting Wu; Wengang Li (Cancer and Metastasis Reviews, 2026)

A new species and a newly recorded species of the genus Hua (Gastropoda: Semisulcospiridae) from the Chishui River, Yunnan, China - Jian-Fu Wei; Yuan-Chao Chen; Xue-Hua Li; Guang-Can Zhou; Qi-Yan Zhu; Ting-Song Yu; Jun-Xing Yang; Xiao-Ai Wang (Molluscan Research, 2026)

Marine plastisphere expands the ecological niche and evolutionary dynamics of nrfA-dependent nitrite ammonifying bacteria - Ziqiu Lin; Shimei Pang; Ting Xu; Ying-Li Zhou; Chuanlun Zhang; Pei-Yuan Qian; Si Zhang (Water Research, 2026)

Haplotype-resolved long-read sequencing reveals parent-of-origin effects of tandem-repeat variation in autism spectrum disorder - Jinchen Li; Tengfei Luo; Xue Ren; Songyu Yang; Hui Quan; Yan Zhu; Senwei Tan; Xiangbin Jia; Pei Yu; Yuanfeng Huang; Zhaowei Jiang; Xudong Xiang; et al. (Science Bulletin, 2026)

Systematic characterization of FBP gene family in Saccharum reveals ScFBP3 as a key regulator of sucrose-mediated plant branching - Huiwen Zhou; Hanmin Luo; Minyi Wei; Ting Luo; Faqian Xiong; Ming Li; Lihang Qiu; Haifeng Yan (Plant Science, 2026)

PM2.5-bound organophosphate esters and childhood attention-deficit hyperactivity disorder symptoms: A population-based study from China - Chu Chu; Xuan Liu; Yan-Xu Chen; Jia-Xiang Dong; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Xia Liang; Yang Zhou; Muhammad Amjad; Yan Yang (NeuroToxicology, 2026)

Study on the synergistic effect of coal-oil co-liquefaction and analysis of liquefied oil products - Jin Jiang; Guanghua Yang; Ting Liu; Xiaodong Zhou; Xiaohui Li; Rui Sheng; Lang Liu (Fuel, 2026)

Rapid identification of binary and ternary adulteration in camellia oil by CRISPR/Cas12a assay - Ting Shi; Tenghui Dai; Jing Zhou; Juan Li; Lulu Zhang; Jieyu Cui; Xiaodong Ma; Junbiao Dai; Ailiang Chen; Xinjie Wang (Food Chemistry, 2026)

WITHDRAWN: Corrigendum to "H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing" [Chem. Eng. J. 469 (2023) 143398] - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2026)

Mitophagy activation for jawbone radiation injury therapy via angiogenesis/osteogenesis-active nanozymes - Tianxiao Wang; Weihua Shao; Ting Zhou; Yuchao Li; Ran Qin; Ziyu Chen; Jikang Cao; Xinyu Hu; Jingxuan Cang; Chang Sun; Yuli Wang; Huijun Jiang; et al. (Science China Life Sciences, 2026)

Response of greenhouse gas emissions, nitrogen loss and microbial communities to the presence of conventional and biodegradable microplastics in soil - Wenxu Li; Mengxiao Li; Jiaju He; Zhenyu Huang; Jian Zeng; Christopher W.N. Anderson; Minghua Zhou; Cheng Zhang; Xuesong Gao; Di Zhao; Ting Lan (Applied Soil Ecology, 2026)

Hydroxyapatite nanoparticles improve vitrified bovine MII oocyte developmental competence by reducing ultrastructural damage and modulating gene expression - Xiao-Xia Li; Yi-Hang Wang; Jun Wang; Shi-Yu Zhang; Jia-Hao Zhang; Shi-Han Zhao; Qi Yan; Ping-Hua Cao; Zi-Qiang Zhang; Chen Zhou; Zhen Zhang; Qiao-Ting Shi; et al. (Animal Reproduction Science, 2026)

Straw return coupled with subsoiling tillage reduces N₂O emissions and increases nitrogen content under long-term (12 years) trial in a coastal saline cotton field - Han Wang; Zhitao Liu; Qiyuan Guo; Lunxiao Shang; Longhao Zhou; Jiaxue Zhao; Ting Huang; Xiaoyu Li; Chenxi Shi; Baltaevich Ahmedov Miraziz; Xianliang Song; Xiaopei Zhang; et al. (Agriculture, Ecosystems & Environment, 2026)

SETD2 governs the regenerative threshold in the liver by gating STAT5-dependent Cox2 signaling - Liping Luo; Ting Chen; Yanzhu Long; Cheng Wang; Peipei Li; Xiaoqi Zhou; Zhengming Du; Tonglang Tang; Jinxuan Wang; Qingliang Zou; Limao Xu; Bo Liu; et al. (Science China Life Sciences, 2026)

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Palaeopolyploidy promoted ancient adaptation of Tibetan sclerophyllous oaks to aridity and cold triggered by mountain uplift - Jin-Jin Hu; Wen-Guang Sun; Jia Liu; Robert A. Spicer; Zhuo Zhou; Yong-Jiang Huang; Zhi-Min Li; Tao Su; Ting-Shen Han; He Tang; Lin-Bo Jia; Yun-Heng Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Inhibition and metabolic toxicity regulation of niacin on Staphylococcus aureus and its application in meat product preservation - Lei Tian; Xiangqi Bai; Chunyang Huang; Min Li; Ting Zhou; Chunling Zhang; Ying Yu; Hu Pan; Yanna Dai; Jifeng Pu; Chengyu Fu; Pengfei Zhang; et al. (International Journal of Food Microbiology, 2026)

Risk assessment, source apportionment and driving mechanism of soil heavy metals in coal mining areas of Xinjiang, China - Xin He; Fei Zhang; Ting Zhou; Boyu Wang; Xuan Zhang; Xiangyu Liu; Zia Ahmed; Mou Leong Tan; Ziheng Feng; Zhihui Li; Xu Ma (Gondwana Research, 2026)

Comprehensive insights into AphA-induced physiological alterations and molecular pathways in Vibrio alginolyticus - Yanni Zhao; Zi Wang; Xuan Wu; Hua Li; Ningning Zhou; Meiru Yan; Ting Shao; Xuefeng Chen; Huan Liu (Food Bioscience, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Human GBP1-neobaicalein targeted bacteria biomimetic nanodelivery system for dual inhibition of host efflux pumps and bacterial outer membrane to eliminate carbapenem-resistant gram-negative bacteria - Ling Wang; Cunze Wang; Jinglin Li; Xinhui Lin; Hongyuan You; Shasha Huang; Mohan Zhang; Zunjian Zhou; Wen Li; Ting Zhang; Shurong Gong (Chemical Engineering Journal, 2026)

A ultralong-life and high-capacity Mg/Na hybrid-ion battery using four-leaf clover-shaped CuSe2/(Cu, Co)Se2 cathode pairing with triglyme electrolyte - Ting Zhou; Tianli Han; Fengming Ma; Cheng Wang; Yunmiao Fan; Xuehui Wang; Haojun Xu; Jiawei Long; Jinjin Li; Huigang Zhang; Jinyun Liu (Chemical Engineering Journal, 2026)

Genome-wide analysis of sunflower (Helianthus annuus) and Orobanche cumana reveals HaEXLA2 and HaEXLB2 as negative regulators of lignin-based resistance - Lei Shen; Yi Duan; Ying Li; Wenya Zhang; Yan Fu; Ting Zhou; Hongju Sun; Ahsan Ayyaz; Ling Xu (Plant Cell Reports, 2026)

Lysosome-targeted copper-modulated carbon dots with near-infrared fluorescence imaging and enhanced photodynamic therapy effects - Ting Chen; Min Zhao; Yuanyuan Li; Yibing Wang; Beibei Zhao; Yanmei Zhou (Analytica Chimica Acta, 2026)

Atmospheric Boundary Layer Eco-Environment Shanghuang Observatory: An Integrated Multiscale Research Platform in Southeastern China for Understanding Boundary Layer Processes, Atmospheric Chemistry Feedback, and Extreme Weather–Climate Linkages - Zifa Wang; Xiaole Pan; Yele Sun; Jinyuan Xin; Hang Su; Junji Cao; Jie Li; Ting Yang; Hang Liu; Weijie Yao; Weiqi Xu; Xueshun Chen; et al. (Advances in Atmospheric Sciences, 2026)

Giardia duodenalis cysts induce bovine neutrophil extracellular trap formation - Yifei Li; Hongsen Yu; Tianyu Li; Xuhai Li; Ting Wu; Xiangyu Yan; Qixi Li; Chenhan Bu; Qi Sun; Jingjing Wang; Ershun Zhou; Zhengtao Yang (Veterinary Parasitology, 2026)

WS2-modified schwertmannite for highly efficient dye wastewater degradation via enhanced Fe cycle in heterogeneous Fenton-like catalysis - Kun Feng; Shuping Zhang; Neng Tao; Zhiyi Sun; Xianqiang Kong; Yuanyu Tan; Xuhao Liu; Lixiang Zhou; Pin Zhou; Yongjun Shen; Ting Li (Journal of Environmental Sciences, 2026)

Assembly processes of bacterial community and characteristics of keystone taxa in farmland soils under single cadmium and combined cadmium-chromium pollution - Hongmei Li; Yongxiu Deng; Guangwei Zhou; Daixi Zhang; Shirong Zhang; Guiyin Wang; Ting Li; Xiaoxun Xu; Xiaomei Pan; Yulin Pu (Journal of Environmental Sciences, 2026)

Insights into the effects of ultrasound on the structural, aggregation behavior, and functional properties of almond isolate protein: An integrated experimental and molecular dynamics simulation studies - Yu-Hang Jiang; Pi-Miao Huang; Yang-You Li; Yu-Ting Zhao; Yue Zheng; Yu-Xing Zhou; Wei-Gang Xin; Hua-Yi Suo (Food Research International, 2026)

A distinct zearalenone detoxification strategy mediated by cytochrome P450 - Ziwei Liu; Rouming Peng; Qian Li; Chun-Chi Chen; Lilan Xin; Kangkang Li; Jian-Wen Huang; Xin Liu; Xiaodong Zhang; Linzhen Hu; Shangwen Luo; Haibing Zhou; et al. (Food Chemistry, 2026)

Perfluorooctane sulfonate (PFOS) induces Caspase-8-mediated pyroptosis via GSDMD and GSDME to drive retinal disease: Evidence from epidemiological and experimental studies - Lu-Yin Wu; Li-Xia Liang; Jia-Xin Zhou; Yun-Ting Zhang; Zeeshan Mohammed; Muhammad Amjad; Yang Zhou; Zhi Wang; Guang-Hui Dong; Wen-Wen Bao (Environmental Pollution, 2026)

Efficient fabrication of PLA/PBAT/ZnO films with inverted-pyramid Micro/nanostructures for robust anti-wet pack and antimicrobial protection - Yu Du; Rong Zhou; Kai Mu; Congyuan Zhang; Changjun Guo; Jiabao Lu; Zihao Li; Heng Xie; Ting Wu; Jinping Qu (Chemical Engineering Journal, 2026)

Zwitterionic nanoparticle-mediated interfacial hydration for robust, salt-rejecting, and anti-fouling solar steam generation - Jianbin Zhang; Yuhao Zhai; Zhichao Chen; Ting Lv; Dianming Li; Yanhua Liu; Yanping Wang; Wufang Yang; Baoli Ou; Libang Feng; Feng Zhou (Chemical Engineering Journal, 2026)

Early Biological Orchestration in Fracture Healing: Decoding the Crosstalk between Inflammation, Coagulation, and Metabolism - Linyuan Xue; Jiyixuan Li; Minglu Hao; Sha Zhou; Ying Yang; Ting Liu; Lei Zhang; Bing Liang; Yingze Zhang; Dongming Xing (Stem Cell Reviews and Reports, 2026)

Probiotic novel strain Lactobacillus reuteri MRD01 alleviates dextran sulfate sodium-induced colitis in male mice by promoting intestinal barrier integrity - Ying Li; Guoao Ding; Guoan Bao; Xiaojun Lai; Ruxin Ye; Ting Wang; Yujie Du; Ke Xiao; Peng Zhou; Jingjing Wang; Xin Xia; Yan Zhang (Antonie van Leeuwenhoek, 2026)

Two new C 19 -diterpenoid alkaloids from Delphinium potaninii var. bonvalotii - Li-Li Ye; Qiao Long; Ye Chang; Ting-Ting Li; Lin Chen; Shuai Huang; Xian-Li Zhou (Natural Product Research, 2026)

Vascular endothelial growth factor (VEGF)-related blood flow regulation and anti-inflammation in the protection of Danzhu Fuyuan Granules against cognitive impairment - Yu Duan; De-Wei Zhu; Qin Liu; Xing-Yuan Li; Xiao-Ting Zhou; Jing-Qing Hu; Ai-Jun Liu (Metabolic Brain Disease, 2026)

An impact-based drought classification method using real-world agricultural drought records and explainable automated machine learning - Keke Zhou; Jianzhu Li; Ting Zhang; Xiaogang Shi; Ping Feng (Journal of Hydrology, 2026)

Crystal phase-dependent ZrO2 for fluoride adsorption in hydrochloric acid - Qian Wu; Xin Huang; Shiyu Sun; Yan Li; Fengzhen Liu; Xin Chen; Na Wang; Ting Wang; Zijian Zhou; Bin Lu; Hongxun Hao (Journal of Environmental Chemical Engineering, 2026)

Multi-target antidiabetic peptides from highland barley (Qingke): Identification, molecular docking, and inhibitory mechanisms against α-amylase, α-glucosidase, and DPP-IV - Juan Li; Muyan Ma; Feng Liang; Yan Du; Wenju Zhou; Pin Ma; Falin Zhang; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li (Food Chemistry, 2026)

Endometrial microbiota-dimethylglycine-Treg cell axis affects endometrial receptivity in recurrent implantation failure - Fen-Ting Liu; Ping Zhou; Feng Deng; Bao-Ying Liao; Zi Yang; Di Sun; Heng Pan; Yang Yu; Shuo Yang; Rong Li (Science China Life Sciences, 2026)

The occupations of microblade technology populations at Jiangjunbu02 site on the northeastern Tibetan Plateau and their relationships with paleoenvironment changes - Yuanxin Li; Juanting Yao; Xuke Shen; Linxueyi Wang; Yan Zhou; Huan Xia; Dongpeng Lin; Lin Chen; Yongxiu Lu; Jian Wang; Ting Cheng; Yan Zhao; et al. (Science China Earth Sciences, 2026)

Protective role and mechanism of sonic hedgehog signaling pathway in spinal cord injury - Li Li Yin; Xiao Zhen Ji; Min Tang; Li Hui Chen; Jiu Zhou Lin; Ya Ling Jin; Wei Ting Chen (Molecular & Cellular Toxicology, 2026)

The GATA3-RFPL3-ASK1 axis suppresses breast cancer growth and lung metastasis - Kang Li; Chang Liu; Jun-Hui Yin; Yu-Ting He; Zhi-Zhi Xu; Wen-Jing Zhang; Jian-Qi Wang; Lu-Yao Hou; Jing Feng; Le-Min Lin; Xiu-Qing Duan; Yi Zhou; et al. (Apoptosis, 2026)

Decumbic acid derivatives from soil fungus Lasiodiplodia sp. BG1083 - Hong-Qiao Dai; Xiao-Bing Su; En-Tao Zhou; Wen-Ting Li; Shuang-Shuang Chen; Hui-Yang Cao; Lin Hu; Meng-Yuan Jiang (Natural Product Research, 2026)

Data fusion enhances the accuracy of soil organic carbon estimation by using high accuracy surface modeling - Wei Zhou; Ting Wang; Yao Peng; Wenping Yu; Xiaofang Sun; Yongzhong Tian; Saibo Li; Zhengping Du; Tianxiang Yue (Soil and Tillage Research, 2026)

Chronological and climatic insights from Karst Cave Silt Sediment in Southwest China - Yuan-Yuan Mu; Qing-Duo Wang; Chang-Sheng Wang; Tian-Zhou Zhang; Shao-Qin Ma; Jing-Ming Yang; Hai-Cheng; Wen-Jun Sun; Jun-Yun Li; Yan-Min Dong; Lu-Peng Yu; Ting-Yong Li (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Quorum sensing-driven biofilm cathode of Shewanella oneidensis for enhanced uranium adsorption: Elucidating the role of exogenous AHLs and validation in actual uranium-contaminated groundwater - Jing Sun; Hong Shu; Xiaoyan Wu; Tingting Liu; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou; Zhongran Dai; Qian Li (Journal of Hazardous Materials, 2026)

Breakthroughs in new pollutant research: Analytical methods, environmental processes, toxicological mechanisms, and control strategies - Lu Jiang; Yali Shi; Lu Bai; Qiang Zhao; Hanyong Peng; Xiaoxi Yang; Yanna Liu; Guangbo Qu; Qunfang Zhou; Yumiao Sun; Jianjie Fu; Jiyan Liu; et al. (Journal of Environmental Sciences, 2026)

Plasmid-mediated modulation of Listeria monocytogenes biofilm formation via TCS/PTS signaling: Implications for food contamination control - Jing Wang; Hui-Min David Wang; Yang Qu; Ting Lin; Changyan Zhou; Zijie Lin; Yangtai Liu; Zhuosi Li; Qingli Dong; Yujuan Suo (Food Research International, 2026)

Effects of polystyrene nanoplastics on tomato plant growth, fruit yield and quality - Mingyuan You; Ting Zhou; Jiahui Yan; Jingyue Ma; Tingting Kong; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Food Chemistry, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

ESIRA, a novel framework integrating efficacy and safety for evaluating first-line treatments in advanced hepatocellular carcinoma - Hai-Long Li; Hui Zhou; Yi-Yang Zhang; Jin-Ting Lai; Zhen-Zhong Zhou; Jing-Yi Huang; Song-Bin Guo; Yu Wang; Wei-Juan Huang; Xiao-Peng Tian (Science China Life Sciences, 2026)

Understanding the role of C5a/C5aR1-mediated complement activation pathway in tumor progression and therapy resistance - Lemei Zheng; Jianxia Wei; Mengna Li; Changning Xue; Qingqing Wei; Zubing Wu; Xiaolong Li; Ting Zeng; Huizhen Xin; Wei Xiong; Hongyu Deng; Ming Zhou (Science China Life Sciences, 2026)

Symbiotic interaction of Chlorella sp. and Shinella sp. for enhanced dissolved organic matter removal from sterilized mixed wastewater - Rumeng Lu; Qiaoyun Huang; Yunpu Wang; Xian Cui; Zhigang Yu; Naif Abdullah Al-Dhabi; Xiang Wang; Roger Ruan; Wangwang Tang; Zihan Li; Ting Zhou; Yuhuan Liu; et al. (Algal Research, 2026)

Health risk assessment of emerging organic contaminants from land-applied biosolids: A comparative study between the U.S. and China - Ting Zhou; Xuan Li; Huan Liu; Shiman Dong; Jing Sun; Saravanamuthu Vigneswaran; Qilin Wang (Water Research, 2026)

Active packaging based on nanocellulose-stabilized essential oil pickering emulsions: A review on enhanced properties and food preservation applications - Fan Li; Mengmeng Pang; Kun Liu; Shasha Lv; Quanfen Guo; Peide Cui; Wanqing Lei; Wei Liu; Xing Zhou; Ting Xu; Chuanling Si (Trends in Food Science & Technology, 2026)

Ochratoxin A induces intestinal barrier impairment and concurrent hepatorenal toxicity in broiler chicks via modulation of autophagy, ferroptosis, and the intestinal microbiota - Qixi Li; Ting Wu; Yueqing Xie; Mingzhen Jiang; Xuhai Li; Hongsen Yu; Ershun Zhou; Zhengtao Yang; Jingjing Wang (Research in Veterinary Science, 2026)

γ-lactam and γ-lactone-containing sesterterpenoids from Colquhounia coccinea var. mollis with immunosuppressive activity - Shu-Xi Jing; Chun-Huan Li; Yan-Chun Liu; Ting-Ting Zhou; Ran Fu; Shi-Hong Luo; Yu Zheng; Xiao-Nian Li; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Corrigendum to “Accessibility of floating wind turbines via walk-to-work: SWATH vs. monohull service vessels” [Ocean. Eng. (342), Part 4, 30 December 2025, 123043] - Ting Zhou; Binbin Li; Kun Liu; Wei Huang; Chenyu Wang; Lei Yang (Ocean Engineering, 2026)

Spatiotemporal patterns of artificial forest expansion and their driving mechanisms for carbon sink enhancement in China (2005–2019) - Si-Yu Li; Xing-Peng Wei; Yuan Meng; Yu-Ting Yang; Zi-Yi Zheng; Jing-Xuan Zhou; Wang-Bo Yuan; Hong-Gang Ni (Land Use Policy, 2026)

Inflammation mediates the association between per- and polyfluoroalkyl substance exposure and kidney function: Integrating epidemiological and animal evidence - Li-Xia Liang; Wen-Wen Bao; Chu Chu; Lu-Yin Wu; Muhammad Amjad; Yun-Ting Zhang; Wan-Ting He; Jing-Wen Huang; Li-Zi Lin; Yang Zhou; Ling-Zhang Meng; Kun Ye; et al. (Journal of Hazardous Materials, 2026)

Microbial metabolism-mediated transformation of dissolved organic matter: Linking antecedent dry-weather degradation to first-flush effects in urban wet-weather overflows - Hao Chen; Xiaonan Ji; Jing Li; Yu Li; Ting Zhang; Weiqi Zhou (Journal of Environmental Chemical Engineering, 2026)

Numerical investigation on combustion behavior of an X-type rotary engine: Impact of hydrogen enrichment and engine speed - Run Zou; Lei Zhang; Ting Hou; Yanhong Zhou; Wei Yang; Lijun Lei; Feng Li (Fuel, 2026)

Deciphering the microbial complexity of Chinese traditional sourdough through integrated learning - Yan Liu; Jinyu Wang; Shiwei Zhou; Feijiang Li; Honghong Cheng; Zheqing Zhu; Jiale Wang; Aowen Liu; Ting Lu; Yujuan Yu; Senmiao Tian; Min Zhang; et al. (Food Research International, 2026)

A novel flavonol-based self-assembled sensor with high sensitivity to biogenic amines and application in detection of fish and prawn freshness - Huan Huang; Guocheng Zhou; Zhiyuan Meng; Ting Li; Linfeng Sun; Zhonglong Wang; Yiqin Yang (Food Control, 2026)

Te-Cu dual adsorption-conversion function cathode enables high-energy-density and long-lifespan liquid metal batteries - Weixin Zhang; Xin He; Ting Zhang; Haomiao Li; Shuai Yan; Xianbo Zhou; Yewei Guo; Min Zhou; Wei Wang; Kai Jiang; Kangli Wang (Chemical Engineering Journal, 2026)

Corrigendum to “Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression” [Chem. Eng. J. 527 (2026) 171844/ CEJ_171844] - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Unlocking dual-pathway peroxydisulfate activation mechanism in single atom Fe-based catalytic membranes for wastewater purification - Ting Zhou; Fupeng Wang; Xuechuan Li; Wenyi Dong; Mengke Qiang; Weigang Liu; Hongjie Wang (Bioresource Technology, 2026)

Icariside II sensitizes osteosarcoma to doxorubicin through the lincROR/Wnt/β-catenin signaling regulatory axis - Shu-ting Zhou; Zhi-peng Li; Yong-xin Mai; Yu-Yan Wang; Feng-xiang Pang; Jin-fang Zhang; Xian-lin Wu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Simulation and Experimental Study of Vessel-Borne Active Motion Compensated Gangway for Offshore Wind Operation and Maintenance - Hongyan Mu; Ting Zhou; Binbin Li; Kun Liu (Journal of Marine Science and Engineering, 2026)
Driven by global initiatives to mitigate climate change, the offshore wind power industry is experiencing rapid growth. Personnel transfer between service operation vessels (SOVs) and offshore wind turbines under complex sea conditions remains a critical factor governing the safety and efficiency of operation and maintenance (O&M) activities. This study establishes a fully coupled dynamic response and control simulation framework for an SOV equipped with an active motion-compensated gangway. A numerical model of the SOV is first developed using potential flow theory and frequency-domain multi-body hydrodynamics to predict realistic vessel motions, which serve as excitation inputs to a co-simulation environment (MATLAB/Simulink coupled with MSC Adams) representing the Stewart platform-based gangway. To address system nonlinearity and coupling, a composite control strategy integrating velocity and dynamic feedforward with three-loop PID feedback is proposed. Simulation results demonstrate that the composite strategy achieves an average disturbance isolation degree of 21.81 dB, significantly outperforming traditional PID control. Validation is conducted using a ship motion simulation platform and a combined wind–wave basin with a 1:10 scaled prototype. Experimental results confirm high compensation accuracy, with heave variation maintained within 1.6 cm and a relative error between simulation and experiment of approximately 18.2%. These findings demonstrate the framework’s capability to ensure safe personnel transfer by effectively isolating complex vessel motions and validate the reliability of the coupled dynamic model for offshore operational forecasting.

Development of a Novel Experimental System for Simulating the Whole Grouting Process of Diffusion–Filling–Splitting in Deep Rock Engineering - Xia-Ting Feng; Xi-Fan Li; Yang-Yi Zhou; Cheng-Xiang Yang; Tian-Xiang Song (Rock Mechanics and Rock Engineering, 2026)

Tracking seasonal variability in plant traits from spaceborne PRISMA and NEON AOP across forest types and ecoregions - Fujiang Ji; Ting Zheng; Alexey N. Shiklomanov; Ruqi Yang; Philip A. Townsend; Fa Li; Dalei Hao; Hamid Dashti; Kyle R. Kovach; Hangkai You; Junxiong Zhou; Min Chen (Remote Sensing of Environment, 2026)

Immunosuppressive spirocyclic labdane diterpenoids from Holocheila longipedunculata - Xiu-Ying Bai; Shu-Xi Jing; Ting-Ting Zhou; Yu Zheng; Yan Liu; Sheng-Hong Li (Phytochemistry, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

A fluorescence biosensor based on upconversion nanoparticles and metal organic frameworks for multiresidue detection and enrichment of neonicotinoid pesticides - Huan Yun; Honglin Li; Zijie Dou; YuHao Zhang; Ting Guo; Ying Zhou; Hongyuan Zhou; Liang Ma; Xiaozhu Liu (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Co-occurrence and reduction mechanisms of microbe-derived dissolved organic nitrogen and nitrous oxide in an oxygenic photobiofilm - Ting Ran; Yu Zhou; Xiaocai Cui; Qian Li; Yangrui Huang; Yun Zhou (Chemical Engineering Journal, 2026)

Non-lytic nanozyme hydrogel for the treatment of fungal keratitis by silent pathogen eradication and host inflammation suppression - Na Li; Xia Qi; Li Ma; Xiaoyu Zhang; Yuxin Liu; Shijiu Chen; Fengmei Shan; Qun Wang; Qingjun Zhou; Ting Wang; Hongwei Wang; Weiyun Shi (Chemical Engineering Journal, 2026)

Causal links between pandemics and weather and air pollution in 39 cities, 2020–2021 - Ting Shi; Bo Zhou; Ailin Qi; Kai Wang; Yunpeng Ao; Chenyi Li; Yuling Zhang (Atmospheric Pollution Research, 2026)

Vacuolar K⁺ efflux transporter TaTPK1-5D confers low-K⁺ tolerance of ‘Zhengmai 136’ through interaction with TaCIPK23-4D in bread wheat - Yingna Feng; Qianni Wei; Sisi Sun; Hongbing Zhang; Ting Zhou; Rui Cui; Wenxu Li; Yunqi Liu; Yingpeng Hua; Zhengfu Zhou (Theoretical and Applied Genetics, 2026)

A Novel Palmitoylation-Related Molecular Signature for Predicting and Therapeutically Targeting Alzheimer’s Disease - Xiuling Miao; Kaiyu Luo; Yinglei Li; Yang Zhou; Meng Wei; Ting Zhang; Yazhuo Hu; Heran Wang; Jianjun Jia (Molecular Neurobiology, 2026)

Sustainable tea production in western Sichuan: Defining optimal soil pH threshold to balance rhizosphere bacterial communities and flavor metabolites - Haojie Cao; Ning Ma; Siyu Wang; Ting Li; Zijun Zhou; Shirong Zhang; Yulin Pu; Yongxia Jia; Xiaojing Liu; Xiaoxun Xu; Guiyin Wang (Applied Soil Ecology, 2026)

Isovitexin accelerates diabetic wound repair via coordinated angiogenesis and collagen remodeling: Mechanistic insights from cellular and streptozotocin-induced SD rat models - Ting-ting Chen; Li-qin Xu; Zhi-gang Gao; Wei-wei Zhou; Yan Ying (Tissue and Cell, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

Hydrolase-oxidase responses mediate distinct carbon dynamics following wetland conversion to paddy versus upland systems - Lifei Su; Yi Liu; Lishan Tan; Xiangling Zhou; Ting Wang; Yinyin She; Jiafang Huang; Yuanbin Cai; Shihua Li; Pingping Guo; Min Luo (Soil Biology and Biochemistry, 2025)

Accessibility of floating wind turbines via walk-to-work: SWATH vs. monohull service vessels - Ting Zhou; Binbin Li; Kun Liu; Wei Huang; Chenyu Wang; Lei Yang (Ocean Engineering, 2025)

Synergistic control of antibiotic resistance via natural illite-activated peroxymonosulfate: Efficiency and mechanism - Xiangqin Zhou; Ting Zhou; Jiuqiang Xiong; Wenjun Wang; Yingbin Li; Long Li; Xiang Tang; Zhuotong Zeng; Biao Song; Chengyun Zhou; Jing Tong (Journal of Hazardous Materials, 2025)

Photodegradation of sulfisoxazole during nitrite-sensitized photolysis - Xu Gao; Xiaoyu Li; Yaowu Xu; Xinyu Zhan; Ting Zhou; Bing Zhou; Xin Wang; Yuhang He; Chunyu Wang; Han Mao (Journal of Environmental Chemical Engineering, 2025)

Synergistic effects of biochar-immobilized Stenotrophomonas acidaminiphila on potassium availability and ryegrass productivity in purplish soil - Tingrui Zhang; Wei Wei; Jinchuan Xie; Zijun Zhou; Yulin Pu; Yongxia Jia; Xiaojing Liu; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Ting Li (Journal of Environmental Management, 2025)

Hofmeister and electrostatic modulation of the structure and polymorphism of rice protein fibrils - Dong Wang; Chuping Zhang; Jianfen Ye; Mengdi Chen; Jiangtao Zhou; Ting Li; Juan Li; Xinxia Zhang; Li Wang (Food Chemistry, 2025)

Efficient lithium extraction from salt lakes brine via regulating the electric double-layer interface of high-loading film electrodes with CMC Li - Yawen Gao; Luxiang Ma; Xin Zeng; Zhixiang Li; Ting Li; Chunxi Hai; Tiandong Chen; Yanxia Sun; Shengde Dong; Xin He; Qi Xu; Xiaowang Wu; et al. (Desalination, 2025)

A customizable woven asymmetric fabric for efficient synergistic water-electricity coproduction from saltwater - Luxin Li; Jiansong Luo; Wenxi Liao; Jiajia Deng; Ting Wang; Yanyan Huang; Jianming Deng; Huang Zhou; Yuxin Yang (Desalination, 2025)

Intelligent inversion analysis of seepage parameters for deep overburden dam foundations based on an improved grey wolf optimization algorithm - Qiaogang Yin; Yanlong Li; Wenwei Li; Lifeng Wen; Ye Zhang; Ting Wang; Tao Yang; Tao Zhou (Computers and Geotechnics, 2025)

Hydrogen bonding enforced supramolecular multifunctional nanocoating for implant osseointegration - Junhong Qiu; Qianqian Qiu; Jiawei Yang; Weilong Tang; Jiarong Xu; Yujie Chen; Hao Cai; Yuqi Wan; Zhilin Yu; Conrado Aparicio; Zhihua Li; Zhou Ye; et al. (Chemical Engineering Journal, 2025)

Gut microbiota-mediated immunomodulation underlies the anti-tumor effects of a novel ginseng polysaccharide - Chaoyu Li; Shengjin Zhou; Siyu Chen; Zhen Xu; Qinbing Xue; Hao Wang; Ting Liu; Wei Chen; Jie Feng; Jingjing Chen; Miao Yu; Bing Wang; et al. (Carbohydrate Polymers, 2025)

Characterizing 3D flash drought events and exploring flash drought propagation in the North China Plain, China - Siyao Zhang; Keke Zhou; Jianzhu Li; Ting Zhang; Ping Feng (CATENA, 2025)

Association between short-term exposure to ambient fine particulate matter & components and the risk of spontaneous abortion - Jialiang He; Wenzheng Zhou; Xin Ming; Yunping Yang; Ziyi He; Yannan Li; Ting Dong; Xinzhen Chen; Min Zhang; Yankun Wang; Yubin Ding; Wei Zhou (Atmospheric Pollution Research, 2025)

Correction: Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2025)

Aquaporins: a novel perspective in the treatment of lung diseases - Mengyuan Wu; Zhiming Miao; Fuxian Liu; Sichao Dai; Yangyang Li; Ting Zhou; Qihong Zhuo; Huanhuan Zhang; Zhangbo Song; Haiyi Nie; Wenxing Yong; Liying Zhang; et al. (Inflammation Research, 2025)

IL-8 promotes pyroptosis through ERK pathway and mediates glucocorticoid resistance in chronic rhinosinusitis with nasal polyps - Wei Zhang; Yun Lei; Ting Zhang; Bo You; Jie Zhang; Yong Zhou; Shaocong Zhang; Xueru Li; Yuting Liu; Lianqin Shen; Jianmei Zhao; Jing Chen (Inflammation Research, 2025)

A standard for geological evaluation of urban underground space resources in the Beijing plain - Han-han He; Cheng-shan Wang; Jing He; Yuan-xin Zhou; Lei Wang; Stuart Marsh; Chao Li; Tong-ming Fang; Fang-zhen Li; Sheng-li Cao; Jing Liu; Yi-ting Zhao (Bulletin of Engineering Geology and the Environment, 2025)

Comparison of Muscle Texture Characteristics and Nutritional Composition Between Gene-Edited Intermuscular-Bone-Free Crucian Carp and Other Varieties - Huijie Zhou; Zhipeng Sun; Tan Zhang; Tingting Zhang; Ting Yan; Huan Xu; Mingliang Wei; Yashan Yin; Na Li; Youyi Kuang; Guangxiang Tong (Fishes, 2025)
The intermuscular-bone-free crucian carp (Carassius auratus, WUCI), developed through CRISPR/Cas9-mediated bmp6a and bmp6b knockout, offers advantages in consumer acceptance and processing efficiency. However, its effects on muscle texture and nutritional quality have not been fully elucidated. In this study, we compared the F3 generation of WUCI with its sibling wild-type crucian carp (Carassius auratus, WT), Songpu silver crucian carp (Carassius gibelio var. Songpu, SPYJ), and Fangzheng silver crucian carp (Carassius gibelio var. Fangzheng, FZYJ), focusing on muscle texture characteristics and nutritional attributes. WUCI exhibited significantly higher shear force but lower hardness than most comparison groups, with no substantial differences in muscle fiber morphology. Amino acid profiles were similar among all groups. WUCI showed lower crude fat content than WT but higher than FZYJ, and comparable levels of polyunsaturated fatty acids (PUFA), n-3 fatty acids, docosahexaenoic acid (DHA), and eicosapentaenoic acid (EPA) to WT and SPYJ. These findings indicate that the knockout of bmp6a and bmp6b does not alter muscle mass in crucian carp, supporting the potential of WUCI for commercial adoption as a gene-edited consumer-oriented fish product.

Distribution, sources, and health risks of PM2.5 and PM1-bound polycyclic aromatic hydrocarbons in the Pearl River Delta - Guang-Hong Zhai; Yue Wen; Mo Yang; Qi-Zhen Wu; Wan-Ting He; Li-Xia Liang; Le-Bing Wang; Yun-Ting Zhang; Jing-Wen Huang; Jia-Xin Zhou; Min Li; Gao Meng; et al. (Environmental Monitoring and Assessment, 2025)

Copper-Induced Nephropathy: Clinical Characterization of 36 Cases and Comprehensive Literature Review - Yi-Ling Li; Jing Chen; Jin-Rong Zhang; Ting-Ting Zhou; Jian-chao Peng; Zhi-Xin Huang; Kang Nong; Michael Aschner; Yue-Ming Jiang (Biological Trace Element Research, 2025)

Reply to “Methodological appraisal of estimating the prevalence and related factors of antenatal depression in China” - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Plasma-activated water: A novel approach to modulating main pectin, hemicellulose and cellulose metabolism in goji berry cell walls - Kai-Ping Cong; Ting-Ting Li; Cai-E. Wu; Gong-Jian Fan; Dan-Dan Zhou; Xiao-Jing Li; An-Di Suo (Postharvest Biology and Technology, 2025)

Scour prediction, monitoring, and protection measures for offshore wind turbines: Recent advancements and insights - Jingcheng Cui; Ting Bao; Xuanming Ding; Chong Tang; Tianbo Li; Weizhen Zhou (Ocean Engineering, 2025)

Biogenic jarosite coating as an innovative passivator for acidic uranium residue stabilization using Acidithiobacillus ferrooxidans - Shangze Li; Ling Xiao; Jing Sun; Qian Li; Guangyue Li; Zhao Cui; Ting Li; Xiaowei Zhou (Journal of Hazardous Materials, 2025)

Nanostructure-enhanced Raman spectroscopy for sensitive and on-site monitoring of anabolic-androgenic steroids in food and drug products - Na Zhou; Yu Zeng; Ting Li; Qiuwen Huang; Yushi Chen; Siqing Liu; Xiaojun Luo; Xiaojun Deng (Food Chemistry, 2025)

The effect and mechanism of NCOA4-mediated ferritinophagy in aluminum-induced ferroptosis of PC12 cells - Ruifeng Liang; Jiafen Zhang; Yan Luo; Yizhe Yang; Ting Zhou; Siyi Li; Jiawei Liu; Bingbing Zhang; Qiao Niu; Hongmei Zhang; Xiaojiang Qin; Junhong Gao (Food and Chemical Toxicology, 2025)

A multi-dimensional approach to assessing source-oriented health risks from heavy metals in coal mining regions - Mengjing Ni; Farui Jiang; Kunyu Li; Qi Liu; Xun Shu; Ting Li; Zijun Zhou; Shirong Zhang; Yulin Pu; Yongxia Jia; Xiaojing Liu (Environmental Pollution, 2025)

Dipyridinium salt-enhanced type II ROS photodynamic antibacterial nanofiber films for long-term preservation of blueberries - Xue-Qi Zhang; Xiuxian Zhu; Fei Guo; Zi-Ming Zhou; Yu-Ting Zhao; Lin-Xuan Song; Zhao-Yang Zhi; Zi-Hui Liang; Zhen-Ke Li; Chang-Hai Yi; Zhen Wang (Chemical Engineering Journal, 2025)

Progress of sludge dewatering and disposal based on electrochemical treatment processes: A critical review - Youpeng Cai; Yifu Li; Zhijin Peng; Lean Zhou; Wei Zhang; Yang Gao; Jinting Wang; Shiquan Sun; Ting Xiong (Chemical Engineering Journal, 2025)

Enhanced arsenite removal in water using multifunctional UiO-66-NH2 embedded chitosan biocomposite beads: defects, oxidation and adsorption - Yuxin Li; Zhimin Wang; Yuanfeng Wei; Ting Wang; Maosong Zhao; Jie Luo; Jun Zhou; Zhaoshuang Li; Kai Yin; Chengbin Liu (Chemical Engineering Journal, 2025)

Cascading effects of tree diversity loss on herbivore-parasitoid interactions - Ming-Qiang Wang; Kai Zhang; Georg Albert; Sylvia Haider; Yi Li; Jing-Ting Chen; Andréa Davrinche; Qing-Song Zhou; Arong Luo; Tobias Proß; Keping Ma; Helge Bruelheide; et al. (Biological Conservation, 2025)

Synthesis and antitumor evaluation of oleanolic acid acylhydrazone derivatives - Juan Cai; Bo-Wen Pan; Liang-Liang Zheng; You-Ping Tian; Zhang-Chao Dong; Li-Juan Liu; Ting-Ting Feng; Ying Zhou; Xiong-Wei Liu; Yang Shi (Molecular Diversity, 2025)

CAR19-T/NK cell and circular aptamer–drug conjugate (ApDC) combination treatment increases immunotherapy efficacy - Ling-Qi Kong; Su-Yun Chen; Xu Cui; Ya-Hui Hu; Lian Wang; Jia-Yao Zhu; Lan-Xuan Guan; Bing-Kun Wang; Li-Ting Yang; Kai-Ming Chen; Chao-Ming Zhou (Molecular and Cellular Biochemistry, 2025)

Eco-intensified recovery of acetonitrile and ethanol from industrial wastewater via heat-integrated reactive pressure-swing distillation - Jian Zhai; Ting Li; Xueke Zheng; Qingbo Sun; Chunbo Hao; Xuefei Leng; Ping Zhao; Jinwen Li; Yuran Zhou (Process Safety and Environmental Protection, 2025)

Metal bioaccumulation and lipid response in aquatic ecosystem: Evidence of machine learning from Chaohu Lake, China - Qi Lu; Zhi Yuan; Wei Chang; Shen-dong Xu; Lan-lan Wu; Gang Liu; Li-yan Yang; Si-ting Liu; Meng-xue Gao; Yi-fan Hu; Xu-dong Zhang; Huan Zhou; et al. (Journal of Hazardous Materials, 2025)

Heteroaggregation between polystyrene micro(nano)plastics and dibutyl phthalate mediates toxicity reduction in macroalgae: Physiological and transcriptomic evidence from Gracilariopsis lemaneiformis - Yuanxia Li; Xiaoqian Zhang; Nianjun Xu; Mingze Chen; Wenting Tang; Na Zhou; Ting Zeng; Xue Sun; Zeming Zhang (Journal of Hazardous Materials, 2025)

Highly efficient stabilization of arsenic in the contaminated sediments of Jiehe River by schwertmannite to inhibit arsenic release into overlying water - Weichen Luo; Ting Li; Yan Dong; Yujun Zhou; Zhaodi Wu; Xuan Liu; Jiahao Ni; Jingang Xu; Dejin Zhang; Mingjiang Zhang; Di Fang; Lixiang Zhou (Journal of Hazardous Materials, 2025)

Quantifying the relative contributions of key drivers to future changes in PAHs health risks over the Yangtze River Delta: A multi-scenario modeling approach - Ning Nie; Ting Li; Xinran Liu; Xiaodan Guan; Shilun Zhou; Min Liu; Dengzhong Zhao (Journal of Hazardous Materials, 2025)

Acid-resistant ZrO2/PPy nanocomposite for efficient fluoride removal from hydrochloric acid - Yan Li; Xin Huang; Fengzheng Liu; Sanli Yin; Zijian Zhou; Bin Lu; Ting Wang; Na Wang; Hongxun Hao (Journal of Environmental Chemical Engineering, 2025)

Efficient removal of metals and resource recovery from acid mine drainage by modified chemical mineralization coupling sodium sulfide precipitation - Ting Li; Fange Cheng; Xin Du; Jianru Liang; Lixiang Zhou (Journal of Environmental Sciences, 2025)

Phosphate perils in marine aquaculture: Systematic toxicity assessment in turbot juveniles in cultivation - Lele Wu; Xin Li; Jiale Zhou; Ting Qi; Yaolin Li; Xiefa Song; Zongcheng Song; Xian Li (Journal of Environmental Sciences, 2025)

Sequential fermentation with Kluyveromyces marxianus and yogurt starter cultures produces stirred fermented milk with reduced lactose and enhanced natural flavor - Yu-Ting Feng; Yan-Ru Zhou; Chang-Cheng Li; Shu-Jun Guo; Zhen-Peng Gao; Chun-Feng Guo (Innovative Food Science & Emerging Technologies, 2025)

Effect of low-energy stirring temperature on the formation of oil-in-water emulsions stabilized by gelatin-arginine complexes - Jun Qi; Yu-cong Li; Hui-min Yan; Li-ting Zeng; Ao-jing Lv; Rui-ling Dong; Xue-qing Li; Zhou Lin; Le-le Shao; Lang Zhang; Guo-qing Duan; Chun-hui Zhang; et al. (Food Research International, 2025)

Purification, identification, and mechanism of action of novel antioxidant peptides from quinoa (Chenopodium quinoa wild.) protein hydrolysate - Huan-Huan Xiao; Xue-Ying Li; Ying-Ying Chen; Jin-Xiang Zhou; Ting Zhang; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Unsupervised SAM segmentation of zebrafish body: Application to melanin analysis - Yuan Meng; Jing-Xuan Zhou; Yu-Ting Yang; Xing-Peng Wei; Si-Yu Li; Hong-Gang Ni (Environmental Pollution, 2025)

Impact of system size on pattern transitions in dissolving rough fractures: experiments, multi-physics coupling simulations and theoretical analysis - Ting Wang; Yaning He; Yanlong Li; Ran Hu; Yang Zhou; Yifeng Chen; Junrui Chai; Yunhe Liu (Computers and Geotechnics, 2025)

Protein engineering and flow reactor design for anchored peptide-mediated continuous biocatalysis - Huan Li; Chun-Jiang Ma; Ya-Ting Gao; Qing-qing Zhou; Huan Chen; Feng Cheng; Ya-Ping Xue; Yu-Guo Zheng (Chemical Engineering Journal, 2025)

Bamboo-inspired self-descaling tubular evaporators with a Janus-confined water layer for rapid and durable hypersaline brine desalination - Yi-Zhou Chen; Ting Shen; Jia-Hui Xin; Yu Zhang; Kai Li; Ling-Shu Wan; Hao-Cheng Yang; Zhi-Kang Xu (Chemical Engineering Journal, 2025)

Single-atom iron-decorated hierarchically porous carbon nanofibers with carbon vacancy-enhanced performance for zinc-air batteries and supercapacitors - Haihan Zhou; Qianqian Wang; Bingyu Zhang; Jing Li; Ting Ou; Hua-Jin Zhai; Jiangwei Zhang (Chemical Engineering Journal, 2025)

Characteristics and influencing factors of loess terraces’ preferential flow under different typical vegetation cover - Shengnan Li; Ce Zheng; Ting Lu; Kexin Zhou; Yidong Gu; Bihui Wang; Yudong Lu (Plant and Soil, 2025)

Machine learning and network toxicology reveal arsenic as a key driver of non-carcinogenic health risks from heavy metal residues in Chinese medicinal plants - Guangying Du; Yuanju Zhang; Ting Zou; Chang Liu; Yingyue Hou; Jing Li; Feifei Deng; Jiayi An; Li Feng; Bangna Wu; Lingdan Huang; Ying Zhou (Science of The Total Environment, 2025)

Prevalence and related factors of antenatal depression in 11 provinces and cities of China: a 100,000 population-based study - Chen Zhang; Chenchi Duan; Han Liu; Hualin Xu; Cheng Li; Jianxia Fan; Hong Li; Xiangjuan Li; Yi Guo; Yeping Wang; Xiufeng Li; Jing Li; et al. (Science Bulletin, 2025)

Arabidopsis HSFA1b functions as a heat sensor inhibiting OST1-mediated stomatal closure through its adenylate-cyclase activity - Yu Zhang; Ru-Feng Song; Xiao-Yu Hu; Hui Zhou; Wei Wang; Junli Zhang; Xin Zhang; Liu-Mei Li; Su-Ting Wang; Yuwei Song; Fuyou Xiang; Jingjing Xing; et al. (Molecular Plant, 2025)

S-vacancy-rich MoS2 for enhanced BPA degradation involved peroxymonosulfate activation: sustainable transformation of toxic V(V) into a homogeneous catalyic system - Jingjing Liu; Shanqi Liang; Ting Xiang; Lei Li; Pin Gao; Juan Zhou (Journal of Water Process Engineering, 2025)

Unveiling the multifunctional roles of karrikin as a novel phytohormone in cadmium detoxification of bread wheat (Triticum aestivum L.) - Ting Zhou; Yu-shan Xiao; Yong-le Fu; Hao Li; Rui Cui; Ying-na Feng; Zheng-fu Zhou; Ying-peng Hua (Journal of Hazardous Materials, 2025)

Shapley additive explanations revealed the effects of climate, topography, anthropogenic activities and geochemical properties on soil cobalt, nickel and vanadium contents - Zhiqiang Bai; Fangyi Li; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Xiaomei Pan; Qinmei Zhong; Wei Zhou; Yulin Pu; Yongxia Jia (Journal of Hazardous Materials, 2025)

Biodiversity and nitrogen metabolism in the plastisphere impacted by urban nitrogen loading from a coastal mega-city - Ziqiu Lin; Shimei Pang; Yunchao Wu; Ting Xu; Ying-Li Zhou; Hao Li; Chuanlun Zhang; Pei-Yuan Qian; Si Zhang (Journal of Hazardous Materials, 2025)

Dose-dependent molecular composition of dissolved organic matter in biochar-amended manure composts - Nennen Zhu; Ao Cheng; Xufang Yu; Xiaolong Liu; Ting Li; Xiujuan Zhou; Wenchao Ji; Xingjun Fan (Journal of Environmental Management, 2025)

Impact evaluation of coastal protection forest program on carbon sequestration change in East China - Hanle Xu; Ting Zhou; Shunbin Yao; Qigang Xu; Guozhi Li; Wu Yang (Journal of Environmental Management, 2025)

Switching low-temperature CO2 hydrogenation product selectivity over metal–organic framework derived Co-based catalyst - Yan-Ting Li; Ying-Fei Huo; Yun-Yan Zhong; Lei Zhou; Min Feng; Tong-Liang Hu (Fuel, 2025)

Effect of layered grinding on the distribution and binding forms of protein and polyphenols in highland barley bran - Muyan Ma; Feng Liang; Wenju Zhou; Pin Ma; Chengjun Ji; Yan Du; Zhaoxin Tu; Li Wang; Xinxia Zhang; Ting Li; Juan Li (Food Bioscience, 2025)

Quantitative assessment of heat tolerance in new rice varieties through field survey during natural extreme heat events - Ting Sun; Tianhui Miao; Jianan Hu; Haoyang Zhou; Minglu Li; Jiayi Zhang; Yuanyuan Pan; Ran Bi; Shenghao Ye; Menglei Wei; Zeyu Wu; Guoqiang Li; et al. (European Journal of Agronomy, 2025)

Monoatomic Fe-N2O2 sites and carboxyl groups in biochar synergistically driving HV-Fe(IV) dominated peroxymonosulfate activation for anilines degradation - Ting Zhou; Wenyi Dong; Xuechuan Li; Weigang Liu; Mengke Qiang; Hongjie Wang (Chemical Engineering Journal, 2025)

Synergistic degradation mechanism of roxithromycin by the combination of TiO2/graphene oxide/polypropylene fiber photocatalytic network and microalgae - Wei Gao; Xiangjie Pan; Junzhuang Wu; Ting Guan; Feng Cai; Jiangang Han; Yanwen Zhou; Jian Qiu; Wei Li (Chemical Engineering Journal, 2025)

ZmDof08, a zinc finger transcription factor, plays critical roles in photosynthesis in maize - Ting Li; Jinjie Guo; Jiahao Zhang; Ping Deng; Yuanyuan Xu; Xinjia Li; Yu He; Lian Zhou; Chaofeng Li; Chaoxian Liu (Plant Cell Reports, 2025)

Empagliflozin Promotes Revascularization in Diabetic Mice Hindlimb Ischemia by Improving Vascular Endothelial Cell Function - Hanjie Liu; Yingfan Li; Xiaoqi Zhou; Ting Chen; Yuanyuan Liu; Shuai Hu; Cheng Wang; Qing Wang; Jianxiong Xu; Xiangyu Zhou; Yang Shen; Chaoping Yu; et al. (Cardiovascular Toxicology, 2025)

Cadmium induces autophagy via IRE1 signaling pathway activated by Ca2 + in GC-2spd cells - Yue Han; Juan Dai; Jinxin Cheng; Yan He; Chengkun Zhao; Rui Li; Yaqin Zhang; Ling Zhang; Ting Zhou; Yuqin Shi (Reproductive Toxicology, 2025)

Ionic liquid-induced regulation of 0D/2D tea biomass carbon quantum dots modified PbBiO2Cl nanosheets: Accelerated charge transfer and boosted photocatalytic activities - Qingsong Hu; Yanbing Liu; Meng Ye; Ting Zhou; Mingyang Li; Wei Jiangs; Binxian Gu (Journal of Water Process Engineering, 2025)

Expanding scales: Achieving prediction of van Genuchten model hydraulic parameters in deep profiles by incorporating broad in situ soil information in pedotransfer functions - Yongping Tong; Yunqiang Wang; Jingxiong Zhou; Xiangyu Guo; Ting Wang; Yuting Xu; Hui Sun; Pingping Zhang; Zimin Li; Ronny Lauerwald (Journal of Hydrology, 2025)

Integrating multi-omics and biomarkers to reveal the stress mechanisms of high fluoride on earthworms - Zhiqiang Bai; Daixi Zhang; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Xiaomei Pan; Qinmei Zhong; Wei Zhou; Yulin Pu; Yongxia Jia (Journal of Hazardous Materials, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

A green approach to CO2 capture using fly ash-based catalysts: Performance and mechanistic insights - Rui Zhang; Lianghong Zhou; Ting Li; Yingjie Niu; Haonan Liu; Ruqi Xiao; Chao’en Li; Francesco Barzagli (Fuel, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Collapse performance of steel modular building under corner module loss: Full-scale test and analysis - Jing-Zhou Zhang; Yi-Ting Deng; Guo-Qiang Li; Ke Cao; Xin Chen; Zhi-Wei Yu (Engineering Structures, 2025)

Nicotianamine facilitates zinc translocation from roots to shoots in the nickel hyperaccumulator Odontarrhena chalcidica - Teng-Hao-Bo Deng; Ya-Zhou Wang; Bing-Lan Mo; Ting Liu; Lei Li; Ye-Tao Tang; Dian Wen; Yong-Dong Huang; Sheng-Sheng Sun; Xu Wang; Rui-Ying Du; Jean-Louis Morel; et al. (Plant and Soil, 2025)

Six Weeks of Moderate-Intensity Treadmill Exercise Improves Intestinal Barrier and Intestinal Inflammation in Parkinson’s Disease Mice - Ting Li; Sheng-Yang Zhou; Wei Quan; Yu Zhou; Jian Wu; Li-Ping Zhao; Chen-Meng Qiao; Wei-Jiang Zhao; Chun Cui; Yan-Qin Shen (Molecular Neurobiology, 2025)

New Insights Into the Phylogeny and Biogeography of Goji Berries ( Lycium , Solanaceae) Inferred From Plastid Data - Gulbar Yisilam; Kenneth M. Cameron; Zhi‐Yong Zhang; En‐Ting Zheng; Chuan‐Ning Li; Zhen‐Zhou Chu; Ying Su; Jia‐Lei Li; Yu‐Wei Wang; Jin Li; Pan Li; Xin‐Min Tian (Journal of Biogeography, 2025)
Aim Lycium L. (Solanaceae), which is known for producing goji berries, is an important plant with both medicinal and edible uses. This genus is globally distributed in temperate and subtropical regions. However, a comprehensive phylogeny and evolutionary history of this plant group is lacking so far. This study was executed to produce novel insights into the phylogenetic relationships and evolutionary history of this small but economically important genus. Location North America, South America, Hawaii, Africa and Eurasia. Taxon Lycium L. (Solanaceae). Methods We established a phylogenetic framework for Lycium based on complete plastome sequences and data from 80 protein‐coding genes across 43 Lycium species using maximum likelihood and Bayesian inference methods. Furthermore, 14 species from the Solanaceae family were used as outgroups. Additionally, two Solanoideae fossils and one secondary calibration point were used to estimate divergence times and reveal the biographical history of these plants through ancestral area reconstruction. Results Our analysis revealed that six North American Lycium species were strongly supported as monophyletic with high support and were sister clades to the remainder of the genus. The remaining species from North America, South America and the Hawaiian Islands shared a common ancestor, whereas all species from Africa, Saharo‐Arabia and Eurasia formed a distinct clade. Our results indicated that Lycium originated in North America during the Late Oligocene and then dispersed to Hawaii and South America, from there to Africa, and then further to Saharo‐Arabia, with a more recent dispersal to Eurasia. Main Conclusions Our plastid genome data confirmed that Lycium originated in North America and identified long‐distance dispersal as the key to its global distribution. Genomic insights facilitate species identification and contribute to conservation efforts.

Influence of biochar on DOM formation in chicken manure composting: spectral properties and molecular weight analysis - Xiaolong Liu; Nennen Zhu; Ao Cheng; Xiujuan Zhou; Dan Chen; Ting Li; Xufang Yu; Wenchao Ji; Xingjun Fan (Environment, Development and Sustainability, 2025)

Tissue and cell types infected by Ecytonucleospora hepatopenaei (EHP) - Yuan Wang; Shi-ting Lin; Ming Zhao; Peng Di; Jun-fang Zhou; Shou-hu Li; Yan-qing Huang; Ying Na; Xin-cang Li; Wen-hong Fang (Journal of Invertebrate Pathology, 2025)

Risk prioritization and experimental validation of per- and polyfluoroalkyl substances (PFAS) in Chaohu Lake: Based on nontarget and target analyses - Wei Chang; Shen-Dong Xu; Ting Liu; Lan-Lan Wu; Si-Ting Liu; Gang Liu; Jian Sun; Ye-Xin Luo; Lei Gao; Hao Li; Qi Lu; Zhi Yuan; et al. (Journal of Hazardous Materials, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Collagen targeting BMSCs-derived extracellular vesicles coupled with decellularized tendon scaffold for anterior cruciate ligament reconstruction - Jie Wang; Jing Cui; Liang-Ju Ning; Yan-Jing Zhang; Fei Xing; Lei-Lei Zhao; Hui-Min Liu; Xuan Li; Min Zhu; Jing-Cong Luo; Zhou Xiang; Ting-Wu Qin (Chemical Engineering Journal, 2025)

Holocene Indian Summer monsoon cyclic oscillations revealed by Qionghai Lake sediments and their influence on civilization evolution - Xiaomei Zhang; Gen Wang; Yongli Wang; Zhifu Wei; Ting Zhang; Xueyun Ma; Zelong Li; Xinyu Huang; Shixin Zhou (CATENA, 2025)

Deformation and Cracking Evolution Mechanism of Surrounding Rock in Deep Clastic Rock Tunnels: A Scaled-Down Excavation Experimental Study - Feiyan Wang; Xia-Ting Feng; Yangyi Zhou; Xiaojun Yu; Chengxiang Yang; Bentong Sun; Fudong Li; Honglin Luo (Rock Mechanics and Rock Engineering, 2025)

Climatic characteristics and interannual influencing factors of extreme cyclones in the arctic cold season - Ting Qin; Hong-Li Ren; Shuo Zhao; Chenguang Zhou; Li Gao; Fei-Fei Jin (Climate Dynamics, 2025)

Discovery of structurally intriguing diterpenoids as anti-neuroinflammatory agents from mangrove plant Excoecaria agallocha L. via inhibiting macrophage polarization and inflammasome - Jun-Yi Li; Ming-Bin Chen; Ting-Ting Fu; Fei-Fei Liu; Jin Liu; Cong-Jun Xu; Jing Zhou; Yong Rao; Zhong-Ping Jiang; Ling Huang (Phytochemistry, 2025)

EHDPP impairs intestinal microbiota homeostasis and induces placental injury through choline mediated gut-placenta axis - Ting Du; Saifei Lei; Zhenyao Huang; Xin Liu; Zhou Jiang; Minlan Lu; Yiyang Zhou; Jiali Yuan; Weiyi Song; Hao Gu; Jing Li (Journal of Hazardous Materials, 2025)

Identification and characterization of aldo-keto reductase responsible for patulin degradation in Saccharomyces cerevisiae - Chao Yang; Lingxuan Huang; Chen Hu; Jieqiong Yao; Ting Zhou; Xiu-Zhen Li; Stephen Y.K. Seah; Bangzhu Peng (Food Chemistry, 2025)

Highland barley functional tea extract alleviates alcoholic liver disease by modulating gut microbiota and reducing hepatic oxidative stress and inflammation in mice - Juan Li; Zhaozhan Liu; Yan Du; Zhiming Zhong; Zhaoxin Tu; Wenju Zhou; Zhengxing Chen; Li Wang; Xinxia Zhang; Ting Li (Food Bioscience, 2025)

Bridging the mercury exposure threshold: Development and application of whole-cell biosensors incorporating biotransformation pathways - Xue-ying Liu; Yan Guo; Wen-qi Zhang; Jiao Bai; Bing-chan Ma; Li-ting Zhou; Chang-ye Hui (Environmental Research, 2025)

Chemical constituents of Ainsliaea fragrans and their chemotaxonomic significance - Xiao-Ting He; Yun-Na Wang; Xue-Mei Zhou; Jing-Jing Zhang; Xiao-Li Li; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

Activation of NR2A-Wnt-TLR2 Signaling Axis in Satellite Glial Cells of the Dorsal Root Ganglion Contributes to Neuropathic Pain Induced by Nerve Injury in Diabetic Mice - Yan-Yan Zhang; De-Xin Zhu; Mu-Yun Wang; Ya-Ting Yi; Yu-Heng Feng; Cheng Zhou; Chun-Jie Li; Fei Liu; Jie-Fei Shen (Molecular Neurobiology, 2025)

Capillary flow of hybrid mode for enhancement of flow rate on μTADs - Yixi Shi; Haonan Li; Hao Chen; Xionghui Li; Muyang Zhang; Qinghao He; Jie Zhou; Jiahua Zhong; Xinyi Chen; Huiru Zhang; Lok Ting Chu; Weijin Guo (Analytica Chimica Acta, 2025)

Lithium-bearing pegmatite identification, based on spectral analysis and machine learning: a case study of the Chaibeiyuan area, NW China - Bin Zhou; Jinggang Gao; Ting Liang; Jiqing Li; Fucheng Yu; Shanping Li; Xijuan Tan; Yonggang Feng (Advances in Space Research, 2025)

Seasonal Variation of Phyllosphere Microbial Communities Under Warming - Chaotang Lei; Shu‐Yi‐Dan Zhou; David T. Tissue; Roy Neilson; Zhiyang Lie; Ting Wu; Xujun Liu; Chushu Meng; Xu Li; Dong Zhu; Juxiu Liu (Global Change Biology, 2025)
The phyllosphere is a complex microbial ecosystem residing on plant leaves, hosting microbes that influence plant growth and fitness. The phyllosphere is sensitive to temperature and moisture, so understanding its response to climate warming and variable moisture associated with changes in seasons is crucial for predicting ecosystem function. We conducted a 12‐year warming experiment in a sub‐tropical forest by transplanting a natural ecosystem from higher to lower elevations. We sampled phyllosphere microbial communities across wet and dry seasons for three consecutive years (years 10–12) to assess potential adaptation strategies to warming. Phyllosphere microbial community structure and diversity varied seasonally, with higher bacterial richness in the dry season; however, warming reduced bacterial richness across seasons. Co‐occurrence networks revealed stronger microbial interactions in the dry season, which exhibited reduced connectivity under warming. Community assembly was largely stochastic, with warming enhancing species turnover and dispersal. Notably, plant probiotics, enriched in the wetter season with greater environmental disturbances, played a key role in adaptation to seasonal changes and warming. Seasonal shifts in microbial function were observed: wet‐season bacteria were enriched in carbohydrate and energy metabolism, while dry‐season bacteria showed elevated sulfur metabolism, reflecting adaptive metabolic strategies to environmental conditions. Our study enhances the understanding of the seasonal patterns of phyllosphere microbial communities and the impact of climate warming, offering new insights into plant–microbial adaptation strategies in response to climate change.

Organic fertilizer intensifies the vertical heterogeneity of DOM in paddy fields through interactions with soil minerals - Yi Xiao; Rong Huang; Weiliang Xiong; Binbin Liu; Qinghua Zhou; Tao Jiang; Vanessa N.L. Wong; Jiang Liu; Yingjie Wu; Youlin Luo; Qiquan Li; Qiang Xu; et al. (Soil and Tillage Research, 2025)

Enhancing fruit quality through unraveling the molecular and physiological basis and preventing cracking in jujube (Ziziphus jujuba Mill.) - Hong-Xiang Zhou; Run-Zhe Wang; Wen-Ting Luo; Yang Liang; Shi-Yu Liu; Juan Chen; Ji-Qing Peng; Yan-Xia Fan; Shu-Zhan Li; Chuan Guo; Zi-Qiang Zhang; Feng-Xia Shao; et al. (Postharvest Biology and Technology, 2025)

Multi-signal fluorescent probe for simultaneous differentiation and imaging of Hg2+, Cys, Hcy, and GSH in living cells and zebrafish - Yang Li; Jing Li; Ting Yu; Hongyi Cai; Youyu Zhang; Haitao Li; Huijun Zhou; Peng Yin (Journal of Hazardous Materials, 2025)

Study on the improvement of Rye bread quality by bacterial Laccase derived from Streptomyces coelicolor - Ran Zhang; Yanhua Li; Yuan Gao; Fengyun Wang; Peng Zhou; Yan Zhang; Ying Li; Kaiyue Wang; Ting Rui; Guilan Zhu; Jingjing Wang; Zemin Fang (Journal of Cereal Science, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

Antioxidant and antimicrobial PSE-like chicken protein isolate films loaded with oregano essential oil nanoemulsion for pork preservation - Chen-Yan Zhu; Ke Li; Yu Wang; Man-Ting Du; Bo Chen; Yun-Tao Wang; Yan-Fang Zhou; Yan-Hong Bai (Food Chemistry, 2025)

Enhanced authentication of organic milk using MALDI-TOF MS with combined lipid-peptide fingerprinting and machine learning integration - Minrui Zhou; Ting Li; Lingling Shen; Qisheng Zhong; Taohong Huang; Ting Zhou (Food Chemistry, 2025)

Exposure-effect of PFOS and PFOA on lung function: An integrated approach with epidemiological, cellular, and animal studies - Jia-Xin Zhou; Xiao-Di Qin; Xuan Liu; Wan-Ting He; Mohammed Zeeshan; Shyamali C. Dharmage; Jennifer Perret; Dinh Bui; Yun-Ting Zhang; Ming-Kun Sun; Jing-Wen Huang; Li-Xia Liang; et al. (Environmental Research, 2025)

Seismic damage prediction of rockfill dams based on crest settlement and missing data imputation - Zhou Zheng; Yanlong Li; Ye Zhang; Lifeng Wen; Ting Wang; Lei She; Tao Yang (Engineering Structures, 2025)

Mycorrhizal growth and resource exchange define plant’s coexistence - Jiqiong Zhou; Pengsen Wang; Xiangjun Li; Li Wei; Yakov Kuzyakov; Yingying Su; Jianguo Zhang; Nan Huang; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; et al. (Plant and Soil, 2025)

The light-responsive transcription factor SlBBX20 improves low-temperature resistance of Solanum lycopersicum by affecting photosynthetic capacity, antioxidant capacity, and osmotic adjustment - Yongbo Ma; Manling Chen; Yingjin Xing; Zhenglun Li; Ting Zhou; Haijing Yan; Jiahui Yan; Songshen Hu; Guobin Li; Xiaohui Hu; Xiaojing Li (Plant Cell Reports, 2025)

Rubrolithibacter danxiaensis gen. nov., sp. nov. isolated from red sandy conglomerate in the Danxia Mountain - Wen-Hui Lian; Huan-Huan He; Ying Wang; Zhuo-Huan Zheng; Fang Chen; Ting Zhou; Chao-Jian Hu; Jia-Rui Han; Lei Dong; Wen-Jun Li (Antonie van Leeuwenhoek, 2025)

Long-term phosphate exposure effects on juvenile turbot (Scophthalmus maximus): Growth, metabolism, and adaptive responses - Xin Li; Lele Wu; Jiale Zhou; Yaolin Li; Ting Qi; Xiefa Song; Zongcheng Song; Xian Li (Marine Pollution Bulletin, 2025)

Three-dimensional dynamic simulation of the rice root system under different phosphorus concentrations - Le Yang; Lan Long; Shirong Ai; Qiangqiang Zhou; Wenhui Li; Ting Liu (Biosystems Engineering, 2025)

Transcription factor AcAGL9 and AcBEH1 synergistically regulate carotenoid biosynthesis during pineapple fruit ripening - Mengting Liu; Ting Li; Rufang Deng; Zhengke Zhang; Yijie Zhou; Xuewu Duan; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Tea biomass carbon quantum dots mediated Bi12O17Cl2 nanosheets for enhanced photocatalytic activities: Promoting the activation of molecular oxygen - Yanbing Liu; Ting Zhou; Mingyang Li; Meng Ye; Jianjian Yi; Binxian Gu; Qingsong Hu (Journal of Environmental Chemical Engineering, 2025)

Impacts of forest expansion on microbial diversity and community assembly in fragmented mountain ecosystems - Wen-Hui Lian; Wen-Sheng Zhao; Jia-Rui Han; Chao-Jian Hu; Guo-Yuan Shi; Fang Chen; Mei-Xiang Li; Ling-Xiang Yue; Shuai Li; Mukhtiar Ali; Lei Dong; Ting Zhou; et al. (Environmental Research, 2025)

Robustness of column-supported modular steel buildings in column loss: Role of double-layer beams and point-restrained slabs - Jing-Zhou Zhang; Yi-Ting Deng; Guo-Qiang Li; Zhi-Wei Yu (Engineering Structures, 2025)

Modeling diabetic cardiomyopathy using human cardiac organoids: Effects of high glucose and lipid conditions - Xiangyu Wang; Xin Tan; Ting Zhang; Shuai Xu; Yiyao Zeng; Anchen Xu; Xian Li; Ge Zhang; Yufeng Jiang; Hezi Jiang; Jili Fan; Xiaohong Bo; et al. (Chemico-Biological Interactions, 2025)

TonguExpert: A Deep Learning-Based Algorithm Platform for Fine-Grained Extraction and Classification of Tongue Phenotypes - Ting Li; Ling Zuo; Pengyu Wang; Liangfu Yang; Zijia Liu; Xu Wang; Jingze Tan; Yajun Yang; Jiucun Wang; Yong Zhou; Li Jin; Guangtao Zhai; et al. (Phenomics, 2025)

Histaminergic Innervation of the Ventral Anterior Thalamic Nucleus Alleviates Motor Deficits in a 6-OHDA-Induced Rat Model of Parkinson’s Disease - Han-Ting Xu; Xiao-Ya Xi; Shuang Zhou; Yun-Yong Xie; Zhi-San Cui; Bei-Bei Zhang; Shu-Tao Xie; Hong-Zhao Li; Qi-Peng Zhang; Yang Pan; Xiao-Yang Zhang; Jing-Ning Zhu (Neuroscience Bulletin, 2025)
The ventral anterior (VA) nucleus of the thalamus is a major target of the basal ganglia and is closely associated with the pathogenesis of Parkinson’s disease (PD). Notably, the VA receives direct innervation from the hypothalamic histaminergic system. However, its role in PD remains unknown. Here, we assessed the contribution of histamine to VA neuronal activity and PD motor deficits. Functional magnetic resonance imaging showed reduced VA activity in PD patients. Optogenetic activation of VA neurons or histaminergic afferents significantly alleviated motor deficits in 6-OHDA-induced PD rats. Furthermore, histamine excited VA neurons via H1 and H2 receptors and their coupled hyperpolarization-activated cyclic nucleotide-gated channels, inward-rectifier K + channels, or Ca 2+ -activated K + channels. These results demonstrate that histaminergic afferents actively compensate for Parkinsonian motor deficits by biasing VA activity. These findings suggest that targeting VA histamine receptors and downstream ion channels may be a potential therapeutic strategy for PD motor dysfunction.

Modulation of Preceding Tibetan Plateau Tropospheric Thermal Anomaly on Summer Temperature Anomalies in the Yangtze and Huaihe River Valleys - Di Li; Ting Zhang; Ge Liu; Jingpeng Liu; Changyan Zhou; Dongmei Qi; Yuhan Feng; Yuwei Zhou (International Journal of Climatology, 2025)
Anomalous warm surface air temperatures (SATs) appeared in eastern China, especially the middle and lower Yangtze and Huaihe River valleys (MLYHRV), in the summer of 2022. Using the 2022 SAT anomaly as a case, this study analyses the reasons for the variation of summer SATs in the MLYHRV and explores the precursory signals for the summer MLYHRV SAT and related mechanisms. The findings indicate that the preceding May mid‐upper (500–300 hPa) tropospheric temperature (TT) over the Arabian Sea and India and the western Tibetan Plateau (TP) can reflect the persistence of the TT anomaly over the western TP and its eastward extension to the Japan Sea from May to summer, which causes downstream East Asian circulation (i.e., the South Asian high and western Pacific subtropical high) and related SAT anomalies over the MLYHRV during summer (especially July–August). In addition, the May La Niña SST can reflect the summer La Niña SST pattern and therefore affect the summer MLYHRV SAT by modulating the East Asian circulations. Using TT and SST precursory signals, a statistical prediction model was developed to predict the summer MLYHRV SAT. This model based on the TT and SST signals shows better prediction ability than the model based only on the traditional La Niña SST signal. The May ASI‐WTP TT may be regarded as a crucial supplementary precursor for forecasting the summer MLYHRV SAT.

Provincial responsibilities and compensations in water pollutant transfers in China - Huiping Li; Baiqin Zhou; Yaxian Li; Ting Zhou; Mengxian Hu; Hui Huang; Yujun Wang; Weihai Pang (Process Safety and Environmental Protection, 2025)

Bifunctional nanobody facilitates a colorimetric and fluorescent dual-mode immunoassay of Staphylococcal enterotoxin A - Yao Zhang; Di Liu; Yudong Tian; Min Li; Yuhuan Li; Ting Zhou; Qin Zhao; Min Zhang; Ying Yu; Hu Pan; Yanna Dai; Zhuoma Dawa; et al. (Food Chemistry, 2025)

Microbiological, physicochemical, textural, and rheological properties of fermented soymilk produced with Enterococcus faecium and Lactiplantibacillus plantarum - Chang-Cheng Li; Shu-Jun Guo; Yu-Ting Feng; Yan-Ru Zhou; Yue Li; Zhen-Peng Gao; Chun-Feng Guo (Food Chemistry, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Atomic-scale anisotropic local electric field of BiOCl for enhanced photoelectrochemical seawater reduction - Fei Wang; Wenbin Li; Zengtao Lv; Linxing Meng; Baiyang Zhou; Ting Ding; Zhuo Zhang; Zaixing Yang (Chemical Engineering Journal, 2025)

Plasma processing of artificial corneal endothelium for the treatment of bullous keratopathy: Basic research and clinical application - Xiaoyu Zhang; Zhen Shi; Hongwei Wang; Suxia Li; Xin Wang; Zongyi Li; Xiuli Sun; Tan Li; Long Zhao; Ting Wang; Qingjun Zhou; Weiyun Shi (Chemical Engineering Journal, 2025)

Machine learning-based prediction of non-aeration linear alkylbenzene sulfonate mineralization in an oxygenic microalgal-bacteria biofilm - Libo Xia; Beibei Wu; Xiaocai Cui; Ting Ran; Qian Li; Yun Zhou (Bioresource Technology, 2025)

Synergistic contribution of soil moisture and sea surface temperature to summer Tibetan Plateau temperature - Ting Zhang; Ge Liu; Mingkeng Duan; Yuhan Feng; Yuwei Zhou; Xin Mao; Xinchen Wei; Jingxin Li (Atmospheric Research, 2025)

The Systematic Analysis of the Impact of China Water Improvement and Fluoride Reduction Project on Children - Bo Yang; Feiqing Wang; Xu Yang; Jinyang Cheng; Juan Chen; Bingbing Li; Ying Zhou; Xiaoxu Chen; Bo Wei; Xiaoshuang Yuan; Ting Tian; Dongxin Tang; et al. (Biological Trace Element Research, 2025)

Biochar enhanced co-composting for peat-free seedling substrate: A win-win solution for sustainable development of modern vegetable industry - Xiaoxia Fan; Yiyuan Wei; Dan Song; Ting Zhou; Ronghua Li; Xiaoxuan Su; Tao Zhang; Shang Cheng; Ran Xiao (Process Safety and Environmental Protection, 2025)

Ticks jump in a warmer world: Global distribution shifts of main pathogenic ticks are associated with future climate change - Bo Cao; Chengke Bai; Kunyi Wu; Ting La; Wenwen Chen; Lianjin Liu; Xiaofang Zhou; Chong Chen; Xian Li; Yiyang Su; Lingyu Che; Guishuang Li (Journal of Environmental Management, 2025)

Using isotope-tracer method with deuterium for quantitative study of hydrogen activation mechanism in direct coal liquefaction - Xiao-Dong Zhou; Xue-Long Yin; Lang Liu; Xue-Li Huang; Jing-Mei Liu; Ting Liu; He Lin; Feng-Yun Ma (Fuel, 2025)

Toxicological interactions of cosmetic and personal care additives mixtures: An update based on measurement and simulation - Yu-Ting Yang; Zi-Yi Zheng; Xing-Peng Wei; Yuan Meng; Jing-Xuan Zhou; Si-Yu Li; Wang-Bo Yuan; Hong-Gang Ni (Environmental Research, 2025)

A case study from a critical stopover site in the East Asian-Australasian Flyway provides lessons for optimal high-tide roost management to support shorebird conservation - Jia Guo; Waner Liang; Yan Zhou; Yifei Jia; Hongyan Yang; Lili Sun; Qing Chen; Ting Fu; Sicheng Ren; Wenkui Jiang; Guangchun Lei; Li Wen (Biological Conservation, 2025)

Tauroursodeoxycholic acid targets HSP90 to promote protein homeostasis and extends healthy lifespan - Jia-Yu Liu; Yao Wang; Yue Guo; Run-Qi Zheng; Yun-Ying Wang; Yan-Yan Shen; Yan-Hong Liu; Ai-Ping Cao; Rui-Bo Wang; Bo-Yang Xie; Shuai Jiang; Qiu-Ying Han; et al. (Science China Life Sciences, 2025)

Grevillosides R-S: glucosides of 5-alkylresorcinol derivatives from roots of Ardisia crispa (Thunb.) A. DC - Xing-xiang Long; Shuang Zhang; Li-juan Xiang; Rui-hang Hu; Ting-ting Feng; Ying Zhou; Xin Yin (Natural Product Research, 2025)

Immunosuppressive leucosceptrane-type sesterterpenoids with antipodal cyclopentenones isolated from Leucosceptrum canum - Kai Guo; Shi-Hong Luo; Yan-Chun Liu; Ting-Ting Zhou; Yan Liu; Sheng-Hong Li (Phytochemistry, 2025)

The miR172a–SNB module orchestrates both induced and adult-plant resistance to multiple diseases via MYB30-mediated lignin accumulation in rice - He Wang; Zhe-Xu Wang; Hong-Yuan Tian; Yu-Long Zeng; Hao Xue; Wan-Ting Mao; Lu-Yue Zhang; Jun-Ni Chen; Xiang Lu; Yong Zhu; Guo-Bang Li; Zhi-Xue Zhao; et al. (Molecular Plant, 2025)

Black soldier fly and microbiome collaborate to bioconvert the tofu whey water in an efficient and environment-friendly manner - Xiaowen Ji; Shaojie Zhou; Wenwen Chen; Bin Cao; Yumeng Sun; Qiyang Che; Yinglao Zhang; Jibin Zhang; Ting Ding; Jiaping Xu; Feng Peng; Maoye Li; et al. (Journal of Water Process Engineering, 2025)

Grazing increases the complexity of networks and ecological stochastic processes of mycorrhizal fungi - Jiqiong Zhou; Pengsen Wang; Li Wei; Jianguo Zhang; Xuxu Li; Nan Huang; Gang Liu; Kun Zou; Rui Fan; Lin Liu; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2025)

Fermented rhubarb alleviates metabolic dysfunction-associated steatotic liver disease symptoms by modulating gut microbiota and activating the hepatic insulin signaling pathway - Heng Yuan; Junyu Zhou; Ting Zhang; Xuangao Wu; Chen Li; Hee-Jong Yang; Do Yeon Jeong; Sunmin Park (Food Bioscience, 2025)

Comprehensive transcriptomic, proteomic, and intestinal microbiota analyses of largemouth bass (Micropterus salmoides) intestines reveal new insights into immune responses to Aeromonas hydrophila infection - Fuyan Chen; Xianhua Ouyang; Zhenping Liao; Ting Huang; Guixiang Tong; Honglian Tan; Mingxu Zhou; Xiaohua Lu; Xinxian Wei; Xueming Yang; Aiying Lei; Jianbin Li (Fish & Shellfish Immunology, 2025)

Microfluidic fabrication of lipid nanoparticles for co-delivery of siRNA and hydroxychloroquine: An engineered theranostic platform for enhanced breast cancer treatment - Lu Huang; Wenli Guo; Ting Zhao; Yanru Feng; Yue Li; Qingqing An; Chenxi Li; Yiwei Tian; Huaxing Zhang; Chenming Zhou; Yanan Sun; Chaoxing He; et al. (Chemical Engineering Journal, 2025)

Urea interfacial polymerization-based ultra-permeable polyamide composite membrane for efficient piggery wastewater purification - Lingfang Huang; Xiaocai Cui; Huimin Dang; Yi Huang; Qian Li; Ting Ran; Xingtao Zuo; Jiajie He; Yun Zhou (Chemical Engineering Journal, 2025)

pH-controlled acetic acid pretreatment for coproduction of low degree of polymerization xylo-oligosaccharides and glucose from corncobs - Chenxi Li; Shujun Hou; Dianxing Lian; Mohaoyang Chen; Shujun Li; Pengfei Li; Ting Wang; Weiwei Zhang; Yawen Zhou; Jianxin Jiang; Yongjun Ji (Bioresource Technology, 2025)

Factors affecting the different growth rates of PM2.5：Evidence from composition variation, formation mechanisms, and importance analysis of water-soluble inorganic ions with case study in northern China - Huan Li; Ting Zhang; Hui Su; Sui Xin Liu; Ying Qiang Shi; Lu Yao Wang; Dong Dong Xu; Jia Mao Zhou; Zhu Zi Zhao; Qi Yuan Wang; Steven Sai Hang Ho; Yao Qu; et al. (Atmospheric Environment, 2025)

Time-Dependent Transcriptional Dynamics of Contextual Fear Memory Retrieval Reveals the Function of Dipeptidyl Peptidase 9 in Reconsolidation - Wen-Ting Guo; Wen-Xing Li; Yu-Chen Liu; Ya-Bo Zhao; Lin Xu; Qi-Xin Zhou (Neuroscience Bulletin, 2025)
Numerous studies on the formation and consolidation of memory have shown that memory processes are characterized by phase-dependent and dynamic regulation. Memory retrieval, as the only representation of memory content and an active form of memory processing that induces memory reconsolidation, has attracted increasing attention in recent years. Although the molecular mechanisms specific to memory retrieval-induced reconsolidation have been gradually revealed, an understanding of the time-dependent regulatory mechanisms of this process is still lacking. In this study, we applied a transcriptome analysis of memory retrieval at different time points in the recent memory stage. Differential expression analysis and Short Time-series Expression Miner (STEM) depicting temporal gene expression patterns indicated that most differential gene expression occurred at 48 h, and the STEM cluster showing the greatest transcriptional upregulation at 48 h demonstrated the most significant difference. We then screened the differentially-expressed genes associated with that met the expression patterns of those cluster-identified genes that have been reported to be involved in learning and memory processes in addition to dipeptidyl peptidase 9 (DPP9). Further quantitative polymerase chain reaction verification and pharmacological intervention suggested that DPP9 is involved in 48-h fear memory retrieval and viral vector-mediated overexpression of DPP9 countered the 48-h retrieval-induced attenuation of fear memory. Taken together, our findings suggest that temporal gene expression patterns are induced by recent memory retrieval and provide hitherto undocumented evidence of the role of DPP9 in the retrieval-induced reconsolidation of fear memory.

Angelic acid triggers ferroptosis in colorectal cancer cells via targeting and impairing NRF2 protein stability - Yongyi Cao; Yu Wang; Yueyang Li; Sihan Liu; Lizhe Wang; Li Zhou; Ting Zhu (Journal of Natural Medicines, 2025)

Construction of label-free electrochemical aptasensor and logic circuit based on triple-stranded DNA molecular switch - Ya Zhou; Li Yang; Xuemei Zhang; Li Zhu; Xiaoli Xiong; Ting Xiao; Liping Zhu (Analytica Chimica Acta, 2025)

Relationship Between Whole Blood Iron Levels and Lipid Profile Parameters in the General Population: Findings from Routine Physical Examination Report - Rou-Jun Pan; Zhi Luo; Yu-Shun You; Jun-Dong Wang; Ya-Qi Chen; Rong-Rong Zhou; Shu-Zi-Qi Chen; Lin-Min Wang; Jun-Xiang Zhao; Hua-Qin Su; Cai-Li Wang; Li-Fen Zhang; et al. (Biological Trace Element Research, 2024)

Widespread presence of gut bacterium Glutamicibacter ectropisis sp. nov. confers enhanced resistance to the pesticide bifenthrin in tea pests - Xiayu Li; Ting Fang; Tian Gao; Hao Gui; Ying Chen; Linlin Zhou; Yong Zhang; Yunqiu Yang; Letian Xu; Yanhua Long (Science of The Total Environment, 2024)

Interactive effects of microplastics and cadmium on soil properties, microbial communities and bok choy growth - Mengxiao Li; Jiaju He; Xiaofeng Chen; Xiaoman Dong; Shuang Liu; Christopher W.N. Anderson; Minghua Zhou; Xuesong Gao; Xiaoyan Tang; Di Zhao; Ting Lan (Science of The Total Environment, 2024)

Biodegradation of imidacloprid and diuron by Simplicillium sp. QHSH-33 - Ke Xu; Xin-Ran Ke; Wan-Ting Zhang; Xin-Yuan Wu; Zhi-Jun Song; Mei-Juan Jiao; Xiao-Juan Gao; Li Zhou; Hong-Yan Ji; Fang Wang; Xiu-Li Wu (Pesticide Biochemistry and Physiology, 2024)

Optimizing redox cycling with α-Fe2O3/MoS2 heterostructures for efficient degradation of antibiotics via peroxymonosulfate activation - Qingsong Hu; Meng Ye; Ting Zhou; Zhixin Wang; Mingyang Li; Yanbing Liu; Jianjian Yi; Binxian Gu (Journal of Water Process Engineering, 2024)

Association between iron status, preeclampsia and gestational hypertension: A bidirectional two-sample Mendelian randomization study - Pengsheng Li; Haiyan Wang; Ting Chen; Gengdong Chen; Zixing Zhou; Shaoxin Ye; Dongxin Lin; Dazhi Fan; Xiaoling Guo; Zhengping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

Associations of maternal serum concentration of iron-related indicators with gestational diabetes mellitus in Chinese: A pilot prospective cohort study - Geng-dong Chen; Peng-sheng Li; Zi-xing Zhou; Ting-ting Pang; Hai-yan Wang; Xiao-yan Gou; Shao-xin Ye; Dong-xin Lin; Da-zhi Fan; Zheng-ping Liu (Journal of Trace Elements in Medicine and Biology, 2024)

A coupled model integrating dual attention mechanism into BiGRU-RED for multi-step-ahead streamflow forecasting - Chunlin Huang; Ting Zhou; Weide Li; Haijiao Yu; Rongxia Li; Jinjie Fang (Journal of Hydrology, 2024)

Potential of Salvinia biloba Raddi for the remediation of water polluted with ciprofloxacin: Removal, physiological response, and root microbial community - Zhangxiong Luo; Meng Qin; Zicong Guo; Xuxin Li; Ting Zhou; Zhuotong Zeng; Chengyun Zhou; Biao Song (Journal of Hazardous Materials, 2024)

The physicochemical properties and emulsion performance of different fractions from rice glutelin fibrils - Ting Li; Jiangtao Zhou; Mingqin Li; Raffaele Mezzenga; Li Wang (Journal of Food Engineering, 2024)

Ecological and vegetation responses in a humid region in southern China during a historic drought - Ting Yang; Jiasheng Qin; Xudong Li; Xu Zhou; Yang Lu (Journal of Environmental Management, 2024)

The catalytic reduction-oxidation collaborative processes for enhanced elimination of TBBPA over Pd/CeO2-R catalyst - Liyu Shi; Xuezhi Peng; Ting Xiang; Lei Li; Juan Zhou (Journal of Environmental Chemical Engineering, 2024)

Urine is better for rare earth elements bimonitoring in long-term exposed population: An exposure-response relationship study - Zhizhou He; Li Liu; Ting Wang; Cailan Zhou; Xuewei Zhang; Nan Wu; Mengmeng Xu; Jianqiong Gao; Bin Li; Yonglan Wang; Qiang Zhi; Chenguang Zhang; et al. (Environmental Research, 2024)

Free-standing, robust, hyperconnective hybrid nanofiber nonwovens enabled by interpenetrating network for oily aerosols purification - Weitao Zhou; Yiming Li; Zeng Qu; Sen Li; Ting Wu; Jingliang Li; Tingting Shi; Jikai Chen; Boyu Li; Haitao Huang; Shan Du (Chemical Engineering Journal, 2024)

Effects of particle breakage on rockslide deposition formations: insights from rigid finite element modelling - Hui Jiang; Jing-Jing Zhu; Wen-Jie Zhang; Jin-Ting Wang; Yuan-De Zhou; Xiu-Li Du (Bulletin of Engineering Geology and the Environment, 2024)

Native CRISPR-Cas-based programmable multiplex gene repression in Klebsiella variicola - Zhifeng Mo; Siying Lin; Ting Li; Guohui Yu; Yunhao Sun; Jianuan Zhou; Zeling Xu (Biotechnology Letters, 2024)

Hg-mining-induced soil pollution by potentially toxic metal(loid)s presents a potential environmental risk and threat to human health: A global meta-analysis - Li Chen; Xiaosan Luo; Haoran He; Ting Duan; Ying Zhou; Lequn Yang; Yi Zeng; Hansong Chen; Linchuan Fang (Soil Ecology Letters, 2024)

The effect of paeoniflorin on the rewarding effect of methamphetamine and the associated cognitive impairment in mice - Xin-shuang Gong; Hai-xing Wang; Xiang-dong Yang; Zhao-ying Yu; Shu-jun Lin; Zhi-ting Zou; Jia-nan Lv; Li-yin Qian; Yu-er Ruan; Zi-zhen Si; Yi Zhou; Yu Liu (Metabolic Brain Disease, 2024)

Co-grown novel S-scheme tubular P–UCN/S-TCN homojunction mediates photocatalysis-PMS activation synergistic system for efficient degradation of antibiotic - Ting Wu; Zhifeng Liu; Binbin Shao; Yuan Pan; Qingyun He; Xiansheng Zhang; Lingfeng Zhou; Yunze Wang; Teng Li; Sheng Liu (Chemosphere, 2024)

Impact of formaldehyde on ozone formation in Central China: Important role of biogenic emission in forest region - Wenting Dai; Ruonan Wang; Haobin Zhong; Lu Li; Yifan Zhang; Jianjun Li; Qiyuan Wang; Junji Cao; Steven Sai Hang Ho; Ting Zhang; Jiamao Zhou; Suixin Liu; et al. (Science of The Total Environment, 2024)

Interleukin-11 drives fibroblast metabolic reprogramming in crystalline silica-induced lung fibrosis - Yujia Xie; Shiyu Yang; Yiju Xu; Pei Gu; Yingdie Zhang; Xiaojie You; Haoyu Yin; Bingxin Shang; Yuxin Yao; Wei Li; Dongming Wang; Ting Zhou; et al. (Science of The Total Environment, 2024)

Ensuring China's food security in a geographical shift of its grain production: Driving factors, threats, and solutions - Shi Xue; Zhou Fang; Carena van Riper; Wei He; Xuxia Li; Fan Zhang; Ting Wang; Changgao Cheng; Qin Zhou; Zhongde Huang; Yang Bai (Resources, Conservation and Recycling, 2024)

Efficient elimination of antibiotics and antibiotic resistance genes in hyperthermophilic sludge composting - Ting Pan; Yan-Yan Zhou; Qian Xiang; Xin-Li An; Qiang Pu; Jian-Qiang Su (Journal of Hazardous Materials, 2024)

Mechanisms of inhibition and recovery under multi-antibiotic stress in anammox: A critical review - Xu Ji; Xiaonong Zhang; Ting Ju; Li Zhou; Da Jin; Peng Wu (Journal of Environmental Management, 2024)

Impact resistance and performance of precast shear walls with various connections under axial and lateral loads - Yun Zhou; Xin Zhang; Fan Yi; Jing-Ming Sun; Jia Ni; Ting Li; Wei-Jian Yi (Engineering Structures, 2024)

Combining biochar with schwertmannite-based solid to enhance co-removal of ciprofloxacin and roxarsone as well as to improve regenerative capacity - Ting Li; Xin Du; Xiqing Wang; Yujun Zhou; Jiansheng Li; Murong Wang; Lixiang Zhou (Chemical Engineering Journal, 2024)

Tunable sulfur vacancies in amorphous-crystalline AC-Bi2S3-x@C derived from CAU-17 for efficient capture of radioiodine: Comparison of sulfur vacancies in amorphous and crystalline structures - Kai-Wei Chen; Xin-Yu Zhou; Yi-Ting Chen; Xiao-Jun Dai; Shu-Xuan Li; Ao-Tian Gu; Chun-Hui Gong; Peng Wang; Ping Mao; Ji-Gen Lu; Yi Yang (Chemical Engineering Journal, 2024)

Correction to: Effectiveness of high-energy dynamic compaction on Layered soil-rock mixture geomaterials based on field test - Yingjie Wei; Yuyou Yang; Mengyao Zhao; Ting Zhou; Huancun Liu; Jianguang Li; Yuxin Jie (Bulletin of Engineering Geology and the Environment, 2024)

A critical review of comammox and synergistic nitrogen removal coupling anammox: Mechanisms and regulatory strategies - Da Jin; Xiaonong Zhang; Xingxing Zhang; Li Zhou; Zixuan Zhu; Ufoymungu Kisa Deogratias; Zhiqiang Wu; Kangyu Zhang; Xu Ji; Ting Ju; Xurui Zhu; Bo Gao; et al. (Science of The Total Environment, 2024)

Beneficial effect of residential greenness on sperm quality and the role of air pollution: A multicenter population-based study - Tingting Dai; Wei Li; Lingxi Wang; Jiayi Zhou; Kaixin Zhong; Yunchong Yao; Xiaoyan Cai; Linwei Tian; Haisheng Wu; Ting Xu; Lina Xiao; Haobo Ni; et al. (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Defective MoSe2 for enhanced remediation of 2,4-D by boosting peroxymonosulfate activation - Ting Xiang; Jiaojiao Yang; Liyu Shi; Lei Li; Quanyuan Chen; Juan Zhou (Journal of Environmental Chemical Engineering, 2024)

HZrO2@PPy nanocomposite for effective fluoride removal from environmental water - Yan Li; Qin Wang; Fengzheng Liu; Zijian Zhou; Xin Huang; Na Wang; Ting Wang; Hongxun Hao (Journal of Environmental Chemical Engineering, 2024)

Mitigating nitrite inhibition in Klebsiella strain denitrification: Stimulating endogenous driving force with microscale zero-valent iron - Wen-ying Cao; Kuang-di Xu; Su Zhang; Si-jia Li; Yi-cheng Yuan; Jing-xuan Lu; Lei Yu; Shao-hua Zhou; Jun-ting Gan; Quan Wang; Rong-ping Chen; Ke Yin (Chemical Engineering Journal, 2024)

UV light absorption at 370 nm by mineral dust, organic carbon, and elemental carbon in the Himalayas and Tibetan Plateau - Chong-Shu Zhu; Yao Qu; Yue Zhou; Nan Wang; Hong Huang; Ting Zhang; Xiao-Li Su; Jun-Ji Cao (Atmospheric Environment, 2024)

Identification of systemic nitrogen signaling in foxtail millet (Setaria italica) roots based on split-root system and transcriptome analysis - Xin-Li Yao; Yu-Ze Wang; Hui-Xin Meng; Ming-Hua Zhang; Xuan Zhou; Xue-Ting Kang; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; Xiaoqian Chu; et al. (Plant Cell Reports, 2024)

Effectiveness of high-energy dynamic compaction on Layered soil-rock mixture geomaterials based on field test - Yingjie Wei; Yuyou Yang; Mengyao Zhao; Ting Zhou; Huancun Liu; Jianguang Li; Yuxin Jie (Bulletin of Engineering Geology and the Environment, 2024)

Sodium Selenite Prevents Matrine-Induced Nephrotoxicity by Suppressing Ferroptosis via the GSH-GPX4 Antioxidant System - Xi Wang; Zixiong Lin; Ting Li; Wenjing Zhu; Hanxin Huang; Jiayan Hu; Jie Zhou (Biological Trace Element Research, 2024)

Cuproptosis-Associated lncRNA Gene Signature Establishes New Prognostic Profile and Predicts Immunotherapy Response in Endometrial Carcinoma - Xi-Ya Jiang; Jing-Jing Hu; Rui Wang; Wei-Yu Zhang; Qin-Qin Jin; Yin-Ting Yang; Jie Mei; Lin Hong; Hui Yao; Feng Tao; Jie-Jie Li; Yu Liu; et al. (Biochemical Genetics, 2024)
Uterine corpus endometrial carcinoma (UCEC), a prevalent kind of cancerous tumor in female reproductive system that has a dismal prognosis in women worldwide. Given the very limited studies of cuproptosis-related lncRNAs (CRLs) in UCEC. Our purpose was to construct a prognostic profile based on CRLs and explore its assess prognostic value in UCEC victims and its correlation with the immunological microenvironment.Methods: 554 UCEC tumor samples and 23 normal samples’ RNA-seq statistics and clinical details were compiled from data in the TCGA database. CRLs were obtained using Pearson correlation analysis. Using LASSO Cox regression, multivariate Cox regression, and univariate Cox regression analysis, six CRLs are confirmed to develop a risk prediction model at last.We identified two main molecular subtypes and observed that multilayer CRLs modifications were related to patient clinicopathological features, prognosis, and tumor microenvironment (TME) cell infiltration characteristics, and then we verified the prognostic hallmark of UCEC and examined its immunological landscape.Finally, using qRT-PCR, model hub genes’ expression patterns were confirmed. Results: A unique CRL signature was established by the combination of six differently expressed CRLs that were highly linked with the prognosis of UCEC patients. According to their CRLs signatures, the patients were divided into two groups: the low-risk and the high-risk groups. Compared to individuals at high risk, patients at low risk had higher survival rates ( p

Triclosan in sludge: Exploring its journey from the sewage treatment plants to land application and potential impacts on the environment - Zhenyao Wang; Xuan Li; Huan Liu; Ting Zhou; Jibin Li; Yi Li; Carol Sze Ki Lin; Qilin Wang (Critical Reviews in Environmental Science and Technology, 2024)

Immunosuppressive leucosesterterpane and penta-nor-leucosesterterpane sesterterpenoids from Leucosceptrum canum - Ting-Ting Zhou; Man-Wen Zhang; Yan-Chun Liu; Xiao-Nian Li; Yan Liu; Kai Guo; Sheng-Hong Li (Phytochemistry, 2024)

Insights on the efficiency and contribution of single active species in photocatalytic degradation of tetracycline: Priority attack active sites, intermediate products and their toxicity evaluation - Jianhui Shi; Tiantian Yang; Ting Zhao; Kaikai Pu; Jiating Shi; Aijuan Zhou; Houfen Li; Sufang Wang; Jinbo Xue (Journal of Environmental Management, 2024)

Caspase-8 promotes NLRP3 inflammasome activation mediates eye development defects in zebrafish larvae exposed to perfulorooctane sulfonate (PFOS) - Lu-Yin Wu; Jing-Lin Zhang; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Wan-Ting He; Nanxiang Jin; Ye Dai; Wei Chi; Zejin Ou; Guang-Hui Dong; Li-Zi Lin (Environmental Pollution, 2024)

Construction of an anti-anionic-depletion layer to mitigate the tip deposition effect for dendrite-free zinc anode - Xiaohui Li; Dan Qiu; Qiancheng Zhou; Ze Yang; Xing Zhou; Wenping Wang; Chenchen Wei; Ting Zou; Ying Yu (Chemical Engineering Journal, 2024)

An injectable COL6-crosslinked HA-DTPH hydrogel promotes spinal tract-like structure organization during spinal cord regeneration - Jia-Hui Sun; Zhou Fang; Zhiling Li; Ting-Ting Zheng; Sheng Liu; Jixiang Zhu; Wensheng Lin; Li-Kang Zhang; Aihua Yin; Aiguo Xuan; Jian-Long Zou (Chemical Engineering Journal, 2024)

Effects of Straw and Nitrogenous Fertilizers on the Soil Aggregate Stability and Quality in Subtropical Regions of China - Jia Yi Yang; Shahbaz Atta Tung; Jin Ting Xu; Yan Qiong Pan; Li Yang; Xun Bo Zhou (Journal of Soil Science and Plant Nutrition, 2024)

Multi-decadal and regional validation of the AMG model at county and grid scales unravels the role of crop residue inputs in increasing soil organic carbon stocks in the Tuojiang River Basin, China - Qi Wang; Pierre Barré; Qiquan Li; Ting Lan; Minghua Zhou; Xuesong Gao; Julia Le Noë (Agriculture, Ecosystems & Environment, 2024)

Vegetation and precipitation change inferred from the δ13C and δ2H values of n-alkanes from lake sediment from 18 cal ka BP, tropical NE Australia - Ting Li; Youping Zhou; Chris M. Wurster; Xiuwen Zhou; Yu Zhao; Rainy Comley; Niels C. Munksgaard; Lucas A. Cernusak; Jordahna Haig; Michael I. Bird (Quaternary Science Reviews, 2024)

Porous hollow nanospheres nickel phosphide and its high catalytic hydrogenation performance on naomaohu coal soluble portion and model compounds - Yingxiong Zhang; Ting Liu; Yakun Tang; Jingmei Liu; Yue Zhang; Xiaodong Zhou; Xiaohui Li; Lang Liu (Fuel, 2024)

Natural aromatic extract of black tea improved the water retention of pork meat batter - Wen-ping Xu; Rui-ling Dong; Ao-jing Lv; Yu-cong Li; Li-ting Zeng; Xue-ling Gao; Jun Qi; Zhou Lin; Hui-min Yan; Chun-hui Zhang; Guo-yuan Xiong (Food Research International, 2024)

Contamination of dairy products with tris(2,4-di-tert-butylphenyl) phosphite and implications for human exposure - Ruize Zhou; Jianqiang Geng; Jie Jiang; Bing Shao; Li Lin; Tongna Mu; Baolong Wang; Ting Liu (Food Chemistry, 2024)

Structural characterization of modified soy protein isolate composite coatings and its application on fresh-cut cantaloupe (Cucumis melo cv. Xiaomi) - Tian Yang; Dan-Dan Zhou; Cai-E Wu; Ting-Ting Li; Gong-Jian Fan; Xiao-Jing Li; Kai-Ping Cong; Zhi-Cheng Yan; Xin Cheng (Food Bioscience, 2024)

Fish decay-accelerating factor (DAF) regulates intestinal complement pathway and immune response to bacterial challenge - Xia Zhang; Yuhan Zhang; Ting Wu; Hao He; Ran Peng; Kelan Jin; Huilan Mo; Fufa Qu; Jianzhou Tang; Yonghua Zhou; Yalin Yang; Zhigang Zhou; et al. (Fish & Shellfish Immunology, 2024)

Enhancing the sodium-ion storage performance of two-dimensional layered Ti3CN with a molecular riveting strategy - Dong-Ting Zhang; Hong-Yan Li; Wen-Jie Shi; Yu-Xia Hu; Ling-Bin Kong; Xue-Feng Lu; Zi-Zhou Yuan; Mao-Cheng Liu (Chemical Engineering Journal, 2024)

Removal of radioactive iodine by Cu2O prepared with PVP as an active agent: Role of crystal facets and oxygen vacancy in adsorption mechanisms - Xiao-Jun Dai; Kai-Wei Chen; Man-Li He; Kai Chen; Xin-Yu Zhou; Yi-Ting Chen; Chun-Hui Gong; Peng Wang; Ping Mao; Yi Yang (Chemical Engineering Journal, 2024)

Dynamic intrauterine crosstalk promotes porcine embryo implantation during early pregnancy - Xupeng Zang; Shengchen Gu; Wenjing Wang; Junsong Shi; Jianyu Gan; Qun Hu; Chen Zhou; Yue Ding; Yanjuan He; Lei Jiang; Ting Gu; Zheng Xu; et al. (Science China Life Sciences, 2024)

Paraquat disrupts KIF5A-mediated axonal mitochondrial transport in midbrain neurons and its antagonism by melatonin - Huihui Hong; Jingdian Li; Tong Tong; Ting Yang; Hui Wang; Yudong Xu; Xiqin Lin; Jinxian Lin; Sicheng Liu; Kun Luo; Zhengping Yu; Wei Yuan; et al. (Science of The Total Environment, 2024)

Emergence of colistin-resistant Stenotrophomonas maltophilia with high virulence in natural aquatic environments - Ting Zhang; Haiyan Wu; Chenchen Ma; Yidi Yang; Haibei Li; Zhongwei Yang; Shuqing Zhou; Danyang Shi; Tianjiao Chen; Dong Yang; Junwen Li; Min Jin (Science of The Total Environment, 2024)

Anti-inflammatory discovery of sesquiterpenoids and a jasmonic acid derivative from Artemisia stolonifera - Ting Wu; Wen-Jing Wang; Zhou-Yuan Li; Yi-Tian Liu; Tian-Ping Yu; Shuang-Ge Li; Hong-Zhi Du; Chun Gui; Da-Hui Liu; Xiao-Long Yang (Phytochemistry, 2024)

Sulfur vacancy-rich bismuth sulfide nanowire derived from CAU-17 for radioactive iodine capture in complex environments: Performance and intrinsic mechanisms - Kai-Wei Chen; Xin-Yu Zhou; Xiao-Jun Dai; Yi-Ting Chen; Shu-Xuan Li; Chun-Hui Gong; Peng Wang; Ping Mao; Yan Jiao; Kai Chen; Yi Yang (Journal of Hazardous Materials, 2024)

Characterization of Pseudomonas spp. contamination and in situ spoilage potential in pasteurized milk production process - Guanhong Chang; Qianhong Li; Ting Wang; Bozheng Zhang; Wendi Wu; Chunyang Lv; Tongzhuo Sun; Ting Zhou; Wanxiang Zheng; Yeru Wang; Xin Wang (Food Research International, 2024)

A novel rejuvenation approach to improve rooting capacity and its mechanism in Cunninghamia lanceolata - Yunni Chang; Ting Xue; Josep Peñuelas; Jordi Sardans; JunXin Zhou; Yang Zhou; Chaobin Xu; XueYan Zheng; WangXun Peng; Yanbing Deng; Quanlin Zhong; Baoyin Li (Forest Ecology and Management, 2024)

Engineering hyperthermophilic pullulanase to efficiently utilize corn starch for production of maltooligosaccharides and glucose - Ting Xie; Li Zhou.; Laichuang Han; Cuiping You; Zhongmei Liu; Wenjing Cui; Zhongyi Cheng; Junling Guo; Zhemin Zhou (Food Chemistry, 2024)

Microscopic identification of foodborne bacterial pathogens based on deep learning method - Qiong Chen; Han Bao; Hui Li; Ting Wu; Xin Qi; Changqiang Zhu; Weilong Tan; Desheng Jia; Dongming Zhou; Yong Qi (Food Control, 2024)

Viscoelastic cues to induce stem cell migration and neuronal differentiation in cell-free hydrogel-assisted TBI recovery - Xiaoyin Liu; Chengheng Wu; Yusheng Zhang; Gaowei Li; Suping Chen; Zhihong Chen; Peng Liu; Kai Wu; Xiaoyang Wu; Ting Zhou; Mingze Zeng; Zi Qiao; et al. (Chemical Engineering Journal, 2024)

Electron transfer-mediated peroxymonosulfate activation through monoatomic Fe–pyridinic N4 moiety in biochar-based catalyst for electron-rich pollutants degradation in groundwater - Ting Zhou; Hongjie Wang; Wenyi Dong; Tianxing Du; Xuechuan Li; Feifei Wang; Zilong Zhao (Chemical Engineering Journal, 2024)

The pivotal role of secondary nutrients and micronutrients in regulating fruit quality and root exudates metabolism profile of citrus - Yanni Tang; Wei Lou; Xiang Yan; Shiqian Li; Pengwei Wang; Yingjie Zhou; Ting Zhan; Siming Zhang; Chengxiao Hu; Xu Wang; Hanliang Liu; Qiling Tan; et al. (Plant and Soil, 2024)

Molecular engineering to elevate reactive oxygen species generation for synergetic damage on lipid droplets and mitochondria - Mingdi Yang; Kaiwen Li; Liangchen Zhong; Yingcui Bu; Yingyong Ni; Ting Wang; Jing Huang; Jingyan Zhang; Hongping Zhou (Analytica Chimica Acta, 2024)

Matrine induces cardiotoxicity by promoting ferroptosis through the Nrf2 antioxidant system in H9c2 cells - Xi Wang; Zixiong Lin; Xinyi Tang; Minjuan Xie; Ting Li; Jie Zhou (Toxicology Letters, 2024)

RATA: A novel class A carbapenemase with broad geographic distribution and potential for global spread - Hongyan Luo; Zhishuang Yang; Ting Lei; Caixia Li; Zuoyong Zhou; Mingshu Wang; Dekang Zhu; Pei Li; Anchun Cheng (Science of The Total Environment, 2024)

Antibiotic resistome in landfill leachate and impact on groundwater - Wei-Li Jia; Min Zhang; Fang-Zhou Gao; Hong Bai; Lu-Xi He; Liang-Ying He; Ting Liu; Yu Han; Guang-Guo Ying (Science of The Total Environment, 2024)

Metabolomic insights into the profile, bioaccessibility, and transepithelial transport of polyphenols from germinated quinoa during in vitro gastrointestinal digestion/Caco-2 cell transport, and their prebiotic effects during colonic fermentation - Meijiao Li; Xuan Zhang; Zhe Gao; Mengying Wu; Ting Ren; Chen Wu; Jie Wang; Yanlou Geng; Wei Lv; Qian Zhou; Wen Zhao (Food Research International, 2024)

Differences among Lactiplantibacillus plantarum strains isolated from different fermented foods in their potential cholesterol-lowering properties - Shu-Jun Guo; Chang-Cheng Li; Yu-Ting Feng; Yan-Ru Zhou; Bin Liu; Zhen-Peng Gao; Chun-Feng Guo (Food Bioscience, 2024)

The insightful water quality analysis and predictive model establishment via machine learning in dual-source drinking water distribution system - Huiping Li; Baiqin Zhou; Xiaoyan Xu; Ranran Huo; Ting Zhou; Xiaochen Dong; Cheng Ye; Tian Li; Li Xie; Weihai Pang (Environmental Research, 2024)

Low-voltage stimulated denitrification performance of high-salinity wastewater using halotolerant microorganisms - Long Chen; Hai Xiang; Li-Ting Zhou; Yan-Qing Zhang; Yang-Cheng Ding; Di Wu; Nan-Wen Zhu; Yi-Feng Zhang; Hua-Jun Feng (Bioresource Technology, 2024)

Characteristics and influencing factors of CO2 emission from inland waters in China - Ting Zhou; Xiaofeng Wang; Zuolin Xiao; Zhaoyin Qing; Xianxiang Li; Jilong Wang; Ziyi Que (Science China Earth Sciences, 2024)

Soil physicochemical properties and plant functional traits regulate ecosystem multifunctionality of alpine grassland under different livestock grazing assemblies - Bin Feng; Yu-Zhen Liu; Wen-Ting Liu; Wei-Dong Lv; Cai-Cai Sun; Zeng-Zeng Yang; Cai-Di Li; Qin-Yuan Zhou; Fang-Cao Wang; Xiao-Xia Yang; Quan-Min Dong (Agriculture, Ecosystems & Environment, 2024)

Coastal hypoxia response to the coupling of catastrophic flood, extreme marine heatwave and typhoon: a case study off the Changjiang River Estuary in summer 2020 - Xiao Ma; Qicheng Meng; Dewang Li; Yuanli Zhu; Xiaobo Ni; Dingyong Zeng; Di Tian; Ting Huang; Zhihao Jiang; Haiyan Jin; Feng Zhou (Acta Oceanologica Sinica, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Temperature-phased anaerobic sludge digestion effectively removes antibiotic resistance genes in a full-scale wastewater treatment plant - Huan Liu; Zehao Zhang; Xuan Li; Ting Zhou; Zhenyao Wang; Jibin Li; Yi Li; Qilin Wang (Science of The Total Environment, 2024)

Non-targeted screening and photolysis transformation of tire-related compounds in roadway runoff - Jinfan Chen; Ting Tang; Yanxi Li; Rui Wang; Xingcai Chen; Dehao Song; Xiaodong Du; Xueqin Tao; Jiangmin Zhou; Zhi Dang; Guining Lu (Science of The Total Environment, 2024)

The effect of artificial light at night (ALAN) on the characteristics of diapause of Aedes albopictus - Qing Liu; Heng-Duan Zhang; Dan Xing; Jing-Wen Xie; Yu-Tong Du; Ming Wang; Zi-Ge Yin; Nan Jia; Chun-Xiao Li; Teng Zhao; Yu-Ting Jiang; Yan-De Dong; et al. (Science of The Total Environment, 2024)

Artificial microbial consortia engineering: Intensify nitrogen removal from mature landfill leachate by simultaneous nitrification and denitrification - Xia Ke; Yi-Xin Li; Ting-Ting Guo; Zu-Lian Liao; Su-Qin Tang; Yi-Cheng Zhang; Shi-Peng Zhou; Ya-Ping Xue; Yu-Guo Zheng (Journal of Water Process Engineering, 2024)

Fe-Mn binary oxides improve the methanogenic performance and reduce the environmental health risks associated with antibiotic resistance genes during anaerobic digestion - Zhihui Chen; Qingling Ding; Xing Ning; Zilin Song; Jie Gu; Xiaojuan Wang; Wei Sun; Xun Qian; Ting Hu; Shumei Wei; Liang Xu; Yuexuan Li; et al. (Journal of Hazardous Materials, 2024)

Eggshell powder as a bio-filler for starch and gelatin: Ternary biodegradable composite films manufactured by extrusion compression molding - Ting Li; Ruofei Li; Haodan Luo; Lu Peng; Jie Wang; Shasha Li; Man Zhou; Xiangyang Yuan; Zhiqing Zhang; Hejun Wu (Food Hydrocolloids, 2024)

Correlation of Immune-Inflammatory Response System (IRS)/Compensatory Immune-Regulatory Reflex System (CIRS) with White Matter Integrity in First-Episode Patients with Schizophrenia - Mengzhuang Gou; Wei Li; Jinghui Tong; Yanfang Zhou; Ting Xie; Ting Yu; Wei Feng; Yanli Li; Song Chen; Baopeng Tian; Shuping Tan; Zhiren Wang; et al. (Molecular Neurobiology, 2024)

Advanced “turn-on” colorimetric uranium platform based on the enhanced nanozyme activity of a donor-acceptor structured covalent organic framework - Sai Jin Xiao; Jing Huang; An Ting Qiu; Guang Zhou Liu; Li Zhang; Ting Wu; Ya Di Shi; Jian-Ding Qiu (Analytica Chimica Acta, 2024)

NKX2-1-AS1 promotes the lymphangiogenesis of lung adenocarcinoma through regulation of ERG-mediated FABP4 - Ting Tao; Hui Chen; Qimei Xu; Zhen Li; Xuelian Chen; Xunjian Zhou; Wu Luo (Tissue and Cell, 2024)

Cadmium disrupts spermatogenic cell cycle via piRNA-DQ717867/p53 pathway - Jiaoyang Wei; Juan Dai; Xiaofan Shi; Ruixue Zhao; Guoqing Fu; Rui Li; Chao Xia; Ling Zhang; Ting Zhou; Huaiji Wang; Yuqin Shi (Reproductive Toxicology, 2024)

Plasma-activated water regulates water distribution to resist softening of goji berries - Kai-Ping Cong; Cai-E. Wu; Ting-Ting Li; Gong-Jian Fan; Dan-dan Zhou; Xiao-jing Li; An-Di Suo; Xu Li (Postharvest Biology and Technology, 2024)

Effects of climate and geochemical properties on the chemical forms of soil Cd, Pb and Cr along a more than 4000 km transect - Zhiqiang Bai; Ting Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Wei Zhou; Xiaomei Pan; Yulin Pu; Yongxia Jia; Zhanbiao Yang; Lulu Long (Journal of Hazardous Materials, 2024)

The interplay of Cxcl10+/Mmp14+ monocytes and Ccl3+ neutrophils proactively mediates silica-induced pulmonary fibrosis - Demin Cheng; Wenxiu Lian; Ting Wang; Sichuan Xi; Xinying Jia; Ziwei Li; Haojie Xiong; Yue Wang; Wenqing Sun; Siyun Zhou; Lan Peng; Lei Han; et al. (Journal of Hazardous Materials, 2024)

Co-hydrothermal carbonization of rape straw and industrial sewage sludge – Applications of hydrochar for N and P adsorptions and for agricultural/horticultural purposes - Chang-Lian Xu; Ailian Li; Xiaoxun Xu; Zhanbiao Yang; Guiyin Wang; Zhang Cheng; Shirong Zhang; Ting Li; Yulin Pu; Guochun Lv; Junzhuo Cai; Wei Zhou; et al. (Journal of Cleaner Production, 2024)

Facet-dependent peroxymonosulfate activity and mechanism of CuO for degradation of organic pollutants - Tong Li; Ze-Zhou Ding; Fei Shi; Yi-Ting Ju; Ting-Ting Du; Chang Liu; Xing Zhang (Journal of Environmental Chemical Engineering, 2024)

Theory-guided unraveling of the mechanism underlying Cu1.0/Mn1.0-ZnO with dual reaction centers for enhanced peroxymonosulfate activation - Kaixuan Wang; Haibo Li; Xiaofei Qin; Ting Ma; Lin Zhu; Chenxi Zhang; Wei Yu; Xulun Zhou (Environmental Research, 2024)

Ozone and its precursors at an urban site in the Yangtze River Delta since clean air action plan phase II in China - Hua Fang; Wenjing Wang; Ran Wang; Hongling Xu; Ying Zhang; Ting Wu; Ruicheng Zhou; Jianxi Zhang; Zhirong Ruan; Feng Li; Xinming Wang (Environmental Pollution, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Evaluation of the Pollination Efficiency of Apple Trees by Osmia excavata Alfken (Hymenoptera: Megachilidae) - Zhaoyun Lyu; Min Feng; Lei Nie; Ting Zhou; Kai Yu; Lili Li; Xingyuan Men; Meng Sun; Yi Yu (Neotropical Entomology, 2024)

Microplastics affect mosquito from aquatic to terrestrial lifestyles and are transferred to mammals through mosquito bites - Jian-hang Li; Xiao-hui Liu; Guo-rui Liang; He-ting Gao; Si-han Guo; Xin-yu Zhou; Dan Xing; Teng Zhao; Chun-xiao Li (Science of The Total Environment, 2024)

Mixed plantations do not necessarily provide higher ecosystem multifunctionality than monoculture plantations - Xu Li; Yue Liu; Guopeng Wu; Zhiyang Lie; Han Sheng; Luis Carlos Ramos Aguila; Muhammmad Sadiq Khan; Xujun Liu; Shuyidan Zhou; Ting Wu; Wenfang Xu; Juxiu Liu (Science of The Total Environment, 2024)

Potassium resources management systems in Chinese agriculture: Yield gaps and environmental costs - Dongxue Li; Ting Li; Jun Gu; Yiliu Wang; Xiaoqin Chen; Dianjun Lu; Yueyue Tao; Zhenling Cui; Xinping Chen; Jianwei Lu; Jun Nie; Huoyan Wang; et al. (Resources, Conservation and Recycling, 2024)

Occurrence, fate, and remediation for per-and polyfluoroalkyl substances (PFAS) in sewage sludge: A comprehensive review - Ting Zhou; Xuan Li; Huan Liu; Shiman Dong; Zehao Zhang; Zhenyao Wang; Jibin Li; Long D. Nghiem; Stuart J. Khan; Qilin Wang (Journal of Hazardous Materials, 2024)

Haze weather and mortality in China from 2014 to 2020: Definitions, vulnerability, and effect modification by haze characteristics - Zhou Yang; Jiangmei Liu; Jun Yang; Li Li; Ting Xiao; Maigeng Zhou; Chun-Quan Ou (Journal of Hazardous Materials, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

OPEs-ID: A software for non-targeted screening of organophosphate esters based on liquid chromatography-high-resolution mass spectrometry - Yinran Xiong; Jinyue Liu; Jing Yu; Da Chen; Tiantian Li; Fengli Zhou; Ting Wu; Xiaotu Liu; Yiping Du (Journal of Hazardous Materials, 2024)

T-2 toxin induces mitochondrial dysfunction in chondrocytes via the p53-cyclophilin D pathway - Fang-fang Yu; Shui-yuan Yu; Lei Sun; Juan Zuo; Kang-ting Luo; Miao Wang; Xiao-li Fu; Feng Zhang; Hui Huang; Guo-yu Zhou; Yan-jie Wang; Yue Ba (Journal of Hazardous Materials, 2024)

Comparison of the flight ability of diapausing and post-diapause Osmia excavata Alfken (Hymenoptera: Megachilidae) at different temperatures - Zhaoyun Lyu; Haigang Liu; Ting Zhou; Min Feng; Zengbin Lu; Lei Nie; Guiping Wang; Guangzhao Wang; Lili Li; Xingyuan Men; Meng Sun; Yi Yu (Journal of Asia-Pacific Entomology, 2024)

Inhibition of high sulfur on functional microorganisms and genes in slightly contaminated soil by cadmium and chromium - Longfei Xu; Guiyin Wang; Shirong Zhang; Ting Li; Xiaoxun Xu; Guoshu Gong; Wei Zhou; Yulin Pu; Yongxia Jia; Yun Li; Lulu Long (Environmental Pollution, 2024)

Simulation of gross primary productivity and impact of drought in Liulin watershed of Taihang mountains over 2000–2020 - Junzhi Zhou; Ting Zhang; Jianzhu Li; Ping Feng (Ecological Modelling, 2024)

Green manuring relocates microbiomes in driving the soil functionality of nitrogen cycling to obtain preferable grain yields in thirty years - Guopeng Zhou; Kunkun Fan; Songjuan Gao; Danna Chang; Guilong Li; Ting Liang; Hai Liang; Shun Li; Jiudong Zhang; Zongxian Che; Weidong Cao (Science China Life Sciences, 2024)

Enhanced dewatering extent of sludge by Fe3O4-driven heterogeneous Fenton - Ting Li; Xin Zhang; Yujun Zhou; Jiawei Yang; Fange Cheng; Di Fang; Jianru Liang; Jiansheng Li; Lixiang Zhou (Waste Management, 2024)

Opportunities for converting waste plastics into petrochemicals: Process design, multi-objective optimization, and omnidirectional techno-economic-society-environment assessment - Xiaobo Chen; Jinqing Zhang; Zhibo Zhang; Zihao Zhang; Xin Zhou; Yaqi Zheng; Ting Wang; Guoliang Li; Ruzhen Ma; Qi Han; Hao Yan; Yibin Liu; et al. (Journal of Cleaner Production, 2024)

Urbanization and weather dynamics co-dominated the spatial-temporal variation in pCO2 and CO2 fluxes in small montanic rivers draining diverse landscapes - Zhaoyin Qing; Xiaofeng Wang; Xianxiang Li; Chen Jian; Yi Yang; Ting Zhou; Tingting Liu; Shuangshuang Liu; Yafang Huang; Yixin He (Journal of Environmental Management, 2024)

Coexistence of microplastics and Cd alters soil N transformation by affecting enzyme activity and ammonia oxidizer abundance - Ting Lan; Xiaoman Dong; Shuang Liu; Minghua Zhou; Yang Li; Xuesong Gao (Environmental Pollution, 2024)

Urine pretreatment enhances energy recovery by boosting medium-chain fatty acids production from waste activate sludge through anaerobic fermentation - Huan Liu; Xuan Li; Zehao Zhang; Jibin Li; Ting Zhou; Zhenyao Wang; Qilin Wang (Chemical Engineering Journal, 2024)

One-stone, two birds: Three-dimensional structure and rich-inorganic solid electrolyte interface derived from Bi nanoparticles modified Ti3C2/CNT/rGO aerogel for anode-free potassium metal batteries - Dong-Ting Zhang; Mao-Cheng Liu; Min-Peng Li; Zi-Zhou Yuan; Yu-Xia Hu; Hao Chen; Chen-Yang Li; Ling-Bin Kong; Kun Zhao; Jun-Qiang Ren; Bao Liu (Chemical Engineering Journal, 2024)

MOF derived MnFeOX supported on carbon cloth as electrochemical anode for peroxymonosulfate electro-activation and persistent organic pollutants degradation - Xiansheng Zhang; Yuan Pan; Yunze Wang; Ting Wu; Binbin Shao; Qingyun He; Lingfeng Zhou; Teng Li; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Application of 3D hierarchical porous NiCo-spinel nanosheet array for enhancement of synergistic activation of peroxymonosulfate: Degradation, Intermediates, mechanism and degradation pathway of tetracycline - Yuan Pan; Xiansheng Zhang; Ting Wu; Binbin Shao; Teng Li; Qingyun He; Zehua Chen; Lingfeng Zhou; Sheng Liu; Xinyi Huang; Zhifeng Liu (Chemical Engineering Journal, 2024)

Sources and secondary transformation potentials of aromatic hydrocarbons observed in a medium-sized city in yangtze river delta region: Emphasis on intermediate-volatility naphthalene - Hua Fang; Wenjing Wang; Hongling Xu; Yuzhe Huang; Han Jiang; Ting Wu; Jun Li; Shuping Zha; Jianxi Zhang; Ruicheng Zhou; Xinming Wang (Atmospheric Environment, 2024)

Superior Photocatalytic Activity and Antibacterial Behavior of Chitosan-Anchored Ag/AgCl Composites - Xiao-fang Li; Ya-ting Zhou; Xiao-qiang Feng (Water, Air, & Soil Pollution, 2024)

High-density lipoprotein regulates angiogenesis by affecting autophagy via miRNA-181a-5p - Bi-Ang Kang; Hua-Ming Li; Ya-Ting Chen; Meng-Jie Deng; Yan Li; Yue-Ming Peng; Jian-Jun Gao; Zhi-Wei Mo; Jia-Guo Zhou; Zhi-Jun Ou; Jing-Song Ou (Science China Life Sciences, 2024)

Effects of uranium mining on soil bacterial communities and functions in the Qinghai-Tibet plateau - Qiang Li; Zhuang Xiong; Peng Xiang; Lin Zhou; Ting Zhang; Qian Wu; Changsong Zhao (Chemosphere, 2024)

Optimization of the adsorption performance of herbal residues as lanthanide ion-modified carriers for phosphate by fly ash and its application - Caigao Zhou; Zihan Chen; Guochun Lv; Changlian Xu; Guiyin Wang; Shirong Zhang; Zhanbiao Yang; Zhang Cheng; Junzhuo Cai; Ting Li; Yulin Pu; Zhien Pu; et al. (Chemosphere, 2024)

Whole-body aging mediates the association between exposure to volatile organic compounds and osteoarthritis among U.S. middle-to-old-aged adults - Hao-long Zhou; Dong-sheng Di; Zhang-bo Cui; Ting-ting Zhou; Ting-ting Yuan; Qian Liu; Jian-li Zhang; Xiao Luo; Dan-yang Ling; Qi Wang (Science of The Total Environment, 2024)

Exploring the effect of photobiomodulation and gamma visual stimulation induced by 808 nm and visible LED in Alzheimer's disease mouse model - Hao Xu; Ziyi Luo; Renlong Zhang; Iuliia Golovynska; Yanxia Huang; Soham Samanta; Ting Zhou; Shaowei Li; Bingang Guo; Liwei Liu; Xiaoyu Weng; Jun He; et al. (Journal of Photochemistry and Photobiology B: Biology, 2024)

Overlooked encounter process that affects physical behaviors of stabilized nanoscale zero-valent iron during in situ groundwater remediation - Yujie Xie; Miaoyue Zhang; Lihang Ma; Ting Du; Dan Zhou; Ming-Lai Fu; Baoling Yuan; Xiao-yan Li; Yi-bo Hu (Journal of Hazardous Materials, 2024)

Enhanced short-chain fatty acids production from anaerobic fermentation of secondary sludge by lignosulfonate addition: Towards circular economy - Zhenyao Wang; Xuan Li; Huan Liu; Ting Zhou; Jibin Li; Muhammad Ahmar Siddiqui; Carol Sze Ki Lin; Siyu Huang; Julie M. Cairney; Qilin Wang (Journal of Cleaner Production, 2024)

Arbuscular mycorrhizae mitigate negative impacts of soil biodiversity loss on grassland productivity - Jiqiong Zhou; Yingying Su; Xiangjun Li; Yakov Kuzyakov; Pengsen Wang; Jinchao Gong; Xuxu Li; Lin Liu; Xinquan Zhang; Congyu Ma; Xiao Ma; Ting Huang; et al. (Journal of Environmental Management, 2024)

Prediction of phosphate adsorption amount, capacity and kinetics via machine learning: A generally physical-based process and proposed strategy of using descriptive text messages to enrich datasets - Baiqin Zhou; Huiping Li; Ziyu Wang; Hui Huang; Yujun Wang; Ruichun Yang; Ranran Huo; Xiaoyan Xu; Ting Zhou; Xiaochen Dong (Chemical Engineering Journal, 2024)

Boosting H2O2 utilization efficiency in benzene hydroxylation to phenol via isolated single VO4 site on hydrophobic poly(ionic liquid)-derivative - Zhe Chen; Chao Wu; Xiaoling Liu; Ting Li; Menglin Xie; Shibo Xi; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2024)

Label-free fluorescence detection of human 8-oxoguanine DNA glycosylase activity amplified by target-induced rolling circle amplification - Mengxu Sun; Xiao Chen; Xiang Chen; Qianying Zhou; Ting Huang; Tong Li; Baoping Xie; Chunrong Li; Jin-Xiang Chen; Zong Dai; Jun Chen (Analytica Chimica Acta, 2024)

Long‐term warming increased carbon sequestration capacity in a humid subtropical forest - Xujun Liu; Zhiyang Lie; Peter B. Reich; Guoyi Zhou; Junhua Yan; Wenjuan Huang; Yingping Wang; Josep Peñuelas; David T. Tissue; Mengdi Zhao; Ting Wu; Donghai Wu; et al. (Global Change Biology, 2024)
Tropical and subtropical forests play a crucial role in global carbon (C) pools, and their responses to warming can significantly impact C‐climate feedback and predictions of future global warming. Despite earth system models projecting reductions in land C storage with warming, the magnitude of this response varies greatly between models, particularly in tropical and subtropical regions. Here, we conducted a field ecosystem‐level warming experiment in a subtropical forest in southern China, by translocating mesocosms (ecosystem composed of soils and plants) across 600 m elevation gradients with temperature gradients of 2.1°C (moderate warming), to explore the response of ecosystem C dynamics of the subtropical forest to continuous 6‐year warming. Compared with the control, the ecosystem C stock decreased by 3.8% under the first year of 2.1°C warming; but increased by 13.4% by the sixth year of 2.1°C warming. The increased ecosystem C stock by the sixth year of warming was mainly attributed to a combination of sustained increased plant C stock due to the maintenance of a high plant growth rate and unchanged soil C stock. The unchanged soil C stock was driven by compensating and offsetting thermal adaptation of soil microorganisms (unresponsive soil respiration and enzyme activity, and more stable microbial community), increased plant C input, and inhibitory C loss (decreased C leaching and inhibited temperature sensitivity of soil respiration) from soil drying. These results suggest that the humid subtropical forest C pool would not necessarily diminish consistently under future long‐term warming. We highlight that differential and asynchronous responses of plant and soil C processes over relatively long‐term periods should be considered when predicting the effects of climate warming on ecosystem C dynamics of subtropical forests.

How accompanying ions affect soil heavy metal removal by polyepoxysuccinic acid during washing? - Qinmei Zhong; Shirong Zhang; Ting Li; Guoshu Gong; Xiaoxun Xu; Guiyin Wang; Xiaomei Pan; Wei Zhou; Yulin Pu; Lulu Long; Shengtao Yang; Yue Yuan (Chemosphere, 2023)

Enhancing microbial salt tolerance through low-voltage stimulation for improved p-chloronitrobenzene (p-CNB) removal in high-salinity wastewater - Long Chen; Li-Ting Zhou; Yang-Cheng Ding; Di Wu; Hua-Jun Feng (Science of The Total Environment, 2023)

Diverse indole-diterpenoids with protein tyrosine phosphatase 1B inhibitory activities from the marine coral-derived fungus Aspergillus sp. ZF-104 - Fei Zhang; Li Yang; Qing-Yi Xie; Jiao-Cen Guo; Qing-Yun Ma; Lu-Ting Dai; Li-Man Zhou; Hao-Fu Dai; Fan-Dong Kong; Du-Qiang Luo; You-Xing Zhao (Phytochemistry, 2023)

Applied gradient boosting decision tree algorithms for accurate prediction of trihalomethanes: A case study in dual-sources drinking water distribution system in metropolitan - Huiping Li; Ranran Huo; Xiaoyan Xu; Baiqin Zhou; Mengxian Hu; Ting Zhou; Xiaochen Dong; Runyao Huang; Li Xie; Weihai Pang (Journal of Water Process Engineering, 2023)

Molecular insights into nitrogen constraint for niche partitioning and physiological adaptation of coastal Synechococcus assemblages - Ting Wang; Yuting Zhou; Jialin Li; Song Qin (Environmental Research, 2023)

Distributed bending stiffness estimation of bridges using adaptive inverse unit load method - Run-Zhou You; Ting-Hua Yi; Liang Ren; Hong-Nan Li (Engineering Structures, 2023)

Enhancing methane production from anaerobic digestion of secondary sludge through lignosulfonate addition: Feasibility, mechanisms, and implications - Zhenyao Wang; Xuan Li; Huan Liu; Ting Zhou; Jibin Li; Muhammad Ahmar Siddiqui; Carol Sze Ki Lin; Mohammad Rafe Hatshan; Siyu Huang; Julie M. Cairney; Qilin Wang (Bioresource Technology, 2023)

STAT6 promoting oxalate crystal deposition-induced renal fibrosis by mediating macrophage-to-myofibroblast transition via inhibiting fatty acid oxidation - Tianhui Yuan; Yuqi Xia; Shengyu Pan; Bojun Li; Zehua Ye; Xinzhou Yan; Weimin Hu; Lei Li; Baofeng Song; Weimin Yu; Haoyong Li; Ting Rao; et al. (Inflammation Research, 2023)

White matter alterations in mild cognitive impairment revealed by meta-analysis of diffusion tensor imaging using tract-based spatial statistics - Longfei Li; Wei Yang; Yu Wan; Hailong Shen; Ting Wang; Liangliang Ping; Chuanxin Liu; Min Chen; Hao Yu; Shushu Jin; Yuqi Cheng; Xiufeng Xu; et al. (Brain Imaging and Behavior, 2023)

Topsoil selenium (Se) under Se-rich farming in China: Current status, cropping impacts and ecological risk assessment - Li Qian; Ting Wang; Yajuan Shi; Qiuyun Xu; Xuan Zhou; Lingjie Ke; Ruoyu Liang; Chuancheng Fu; Xiaoqi Zheng; Guoxin Sun (Journal of Environmental Management, 2023)

Stability and emetic activity of enterotoxin like X (SElX) with high carrier rate of food poisoning Staphylococcus aureus - Yangli Wan; Liu Yang; Qianhong Li; Xiaowen Wang; Ting Zhou; Dishi Chen; Li Li; Yeru Wang; Xin Wang (International Journal of Food Microbiology, 2023)

Promoting dewatering efficiency of sludge by bioleaching coupling chemical flocculation - Ting Li; Jiawei Yang; Yujun Zhou; Xuan Liu; Yixin Luo; Di Fang; Jianru Liang; Jiansheng Li; Lixiang Zhou (Environmental Research, 2023)

Laccase-triggered one-step fabrication of positively charged phenolic acid-amine networks for nanofiltration - Ping Fu; Di Zhou; Wan-Long Li; Wan-Ting Lin; Xiao-Jun Huang; Zhi-Kang Xu; Ling-Shu Wan (Desalination, 2023)

Multifunctional platinum-tellurium nanorods modified with hyaluronic acid remove reactive oxygen species to improve the photothermal treatment of rheumatoid arthritis - Meng-Wen Ma; Kai-Lin He; Chao-Qing Li; Xiao-Ting Xie; Sui Zhou; Bin Zhang; Xiao-Lin Hou; Cheng Li; Yuan-Di Zhao; Ling-Li Dong; Bo Liu (Chemical Engineering Journal, 2023)

Metagenomics insights into high-rate nitrogen removal from municipal wastewater by integrated nitrification, partial denitrification and Anammox at an extremely short hydraulic retention time - Junjiang Chen; Xiaonong Zhang; Li Zhou; Zixuan Zhu; Zhiqiang Wu; Kangyu Zhang; Yiwen Wang; Ting Ju; Xu Ji; Da Jin; Peng Wu; Xingxing Zhang (Bioresource Technology, 2023)

Long-term field translocation differentially affects arbuscular mycorrhizal and ectomycorrhizal trees in a sub-tropical forest - Ting Wu; David T Tissue; Wei Su; Xu Li; Shimin Yang; Xujun Liu; Yue Liu; Zhiyang Lie; Shuyidan Zhou; Ze Meng; Junhua Yan; Xuli Tang; et al. (Agricultural and Forest Meteorology, 2023)

Biofilm bioactivity affects nitrogen metabolism in a push-flow microalgae-bacteria biofilm reactor during aeration-free greywater treatment - Beibei Wu; Ting Ran; Sibei Liu; Qian Li; Xiaocai Cui; Yun Zhou (Water Research, 2023)

Maternal transfer of F-53B inhibited neurobehavior in zebrafish offspring larvae and potential mechanisms: Dopaminergic dysfunction, eye development defects and disrupted calcium homeostasis - Luyin Wu; Mohammed Zeeshan; Yao Dang; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Yuan-Yuan Fan; Ming-Kun Sun; Tao Yu; Yue Wen; et al. (Science of The Total Environment, 2023)

Assessment of HCHO in Beijing during 2009 to 2020 using satellite observation and numerical model: Spatial characteristic and impact factor - Jiachen Fan; Tijian Wang; Qingeng Wang; Danyang Ma; Yasong Li; Minqiang Zhou; Ting Wang (Science of The Total Environment, 2023)

Schwertmannite-based heterogeneous Fenton for enhancing sludge dewaterability over a wide pH range - Ting Li; Xin Zhang; Yujun Zhou; Xin Du; Di Fang; Jianru Liang; Jiansheng Li; Lixiang Zhou (Journal of Hazardous Materials, 2023)

Impurity removal of acid leachates from rare earth slag with sodium hydroxide and ammonium bicarbonate: Mechanism and efficiency optimization - Yilin Wu; Shirong Zhang; Guiyin Wang; Ting Li; Xiaoxun Xu; Yulin Pu; Wei Zhou; Yun Li; Yongxia Jia (Journal of Cleaner Production, 2023)

Efficient removal of Cr(VI) from wastewater by ZnO-polyacrylic acid/cellulose fiber/polyethylene glycol hydrogel: Synergistic effect of adsorption and photocatalytic reduction - Qing Li; Xiaojie Zhuang; Guanhong Zhou; Zhenfei Yang; Ting Yang; Hongbo Xiao; Tao Xu; Wenlei Wang (Journal of Environmental Chemical Engineering, 2023)

Influence of cold atmospheric pressure plasma treatment of Spirulina platensis slurry over biomass characteristics - Zihan Li; Ting Zhou; Qi Zhang; Tongying Liu; Jiangling Lai; Canbo Wang; Leipeng Cao; Yuhuan Liu; Roger Ruan; Mingxiong Xue; Yunpu Wang; Xian Cui; et al. (Bioresource Technology, 2023)

Contribution of sea surface temperature anomalies in the Barents and Yellow-Japan Seas to summer high temperature anomalies over the eastern Tibetan Plateau - Ting Zhang; Ge Liu; Mingkeng Duan; Xin Mao; Xinchen Wei; Yuhan Feng; Yuwei Zhou; Jingxin Li (Atmospheric Research, 2023)

The hairy root induction efficiency and that plumbagin of Plumbago auriculata L. - Zian Zhao; Suping Gao; Ju Hu; Ting Lei; Yunzhu Zhou; Yirui Li; Cailei Liu (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Tree communities and functional traits determine herbivore compositional turnover - Ming-Qiang Wang; Zhixin Wen; Jinzhao Ke; Douglas Chesters; Yi Li; Jing-Ting Chen; Arong Luo; Xiaoyu Shi; Qing-Song Zhou; Xiao-Juan Liu; Keping Ma; Helge Bruelheide; et al. (Oecologia, 2023)

Effect of humic substances on the anaerobic digestion of secondary sludge in wastewater treatment plants: a review - Zhenyao Wang; Xuan Li; Muhammad Ahmar Siddiqui; Huan Liu; Ting Zhou; Lei Zheng; Siyu Huang; Li Gao; Carol Sze Ki Lin; Qilin Wang (Environmental Chemistry Letters, 2023)

Salidroside promotes healthy longevity by interfering with HSP90 activity - Jianfei Zhang; Zhiquan Li; Jiangbo Song; Lei Zhou; Xin Chen; Wen Ge; Tianyi Dong; Yuxin Luo; Ting Mao; Zheng Li; Duan Tan; Lene Juel Rasmussen; et al. (GeroScience, 2023)

A cytochrome P450 system initiates 4-nitroanisole degradation in Rhodococcus sp. strain JS3073 - Shu-Ting Zhang; Tao Li; Shi-Kai Deng; Jim C. Spain; Ning-Yi Zhou (Journal of Hazardous Materials, 2023)

Environmental pollutant pre- and polyfluoroalkyl substances are associated with electrocardiogram parameters disorder in adults - Yuan-Yuan Fan; Chu Chu; Yun-Ting Zhang; Kun Zhao; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Li-Hao Guo; Lu-Yin Wu; Li-Zi Lin; Ru-Qing Liu; Wenru Feng; et al. (Journal of Hazardous Materials, 2023)

Surface engineering of Al2O3 nanotubes by ureasolysis method for activating persulfate degradation of antibiotics - Zheng-Wu Wang; Mei-Yun Xiao; Jun-Feng Tang; Ming-Qian Li; Xia-Yin Yin; Ting Wang; Yi-Zhou Zhu; Dai-Wen Pang; He-Fang Wang (Journal of Hazardous Materials, 2023)

Research on the reaction path of chlorobenzene oxidation by electrochemical-sodium persulfate system - Shicheng Yuan; Hui Hu; Hao Huang; Zhongming Chen; Jiaxin Chen; Mi Zhang; Kunpeng Li; Ting Zhou; Ruibin Lv (Journal of Cleaner Production, 2023)

Prenatal exposure to PM2.5 and its constituents with children's BMI Z-score in the first three years: A birth cohort study - Shuang Zhou; Tiantian Li; Na Han; Kai Zhang; Yi Zhang; Qin Li; Yuelong Ji; Jue Liu; Hui Wang; Jianlin Hu; Ting Liu; Hein Raat; et al. (Environmental Research, 2023)

Spatial–Temporal Evolution and Countermeasures for Coal and Gas Outbursts Represented as a Dynamic System - Chaojun Fan; Lingjin Xu; Derek Elsworth; Mingkun Luo; Ting Liu; Sheng Li; Lijun Zhou; Weiwei Su (Rock Mechanics and Rock Engineering, 2023)

IRAK-M Ablation Promotes Status Epilepticus-Induced Neuroinflammation via Activating M1 Microglia and Impairing Excitatory Synaptic Function - Xiao-Shan Liang; Ting-Lin Qian; Yi-Fan Xiong; Xiao-Tao Liang; Yue-Wen Ding; Xiao-Yu Zhu; Yun-Lv Li; Jie-Li Zhou; Le-Yi Tan; Wei-Peng Li; Wei Xie (Molecular Neurobiology, 2023)

Orally Induced High Serum Level of Trimethylamine N-oxide Worsened Glial Reaction and Neuroinflammation on MPTP-Induced Acute Parkinson’s Disease Model Mice - Chen-Meng Qiao; Wei Quan; Yu Zhou; Gu-Yu Niu; Hui Hong; Jian Wu; Li-Ping Zhao; Ting Li; Chun Cui; Wei-Jiang Zhao; Yan-Qin Shen (Molecular Neurobiology, 2023)

Isoptericola croceus sp. nov., a novel actinobacterium isolated from saline–alkali soil - Yu-Ting OuYang; Ai-Ping Lv; Lan Liu; Ting-Ting Li; Yi Zhou; Ting-Ting She; Li-Xiang Cao; Jian-Yu Jiao; Shuang Wang; Wen-Jun Li (Antonie van Leeuwenhoek, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

MiR-425-5p suppression of Crebzf regulates oocyte aging via chromatin modification - Kadiliya Jueraitetibaike; Ting Tang; Rujun Ma; Shanmeizi Zhao; Ronghua Wu; Yang Yang; Xuan Huang; Xi Cheng; Cheng Zhou; Hong Zhang; Lu Zheng; Xie Ge; et al. (GeroScience, 2023)
Female infertility due to declining oocyte quality with age remains a significant challenge for patients and physicians, despite extensive research efforts. Recent studies suggest that microRNAs (miRNAs), which respond to various stressors in the aging process, may provide a promising solution. With the approval of small RNA drugs for clinical use, miRNA-based treatment of oocyte aging appears to be a viable option. Through high-throughput sequencing, miR-425-5p was identified as the only miRNA elevated under natural aging and oxidative stress. Microinjection of inhibitors to inhibit miR-425-5p effectively improved compromised phenotypes of old oocytes in vitro. Further investigation revealed that Crebzf acts as a mediator of miR-425-5p 's age-related functions in old oocytes. In vivo treatment with miR-425-5p antagomirs significantly improved impaired oocyte development in reproductively old females by targeting Crebzf . Single-cell RNA sequencing revealed that Crebzf plays a vital role in regulating mRNAs targeting histone H3, trimethylated lysine 4 (H3K4me3), a crucial marker for transcriptional silencing. Overexpression of miR-425-5p could hinder oocyte maturation by downregulating Crebzf expression and disrupting transcriptional regulation. Our findings provide new insights into the potential of miR-425-5p antagomirs as a treatment for female infertility and highlight an elegant mechanism by which miR-425-5p inhibition of Crebzf inhibits a developmental switch in GV oocytes by regulating a group of histone methyltransferase mRNAs.

Climate change impacts on wastewater infrastructure: A systematic review and typological adaptation strategy - Jibin Li; Xuan Li; Huan Liu; Li Gao; Weitong Wang; Zhenyao Wang; Ting Zhou; Qilin Wang (Water Research, 2023)

Association of long-term particulate matter exposure with all-cause mortality among patients with ovarian cancer: A prospective cohort - Yi-Zi Li; Shu-Hong Huang; Su Shi; Wen-Xiao Chen; Yi-Fan Wei; Bing-Jie Zou; Wei Yao; Lu Zhou; Fang-Hua Liu; Song Gao; Shi Yan; Xue Qin; et al. (Science of The Total Environment, 2023)

Melatonin-induced plant adaptation to cadmium stress involves enhanced phytochelatin synthesis and nutrient homeostasis in Solanum lycopersicum L. - Qufan Xing; Md. Kamrul Hasan; Zhichao Li; Ting Yang; Weiduo Jin; Zhenyu Qi; Ping Yang; Guanghui Wang; Golam Jalal Ahammed; Jie Zhou (Journal of Hazardous Materials, 2023)

Construction of PES mixed matrix membranes incorporating ZnFe2O4 @MXene composites with high permeability and antifouling performance - Ping Zhou; Ting Wang; Chun-Hui Du; Guo-qin Wang; Li-guang Wu; Xiao-jia Jiang; Hai-Chang Guo (Journal of Environmental Chemical Engineering, 2023)

Synthetic phylogenetically diverse communities promote denitrification and stability - Min Zhou; Xiaotong Guan; Ting Deng; Ruiwen Hu; Lu Qian; Xueqin Yang; Bo Wu; Juan Li; Qiang He; Longfei Shu; Qingyun Yan; Zhili He (Environmental Research, 2023)

MOF-on-MOF-derived hollow FeNi3/N-doped carbon nanorods for efficient oxygen evolution - Dandan Chen; Xiangli Ji; Xuemei Zhou; Qiuhong Sun; Shaojie Xu; Lujiao Mao; Zeyi Guo; Jia Guan; Ting-Ting Li; Jinjie Qian (Chemical Engineering Journal, 2023)

H2S-releasing versatile hydrogel dressing with potent antimicrobial, anti-inflammatory, epithelialization and angiogenic capabilities for diabetic wound healing - Jiale Chen; Zhixiang Mu; Dongfan Chen; Chen Huang; Ting Jin; Lin Li; Youyun Zeng; Qiang Zhou; Yanmei Zhang; Hongli Mao; Hui Deng; Xinkun Shen; et al. (Chemical Engineering Journal, 2023)

Correction: Changes in soil phosphorus fractions following the conversion of Chinese fir plantations to evergreen broad-leaved forests in subtropical China - Junjie Lei; Yuanying Peng; Juan Cao; Rujie Li; Qiang Jia; Xiao Shi; Ting Zhou; Wende Yan; Xiaoyong Chen (European Journal of Forest Research, 2023)

Changes in soil phosphorus fractions following the conversion of Chinese fir plantations to evergreen broad-leaved forests in subtropical China - Junjie Lei; Yuanying Peng; Juan Cao; Rujie Li; Qiang Jia; Xiao Shi; Ting Zhou; Wende Yan; Xiaoyong Chen (European Journal of Forest Research, 2023)

Expression profiles and bioinformatic analysis of microRNAs in myocardium of diabetic cardiomyopathy mice - Ting Wang; Lingling Yuan; Yanxia Chen; Jing Wang; Na Li; Hong Zhou (Genes & Genomics, 2023)

Gross nitrogen transformations and ammonia oxidizers affected by nitrification inhibitors and/or organic amendments in a calcareous soil: A 15N tracing study - Xiaoqian He; Mengxiao Li; Minghua Zhou; Wei Zhou; Guangdeng Chen; Yanyan Zhang; Yang Li; Min Zeng; Xuesong Gao; Ting Lan (Applied Soil Ecology, 2023)

Two new diterpenoids from the rhizomes of Zingiber officinale - Mi Zhou; Ting Li; Chen Zeng; Da-bo Pan; Hai-bo Li; Yang Yu (Natural Product Research, 2023)

Experiments and machine learning-based modeling for haloacetic acids rejection by nanofiltration: Influence of solute properties and operating conditions - Feifei Wang; Weikang Wang; Hongjie Wang; Zilong Zhao; Ting Zhou; Chengjun Jiang; Ji Li; Xiaolei Zhang; Tianzhe Liang; Wenyi Dong (Science of The Total Environment, 2023)

Advanced oxidation-based combined conditioning technologies to improve sludge dewaterability: A mini review - Zhongqi He; Xu Zhou; Xiumin Fan; Wenbiao Jin; Chuan Chen; Bowen Yan; Shiyu Yin; Ting Zhou; Xuan Li; Guangming Jiang (Journal of Water Process Engineering, 2023)

Engineering oxygen vacancies of 2D WO3 for visible-light-driven benzene hydroxylation with dioxygen - Tao Chen; Fangpei Ma; Zhe Chen; Menglin Xie; Ting Li; Yu Zhou; Jun Wang (Chemical Engineering Journal, 2023)

Enhanced ion recognition through bi-directionally layered spacing regulation of 1D tubular titanate nanofilms - Shiyu Sun; Xin Huang; Jingtao Bi; Na Wang; Ting Wang; Lina Zhou; Li Wang; Shyam Lamichhane; Hongxun Hao (Chemical Engineering Journal, 2023)

Agomir miRNA-150-5p alleviates pristane-induced lupus by suppressing myeloid dendritic cells activation and inflammation via TREM-1 axis - Chenran Yue; Wenqian Wang; Sheng Gao; Jianzhong Ye; Ting Zhang; Zhouhang Xing; Yuanyuan Xie; Hengrong Qian; Xueyin Zhou; Shuting Li; Anni Yu; Liangxing Wang; et al. (Inflammation Research, 2023)

Cadmium-resistant phosphate-solubilizing bacteria immobilized on phosphoric acid-ball milling modified biochar enhances soil cadmium passivation and phosphorus bioavailability - Tingrui Zhang; Ting Li; Zijun Zhou; Zengqiang Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Yongxia Jia; Xiaojing Liu; Yun Li (Science of The Total Environment, 2023)

Paleo-temperature inferred from brGDGTs over the past 18 cal ka BP from Lake Barrine, tropical NE Australia - Ting Li; Rainy Comley; Enlou Zhang; Youping Zhou; Xiuwen Zhou; Niels C. Munksgaard; Zeyang Zhu; Jordahna Haig; Fengfeng Zheng; Michael I. Bird (Quaternary Science Reviews, 2023)

Reconstruction of three-dimensional porous media using multi-scale generative adversarial networks - Ting Zhang; Mengling Ni; Qijie Guan; Deya Li; Shaojing Zhou; Yi Du (Journal of Applied Geophysics, 2023)

A label-free fluorescent aptasensor based on a novel exponential rolling circle amplification for highly sensitive ochratoxin A detection - Daozhong Zhu; Ting Huang; Qianying Zhou; Zizhong Yang; Birong Liu; Minmin Li; Chunrong Li; Jin-Xiang Chen; Zong Dai; Jun Chen (Food Chemistry, 2023)

Preferential, synergistic sorption and reduction of Cr(VI) from chromium–rhodamine B mixed wastewater by magnetic porous biochar derived from wasted Myriophyllum aquaticum biomass - Dong Zhang; Danli Zhou; Li Lu; Ming Zhang; Ting Lü; Jingang Huang; Hongting Zhao; Jie Zhou; Jörg Rinklebe (Environmental Pollution, 2023)

Recent development of sustainable self-healable electronic skin applications, a review with insight - Jean-Sébastien Benas; Fang-Cheng Liang; Manikandan Venkatesan; Zhen-Li Yan; Wei-Cheng Chen; Su-Ting Han; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2023)

Long-term effect of free ammonia pretreatment on the semi-continuous anaerobic primary sludge digester for enhancing performance: Towards sustainable sludge treatment - Huan Liu; Xuan Li; Ting Zhou; Zehao Zhang; Long D. Nghiem; Li Gao; Qilin Wang (Chemical Engineering Journal, 2023)

Soil organic matter content prediction using Vis-NIRS based on different wavelength optimization algorithms and inversion models - Wei Zhou; Jieyun Xiao; Haoran Li; Qi Chen; Ting Wang; Qian Wang; Tianxiang Yue (Journal of Soils and Sediments, 2023)

Clinical and genome-wide association analysis of chemoradiation-induced hearing loss in nasopharyngeal carcinoma - Yong-Qiao He; Lu-Ting Luo; Tong-Min Wang; Wen-Qiong Xue; Da-Wei Yang; Dan-Hua Li; Hua Diao; Ruo-Wen Xiao; Chang-Mi Deng; Wen-Li Zhang; Ying Liao; Yan-Xia Wu; et al. (Human Genetics, 2023)
Chemoradiation-induced hearing loss (CRIHL) is one of the most devasting side effects for nasopharyngeal carcinoma (NPC) patients, which seriously affects survivors’ long-term quality of life. However, few studies have comprehensively characterized the risk factors for CRIHL. In this study, we found that age at diagnosis, tumor stage, and concurrent cisplatin dose were positively associated with chemoradiation-induced hearing loss. We performed a genome-wide association study (GWAS) in 777 NPC patients and identified rs1050851 (within the exon 2 of NFKBIA ), a variant with a high deleteriousness score, to be significantly associated with hearing loss risk (HR = 5.46, 95% CI 2.93–10.18, P = 9.51 × 10 –08 ). The risk genotype of rs1050851 was associated with higher NFKBIA expression, which was correlated with lower cellular tolerance to cisplatin. According to permutation-based enrichment analysis, the variants mapping to 149 hereditary deafness genes were significantly enriched among GWAS top signals, which indicated the genetic similarity between hereditary deafness and CRIHL. Pathway analysis suggested that synaptic signaling was involved in the development of CRIHL. Additionally, the risk score integrating genetic and clinical factors can predict the risk of hearing loss with a relatively good performance in the test set. Collectively, this study shed new light on the etiology of chemoradiation-induced hearing loss, which facilitates high-risk individuals’ identification for personalized prevention and treatment.

Plastic wastes and surface antibiotic resistance genes pollution in mangrove environments - Ruikun Sun; Yu Liu; Ting Li; Zhong-Ji Qian; Chunxia Zhou; Pengzhi Hong; Shengli Sun; Chengyong Li (Environmental Monitoring and Assessment, 2023)

Characterization of ionic liquids removing heavy metals from electroplating sludge: Influencing factors, optimisation strategies and reaction mechanisms - Chenchen Cao; Xiaoxun Xu; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Shirong Zhang; Ting Li; Yulin Pu; Guochun Lv; Changlian Xu; Junzhuo Cai; Wei Zhou; et al. (Chemosphere, 2023)

Watershed urbanization dominated the spatiotemporal pattern of riverine methane emissions: Evidence from montanic streams that drain different landscapes in Southwest China - Xianxiang Li; Yixin He; Xiaofeng Wang; Huai Chen; Tingting Liu; Yizi Que; Xingzhong Yuan; Shengnan Wu; Ting Zhou (Science of The Total Environment, 2023)

Sulfite pretreatment enhances the medium-chain fatty acids production from waste activated sludge anaerobic fermentation - Xuan Li; Huan Liu; Zehao Zhang; Ting Zhou; Qilin Wang (Science of The Total Environment, 2023)

Quantifying the effects of submicroscopic metallic iron on VIS–NIR spectra of lunar soils - Yanhua Peng; Siting Zhang; Hong Tang; Zhuang Guo; Wen Yu; Guozhu Chen; Chen Li; Bingkui Miao; Bing Mo; Encheng He; Ting Zhou; Zhipeng Xia; et al. (Icarus, 2023)

Fabrication and characterization of self-assembled whey protein isolate/short linear glucan core–shell nanoparticles for sustained release of curcumin - Xiaojing Li; Ting Xu; Caie Wu; Gongjian Fan; Tingting Li; Yaosong Wang; Dandan Zhou (Food Chemistry, 2023)

Development and characterization of antioxidant composite films based on starch and gelatin incorporating resveratrol fabricated by extrusion compression moulding - Hejun Wu; Ting Li; Lu Peng; Jie Wang; Yuixiao Lei; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang (Food Hydrocolloids, 2023)

CO2 improves the anaerobic biodegradation intensity and selectivity of heterocyclic hydrocarbons in heavy oil - Lu Zhang; Xiangyu Zhou; Chuxiao Hu; Shun Yao; Lei Shi; Tong Niu; Xin Li; Lihua Tong; Jiaqiang Zhang; Ting Ma; Wenjie Xia (Environmental Research, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Occurrence and ecological risk assessment of 16 phthalates in surface water of the mainstream of the Yangtze River, China - Jia-Nan Ren; Ning-Zheng Zhu; Xiang-Zhou Meng; Chong-Jing Gao; Kai Li; Li-Min Jin; Ting-Ting Shang; Fang-Ting Ai; Ming-Hong Cai; Jian-Fu Zhao (Environmental Science and Pollution Research, 2023)

Karst-ecological changes during the middle and late Holocene in Southwest China revealed by δ18O and δ13C records in a stalagmite - Rong Duan; Ting-Yong Li; Jun-Yun Li; Christoph Spötl; Hong-Chun Li; Hai-Bo Wang; Hai Cheng; You-Feng Ning; Chuan-Chou Shen; Jing-Li Zhou; Chao-Jun Chen; Tsai-Luen Yu; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

A minimal genome design to maximally guarantee fertile inter-subspecific hybrid rice - Penghui Zhou; Zhengji Wang; Xingchen Zhu; Yao Tang; Liang Ye; Huihui Yu; Yating Li; Ningke Zhang; Ting Liu; Tian Wang; Yuying Wu; Dengyun Cao; et al. (Molecular Plant, 2023)

Spectral light quality regulates the morphogenesis, architecture, and flowering in pepper (Capsicum annuum L.) - Wen-Feng Nie; Yu Li; Yue Chen; Yong Zhou; Ting Yu; Yanhong Zhou; Youxin Yang (Journal of Photochemistry and Photobiology B: Biology, 2023)

Formation and characterization of plant-based amyloid fibrils from hemp seed protein - Ines Kutzli; Jiangtao Zhou; Ting Li; Stefan K. Baier; Raffaele Mezzenga (Food Hydrocolloids, 2023)

Insights into the pigment and non-pigment phenolic profile of polyphenol extracts of jujube peel and their antioxidant and lipid-lowering activities - Jin-Feng Dou; Cai-E Wu; Gong-Jian Fan; Ting-Ting Li; Xiao-Jing Li; Dan-Dan Zhou; Jin-Peng Zhu; Chun-Mei Li (Food Bioscience, 2023)

Sb2Te3 hexagonal nanoplates as conversion-alloying anode materials for superior potassium-ion storage via physicochemical confinement effect of dual carbon matrix - Shaokun Chong; Shuangyan Qiao; Lingling Yuan; Qianwen Zhou; Ting Li; Shihong Dong; Yikun Wang; Meng Ma; Wei Huang (Chemical Engineering Journal, 2023)

Polymorphism of Pradofloxacin: Crystal Structure Analysis, Stability Study, and Phase Transformation Behavior - Wenlei Li; Lina Zhou; Beiqian Tian; Kui Chen; Yaoguang Feng; Ting Wang; Na Wang; Xin Huang; Hongxun Hao (Pharmaceutical Research, 2023)

Inhibition of ferroptosis by icariin treatment attenuates excessive ethanol consumption-induced atrial remodeling and susceptibility to atrial fibrillation, role of SIRT1 - Li-Ming Yu; Xue Dong; Tao Huang; Ji-Kai Zhao; Zi-Jun Zhou; Yu-Ting Huang; Yin-Li Xu; Qiu-Sheng Zhao; Zhi-Shang Wang; Hui Jiang; Zong-Tao Yin; Hui-Shan Wang (Apoptosis, 2023)

Comprehensive treatment strategy for diesel truck exhaust - Tian Li; Hai-Li Yang; Le-Tian Xu; Yu-Ting Zhou; Yong-Jun Min; Shi-Cheng Yan; Yong-Hui Zhang; Xiao-Ming Wang (Environmental Science and Pollution Research, 2023)

Potential antiplatelet aggregation metabolites from the discarded sorghum ( Sorghum bicolor L.) root - Wan-ting Xu; Qiao An; Ling-hui Ruan; Fei Zhou; Lang Zhou; Mei Peng; Li-lang Li; Xiao-sheng Yang; Qi-ji Li; Juan Yang (Natural Product Research, 2023)

Enhancing sludge dewatering efficiency through bioleaching facilitated by increasing reactive oxygen species - Ting Li; Jiawei Yang; Yujun Zhou; Yixin Luo; Bo Zhou; Di Fang; Jiansheng Li; Lixiang Zhou (Water Research, 2023)

Insight into the formation mechanism of algal biofilm in soy sauce wastewater - Jun Qian; Ting Wan; Yuxin Ye; Jingjing Li; Tatsuki Toda; Hongwu Li; Mutsumi Sekine; Yoshiki Takayama; Shinichi Koga; Shengxi Shao; Liangliang Fan; Peilun Xu; et al. (Journal of Cleaner Production, 2023)

ApCYP4C6 participates in the metabolism of glucosinolates in pea aphids Acyrthosiphon pisum - Lei Liu; Wen-Jun Wang; Li-Wen Song; Yi-Ting Wu; Jiang-Wen Wei; Sen-Shan Wang; Jing-Jiang Zhou (Journal of Asia-Pacific Entomology, 2023)

Facile synthesis of novel helical imprinted fibers based on zucchini-derived microcoils for efficient recognition of target protein in biological sample - Xinya Xu; Yundong Xie; Pengqi Guo; Yongheng Shi; Meng Sun; Jing Zhou; Chuan Wang; Chaojun Han; Jiping Liu; Ting Li (Food Chemistry, 2023)

Sustained-release antibacterial gelatin films: Effects of diatomite/carvacrol complex on their structure, physicochemical and antibacterial properties - Hejun Wu; Ling Ma; Sen Li; Jie Wang; Ting Li; Lu Peng; Shasha Li; Qingye Li; Xiangyang Yuan; Man Zhou; Zhiqing Zhang; Yuntao Liu (Food Packaging and Shelf Life, 2023)

Effect of potassium fertilizer on tea yield and quality: A meta-analysis - Shiqi Xi; Hongyu Chu; Zijun Zhou; Ting Li; Shirong Zhang; Xiaoxun Xu; Yulin Pu; Guiyin Wang; Yongxia Jia; Xiaojing Liu (European Journal of Agronomy, 2023)

UV-Laser ablation enhanced Joule-heating catalyst support for electrified MSR in microreactor - Xinying Li; Ding Yuan; Tian Xie; Quancong Zhang; Wenjun Xu; Ting Fu; Xuyang Chu; Tao Luo; Linjing Wu; Wei Zhou (Chemical Engineering Journal, 2023)

Impact of BSG/CD147 gene expression on diagnostic, prognostic and therapeutic strategies towards malignant cancers and possible susceptibility to SARS-CoV-2 - Jiewen Fu; Binghui Song; Jiaman Du; Shuguang Liu; Jiayue He; Ting Xiao; Baixu Zhou; Dabing Li; Xiaoyan Liu; Tao He; Jingliang Cheng; Junjiang Fu (Molecular Biology Reports, 2023)

Effects of exogenous carbon and nitrification inhibitors on denitrification rate, product stoichiometry and nirS/nirK-type denitrifiers in a calcareous soil: evidence from 15 N anaerobic microcosm assays - Ting Lan; Mengxiao Li; Xiaoqian He; Junji Yuan; Minghua Zhou; Xiaoyan Tang; Yanyan Zhang; Yang Li; Zhaonan Tian; Xuesong Gao (Journal of Soils and Sediments, 2023)

Effects of long-term grazing exclusion on vegetation structure, soil water holding capacity, carbon and nitrogen sequestration capacity in an alpine meadow on the Tibetan Plateau - Yong-sheng Yang; Fa-wei Zhang; Xian-rong Xie; Jun-bang Wang; Ying-nian Li; Xiao-tao Huang; Hui-ting Li; Hua-kun Zhou (Journal of Mountain Science, 2023)

Effect of chromium stress on metal accumulation and cell wall fractions in Cosmos bipinnatus - XiaoFang Yu; ZiHan Yang; YuHan Xu; ZhiWen Wang; ChunYu Fan; XiaoXuan Zeng; YuJia Liu; Ting Lei; MingYan Jiang; JiaNi Li; Xue Xiao; LiJuan Yang; et al. (Chemosphere, 2023)

Associations between short-term and long-term exposure to particulate matter and preterm birth - Yun-Fei Su; Cheng Li; Jing-Jing Xu; Fang-Yue Zhou; Tao Li; Cong Liu; Yan-Ting Wu; He-Feng Huang (Chemosphere, 2023)

The size of the susceptible pool differentiates climate effects on seasonal epidemics of bacillary dysentery - Haobo Ni; Qinghui Zeng; Ting Xu; Lina Xiao; Xiaolin Yu; Jinrui Hu; Yang Li; Hualiang Lin; Pi Guo; Haijian Zhou (Science of The Total Environment, 2023)

A review on microalgae-mediated biotechnology for removing pharmaceutical contaminants in aqueous environments: Occurrence, fate, and removal mechanism - Ting Zhou; Zehao Zhang; Huan Liu; Shiman Dong; Long D. Nghiem; Li Gao; Alex V. Chaves; Arash Zamyadi; Xuan Li; Qilin Wang (Journal of Hazardous Materials, 2023)

FSP synthesized core-shell CuOx@SiO2 catalyst with excellent thermal stability for catalytic combustion of ammonia - Guangzhao Zhou; Yiran Zhang; Xuteng Zhao; Yu Gui; Xiaochao Wang; Linjia Li; Ting Chen; Zhen Huang; He Lin (Fuel, 2023)

Using transcriptomics to reveal the molecular mechanism of higher alcohol metabolism in Saccharomyces cerevisiae - Danyao Cui; Ling Liu; Xiaoyuan Zhang; Liangcai Lin; Xin Li; Ting Cheng; Chunhui Wei; Yu Zhang; Zheng Zhou; Wei Li; Cuiying Zhang (Food Bioscience, 2023)

Efficient fabrication of desert beetle-inspired micro/nano-structures on polypropylene/graphene surface with hybrid wettability, chemical tolerance, and passive anti-icing for quantitative fog harvesting - Wei-long Zhou; Ting Wu; Yu Du; Xiao-hu Zhang; Xin-chang Chen; Jin-bo Li; Heng Xie; Jin-ping Qu (Chemical Engineering Journal, 2023)

Micropyrones A and B, two new α -pyrones from the actinomycete Microbacterium sp. GJ312 isolated from Glycyrrhiza uralensis Fisch - Ying-Ting Xu; Yu-Cai Luo; Jing-Hua Xue; Yu-Ping Li; Lei Dong; Wen-Jun Li; Zhong-Yu Zhou; Xiao-Yi Wei (Natural Product Research, 2023)

Chemical composition and therapeutic mechanism of Xuanbai Chengqi Decoction in the treatment of COVID-19 by network pharmacology, molecular docking and molecular dynamic analysis - Liming Fan; Shuai Feng; Ting Wang; Xinli Ding; Xinxin An; Zhen Wang; Kun Zhou; Minjuan Wang; Xifeng Zhai; Yang Li (Molecular Diversity, 2023)

Coexistence of antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) and IgA nephropathy - Qi Xiong; Wei Lin; Chanjuan Shen; Ting Meng; Rong Tang; Joshua D. Ooi; Peter J. Eggenhuizen; Jinbiao Chen; Wannian Nie; Xia Li; Qiaoling Zhou; Ping Xiao; et al. (Immunologic Research, 2023)

Proactive therapeutic drug monitoring of vincristine in pediatric and adult cancer patients: current supporting evidence and future efforts - Chun-Ying Wu; Guan-Ting Li; Chen-Chao Chu; Hong-Li Guo; Wei-Rong Fang; Tao Li; Yong-Ren Wang; Jing Xu; Ya-Hui Hu; Li Zhou; Feng Chen (Archives of Toxicology, 2023)

Prenatal titanium exposure and child neurodevelopment at 1 year of age: A longitudinal prospective birth cohort study - Yangqian Jiang; Yongyue Wei; Wenhui Guo; Jiangbo Du; Tao Jiang; Hongxia Ma; Guangfu Jin; Ting Chen; Rui Qin; Shiyao Tao; Qun Lu; Hong Lv; et al. (Chemosphere, 2023)

Response of ecosystem gross primary productivity to drought in northern China based on multi-source remote sensing data - Ting Zhang; Junzhi Zhou; Ping Yu; Jianzhu Li; Yanfu Kang; Bo Zhang (Journal of Hydrology, 2023)

Clean hydrometallurgical route for highly efficient decontamination and recycling of multiple heavy metals from hazardous Pb smelting residues: Multi-objective leaching optimization, adsorption, and risk assessment - Yu Zhang; Ting Li; Shirong Zhang; Guiyin Wang; Xiaoxun Xu; Yulin Pu; Lulu Long; Jinsong He; Wei Zhou; Guoshu Gong; Ling Luo (Journal of Cleaner Production, 2023)

Atmospheric environment monitoring technology and equipment in China: A review and outlook - Youwen Sun; Ting Yang; Huaqiao Gui; Xin Li; Weigang Wang; Jun Duan; Shushuai Mao; Hao Yin; Bin Zhou; Jianlei Lang; Haijin Zhou; Cheng Liu; et al. (Journal of Environmental Sciences, 2023)

Mo isotopes archive oceanic sediments in post-orogenic lithospheric mantle - Feng Huang; Jie Li; Jifeng Xu; Jianlin Chen; Baodi Wang; Pan Hu; Rong Xu; Yunchuan Zeng; Le Zhang; Ting Zhou (Geochimica et Cosmochimica Acta, 2023)

Modifying functional properties of food amyloid-based nanostructures from rice glutelin - Ting Li; Jiangtao Zhou; Qinglan Wu; Xinxia Zhang; Zhengxing Chen; Li Wang (Food Chemistry, 2023)

Oligosaccharide analysis of the backbone structure of the characteristic polysaccharide of Dendrobium officinale - Tin-Long Wong; Li-Feng Li; Ji-Xia Zhang; Quan-Wei Zhang; Xue-Ting Zhang; Li-Shuang Zhou; Hau-Yee Fung; Lei Feng; Hui-Yuan Cheng; Chu-Ying Huo; Man Liu; Wan-Rong Bao; et al. (Food Hydrocolloids, 2023)

A thin LiGa alloy layer from in-situ electroreduction to suppress anode dendrite formation in lithium-sulfur pouch cell - Rong Li; Liwen Yang; Lei Song; Changan Zhou; Jiayu Zhou; Ting Chen; Chen Wu; Yujia Zeng; Kui Ma; Hairong Yue (Chemical Engineering Journal, 2023)

Photothermal activation of peroxydisulfate using iron nanoparticles/MXene@polyurethane sponge module for treatment of landfill leachate: From lab to pilot scale - Haoran Song; Rui Zhou; Shiting Pan; Yuwei Wang; Yang Cai; Qingyun Li; Ting Wu; Yongming Shen; Changping Li (Chemical Engineering Journal, 2023)

A dual-functional fluorescent probe for simultaneous visualization and quantification of Au and Pd species in environmental and biological systems - Yabing Gan; Guoxing Yin; Zhaomin Xu; Huyang Zhou; Ting Yu; Haitao Li; Peng Yin (Chemical Engineering Journal, 2023)

Outer membrane protein of OmpF contributes to swimming motility, biofilm formation, osmotic response as well as the transcription of maltose metabolic genes in Citrobacter werkmanii - Gang Zhou; Ying-Si Wang; Hong Peng; Hui-Zhong Liu; Jin Feng; Su-Juan Li; Ting-Li Sun; Cai-Ling Li; Qing-Shan Shi; Xiao-bao Xie (World Journal of Microbiology and Biotechnology, 2023)

Longitudinal expression profiles of flavonoid synthesis-related genes and their correlations with contents of flavonoids including anthocyanins in purplish-green aerial stems of Panax notoginseng - Hongling Zhang; Guiqiong Li; Min Jiang; Changling Zhao; Pengyu Zhao; Chen Wang; Guosong Wen; Feng Zhou; Wenhua Dongchen; Shaozhong Xu; Ting Mu; Fanlai Meng; et al. (Acta Physiologiae Plantarum, 2023)

Selenium attenuates the association of co-exposure to arsenic, cadmium, and lead with cognitive function among Chinese community-dwelling older adults - Bei-Jing Cheng; Jie Sheng; Hong-Li Wang; Yuan Wang; Hong-Juan Cao; Xiu-De Li; Ting-Ting Zhou; Xiang-Long Meng; Huan-Huan Nie; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; et al. (Environmental Science and Pollution Research, 2022)

Chronological deposition record of trace metals in sediment cores from Chaohu Lake, Anhui Province, China - Xin Wang; Na Gao; Yangyang Liang; Fei Liu; Xiuping Hong; Xiujie Zhou; Liqiang Sun; Hui Li; Ting Fang (Environmental Monitoring and Assessment, 2022)

The spatial distribution and characterization of phosphorus and nitrogen in a water-carrying lake: a case study of Lake Jiaogang, China - Tianlun Han; Kang Zhou; Jiuling Li; Ting Chen; Xueting Xu; Shuai Zhang; Jianying Chao; Ming Kong (Environmental Science and Pollution Research, 2022)

A novel bio-washing eluent obtained from fermentation of fruit wastes for removal of soil Pb: efficiency, mechanism, and risk assessment - Xiaomei Pan; Shirong Zhang; Ting Li; Guiyin Wang; Xiaoxun Xu; Yun Li; Wei Zhou; Jinsong He; Lulu Long; Ouping Deng; Ling Luo; Guoshu Gong (Environmental Science and Pollution Research, 2022)

Dynamic pollution emission prediction method of a combined heat and power system based on the hybrid CNN-LSTM model and attention mechanism - Anping Wan; Jie Yang; Ting Chen; Yang Jinxing; Ke Li; Zhou Qinglong (Environmental Science and Pollution Research, 2022)

Bioremediation of quinclorac injury on tobacco by a rhizosphere bacterium - Linhan Li; Ting Zhou; Linyu Zhong; Qian Zhou; Gang Gu; Mengjun Hu; Fengping Chen; Sheng Lin (World Journal of Microbiology and Biotechnology, 2022)

Genetic relationships of 24 Pennisetum cultivars and construction of DNA fingerprints based on SSR markers - Chengran Wang; Xuming Dan; Ting Liu; Qingyao Li; Zhengjun Pu; Puding Zhou; Yixin Deng; Linkai Huang (Journal of Plant Biochemistry and Biotechnology, 2022)

Two novel and efficient plant composites for the degradation of oxytetracycline: nanoscale ferrous sulphide supported on rape straw waste - Yan Yang; Xiaoxun Xu; Shirong Zhang; Guiyin Wang; Zhanbiao Yang; Zhang Cheng; Junren Xian; Ting Li; Yulin Pu; Wei Zhou; Gang Xiang (Environmental Science and Pollution Research, 2022)

Negative air ion exposure ameliorates depression-like behaviors induced by chronic mild stress in mice - Yun-Qing Hu; Ting-Ting Niu; Jian-ming Xu; Li Peng; Qing-Hua Sun; Ying Huang; Ji Zhou; Yu-Qiang Ding (Environmental Science and Pollution Research, 2022)
The presence of negative air ions (NAI) is suggested to be a beneficial factor in improving psychological status and used in treating depression as an alternative approach. However, more biological evidence from animal models is needed to ensure the effects of NAI on the mood regulation, through which can facilitate identification of possible underlying mechanisms. In this study, the chronic mild stress (CMS) protocol was used to induce depressive-like behaviors in mice, and the effects of NAI exposure on CMS-induced depression-like behaviors were examined. Thirty-day NAI exposure prevented the CMS-induced depression-like behaviors as shown by the restoration of sucrose preference and reduced immobility time in the tail suspension test. In addition, the elevation of serous corticosterone was present in CMS-treated mice but not existed in those with the NAI exposure. Furthermore, we observed altered ratios of some cytokines secreted by type 1 T helper (Th1) cells and Th2 cells in CMS-treated mice, but it could be restored after NAI exposure. In conclusion, NAI intervention is able to ameliorate CMS-induced depression-like behaviors in mice, and this effect is associated with the alteration of corticosterone and functional rebalance between Th1 and Th2 cells.

Transcriptomic analysis reveals yolk accumulation mechanism from the hepatopancreas to ovary in the pacific white shrimp Litopenaeus vannamei - Zhi Li; Minyu Zhou; Yao Ruan; Xiaoli Chen; Chunhua Ren; Hao Yang; Xin Zhang; Jinshang Liu; Huo Li; Lvping Zhang; Chaoqun Hu; Ting Chen; et al. (Frontiers in Marine Science, 2022)
The Pacific white shrimp Litopenaeus vannamei is an economically important penaeid species worldwide. Under farming conditions, the full ovarian maturation of L. vannamei generally depends on the combination of artificial ablation of unilateral eyestalk and feeding high-quality natural diets, suggesting that nutrient accumulation is important to ovarian maturation. In this study, we aimed to investigate the gene expression related to nutritional accumulation in L. vannamei during ovarian development by transcriptomic analysis. A total of 52.45 Gb of high-quality transcriptome data were obtained from 8 samples from the hepatopancreas and ovaries from shrimp in gonadal developmental stages I-IV. A total of 23,149 expressed genes were detected, of which 19,852 were known genes and 3,297 were novel genes. Our study found that genes related to amino acid, carbohydrate and lipid metabolism were expressed at higher levels in the hepatopancreas than in the ovary. The genes for most lipoproteins and their receptors were predominantly expressed in the hepatopancreas, while vitellogenin receptor ( VgR ) was specifically expressed in the ovary. Moreover, two vitellogenin ( Vg ) genes were identified, in which one was specifically expressed in the hepatopancreas and defined as Hp-Vg , and the other was specifically expressed in the ovary and defined as Ov-Vg . In addition, genes related to carotenoid metabolism were enriched in the hepatopancreas. This study provides solid evidence that the hepatopancreas is the major exogenous vitellogenesis site for ovarian maturation of L. vannamei . Two distinct Vg genes perform exogenous and endogenous vitellogenesis in the hepatopancreas and ovary in L. vannamei , respectively. The results of this study also presented some new insights for understanding the nutritional dynamics from the hepatopancreas to ovary during ovarian maturation in penaeids.

Scaffold Engineering with Flavone-Modified Biomimetic Architecture for Vascular Tissue Engineering Applications - Chao Xie; Ting Guo; Wei Wang; Gang Li; Zhou Cai; Shen Chen; Xianwei Wang; Ziyu Liu; Zuyong Wang (Tissue Engineering and Regenerative Medicine, 2022)

Human Umbilical Cord-Derived Mesenchymal Stem Cells Ameliorate Skin Aging of Nude Mice Through Autophagy-Mediated Anti-Senescent Mechanism - Ting Li; Li Zhou; Mengqiang Fan; Zuxiang Chen; Li Yan; Haishan Lu; Ming Jia; Huiling Wu; Letian Shan (Stem Cell Reviews and Reports, 2022)

Lead Exposure in Developmental Ages Promotes Aβ Accumulation by Disturbing Aβ Transportation in Blood-Cerebrospinal Fluid Barrier/Blood–Brain Barriers and Impairing Aβ Clearance in the Liver - Can-Can Zhou; Xu-Jie Wang; Zi-Chen Li; Wen-Jie Lu; Yun-Ting Zhang; Fu-Ming Shen; Dong-Jie Li (Biological Trace Element Research, 2022)

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

Prediction of drought/flood intensities based on a 500-year time series in three different climate provinces of China - Yu Peng; Zhaohua Wang; Yixin Cui; Yali Su; Yiyun Tang; Shiqian Luo; Lianlin Liu; Yanqiu Zhou; Jihui Dong; Wentao Wang; Xiang Li; Jiaxin Shang; et al. (Regional Environmental Change, 2022)

The relative importance of intraspecific variation in above- and belowground plant traits in shaping salt marsh soil bacterial diversity and composition - Hao Liu; Ting Zhu; Xiao Xu; Jia Yao; Chenhao Zhou; Jihua Wu; Bo Li; Ming Nie (Plant and Soil, 2022)

Genome-based reclassification of the genus Meiothermus along with the proposal of a new genus Allomeiothermus gen. nov - Jian-Yu Jiao; Zheng-Han Lian; Ze-Tao Liu; Lan Liu; Meng-Meng Li; Ai-Ping Lv; Wen-Dong Xian; Ting Zhou; Zhitang Lyu; Nimaichand Salam; Wen-Jun Li (Antonie van Leeuwenhoek, 2022)

Abnormal functional connectivity of the salience network in insomnia - Yongxin Cheng; Ting Xue; Fang Dong; Yiting Hu; Mi Zhou; Xiaojian Li; Ruoyan Huang; Xiaoqi Lu; Kai Yuan; Dahua Yu (Brain Imaging and Behavior, 2022)

Effects of synthetic nitrification inhibitor (3,4-dimethylpyrazole phosphate; DMPP) and biological nitrification inhibitor (methyl 3-(4-hydroxyphenyl) propionate; MHPP) on the gross N nitrification rate and ammonia oxidizers in two contrasting soils - Ting Lan; Mengxiao Li; Xiaoqian He; Ouping Deng; Wei Zhou; Ling Luo; Guangdeng Chen; Shu Yuan; Jing Ling; Min Zeng; Xuesong Gao (Biology and Fertility of Soils, 2022)

Distribution Patterns of Synechococcus Indicated Their Environmental Constraints and Related Geochemical Processes in the Yellow Sea - Yuting Zhou; Ting Wang; Xi Chen; Song Qin; Zhenjun Zhao; Xinyi Guo; Jialin Li (Journal of Ocean University of China, 2022)

Unexpected role of electron‐transfer hub in direct degradation of pollutants by exoelectrogenic bacteria - Ting‐Ting Zhu; Zhou‐Hua Cheng; Sheng‐Song Yu; Wen‐Wei Li; Dong‐Feng Liu; Han‐Qing Yu (Environmental Microbiology, 2022)
Summary Exoelectrogenic bacteria (EEB) are capable of anaerobic respiration with diverse extracellular electron acceptors including insoluble minerals, electrodes and flavins, but the detailed electron transfer pathways and reaction mechanisms remain elusive. Here, we discover that CymA, which is usually considered to solely serve as an inner‐membrane electron transfer hub in Shewanella oneidensis MR‐1 (a model EEB), might also function as a reductase for direct reducing diverse nitroaromatic compounds (e.g. 2,4‐dichloronitrobenzene) and azo dyes. Such a process can be accelerated by dosing anthraquinone‐2,6‐disulfonate. The CymA‐based reduction pathways in S . oneidensis MR‐1 for different contaminants could be functionally reconstructed and strengthened in Escherichia coli . The direct reduction of lowly polar contaminants by quinol oxidases like CymA homologues might be universal in diverse microbes. This work offers new insights into the pollutant reduction mechanisms of EEB and unveils a new function of CymA to act as a terminal reductase.

Baicalin attenuates amyloid β oligomers induced memory deficits and mitochondria fragmentation through regulation of PDE-PKA-Drp1 signalling - Hai-Yang Yu; Ye Zhu; Xin-Li Zhang; Lei Wang; Yan-Meng Zhou; Fang-Fang Zhang; Han-Ting Zhang; Xiao-Min Zhao (Psychopharmacology, 2022)

Correction to: Vitamin D mediates the association between acrylamide hemoglobin biomarkers and obesity - Ting Yin; Fang Xu; Shi Shi; Shengen Liao; Xiaosu Tang; Haifeng Zhang; Yanli Zhou; Xinli Li (Environmental Science and Pollution Research, 2022)

Vitamin D mediates the association between acrylamide hemoglobin biomarkers and obesity - Ting Yin; Fang Xu; Shi Shi; Shengen Liao; Xiaosu Tang; Haifeng Zhang; Yanli Zhou; Xinli Li (Environmental Science and Pollution Research, 2022)

Caldalkalibacillus salinus sp. nov., isolated from a salt lake in Xinjiang, northwest China - Ting-Hao Ouyang; Man Peng; Zhen Zhang; Wei-Xun Chunyu; Li-Ming Wang; En-Min Zhou; Xu-Hong Gao; Shu-Kun Tang (Archives of Microbiology, 2022)

Northward Shift in Landfall Locations of Tropical Cyclones over the Western North Pacific during the Last Four Decades - Ting Chen; Shumin Chen; Mingsen Zhou; Chaoyong Tu; Aoqi Zhang; Yilun Chen; Weibiao Li (Advances in Atmospheric Sciences, 2022)

Effect of Sodium Salicylate on Calcium Currents and Exocytosis in Cochlear Inner Hair Cells: Implications for Tinnitus Generation - Ting Fan; Meng-Ya Xiang; Ruo-Qiao Zhou; Wen Li; Li-Qin Wang; Peng-Fei Guan; Geng-Lin Li; Yun-Feng Wang; Jian Li (Neuroscience Bulletin, 2022)

Williamsia soli sp. nov., an actinobacterium isolated from soil at a thermal power plant in Yantai, China - Ming-Jing Zhang; Xue-Han Li; Li-Yang Peng; Shuai-Ting Yun; Zhuo-Cheng Liu; Yan-Xia Zhou (Archives of Microbiology, 2022)

The roles of microRNAs played in lung diseases via regulating cell apoptosis - Qiaoling Huang; Li Chen; Qinqin Bai; Ting Tong; You Zhou; Zhongyu Li; Chunxue Lu; Shenghua Chen; Lili Chen (Molecular and Cellular Biochemistry, 2021)

Luteirhabdus pelagi gen. nov., sp. nov., a novel member of the family Flavobacteriaceae, isolated from the West Pacific Ocean - Wen-Ting Ren; Fan-Xu Meng; Li-Li Guo; Li Sun; Xue-Wei Xu; Peng Zhou; Yue-Hong Wu (Archives of Microbiology, 2021)
A Gram-stain-negative, aerobic, and yellow-pigmented bacterium, designated A3-108 T , was isolated from seawater of the West Pacific Ocean. Cells were non-motile and rod-shaped, with carotenoid-type pigments. Strain A3-108 T grew at pH 6.0–8.5 (optimum 6.5) and 15–40 °C (optimum 28 °C), in the presence of 0.5–10% (w/v) NaCl (optimum 1.0%). It possessed the ability to produce H 2 S. Based on the 16S rRNA gene analysis, strain A3-108 T exhibited highest similarity with Aureisphaera salina A6D-50 T (90.6%). Phylogenetic analysis shown that strain A3-108 T affiliated with members of the family Flavobacteriaceae and represented an independent lineage. The principal fatty acids were iso-C 15:0 , iso-C 17:0 3-OH, iso-C 15:1 G, and summed feature 3 (C 16:1 ω 7 c and/or C 16:1 ω 6 c ). The sole isoprenoid quinone was MK-6. The major polar lipids were phosphatidylethanolamine, one unidentified aminophospholipid, one unidentified aminolipid and one unidentified lipid. The ANIb, in silico DDH and AAI values among the genomes of strain A3-108 T and three reference strains were 67.3–71.1%, 18.7–22.1%, and 58.8–71.4%, respectively. The G + C content was 41.0%. Distinctness of the phylogenetic position as well as differentiating chemotaxonomic and other phenotypic traits revealed that strain A3-108 T represented a novel genus and species of the family Flavobacteriaceae , for which the name Luteirhabdus pelagi gen. nov., sp. nov. is proposed (type strain, A3-108 T = CGMCC 1.18821 T = KCTC 82563 T ).

Pivotal role of the gut microbiota in congenital insensitivity to pain with anhidrosis - Mi Zhang; Yishun Hong; Wenyao Wu; Ningbo Li; Baowen Liu; Jiaoli Sun; Xueqin Cao; Ting Ye; Ling Zhou; Cunming Liu; Chun Yang; Xianwei Zhang (Psychopharmacology, 2021)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Efficiency and comprehensive risk assessment of soil Pb and Cd by washing technique with three biodegradable eluents - Qinmei Zhong; Shirong Zhang; Xiaomei Pan; Guiyin Wang; Xiaoxun Xu; Ting Li; Wei Zhou; Yan He; Ling Luo; Yan Liu; Lulu Long (Environmental Science and Pollution Research, 2021)

Echinicola salinicaeni sp. nov., a novel bacterium isolated from saltern mud - Han Zhao; Chun-Yi Song; Rui Yin; Yan-Jun Yi; Shuai-Ting Yun; Ying-Xiu Li; Yan-Xia Zhou (Antonie van Leeuwenhoek, 2021)

Phenotypic and genomic adaptations to the extremely high elevation in plateau zokor ( Myospalax baileyi ) - Tao Zhang; Jie Chen; Jia Zhang; Yuan‐Ting Guo; Xin Zhou; Meng‐Wen Li; Zhi‐Zhong Zheng; Tong‐Zuo Zhang; Robert W. Murphy; Eviatar Nevo; Peng Shi (Molecular Ecology, 2021)
The evolutionary outcomes of high elevation adaptation have been extensively described. However, whether widely distributed high elevation endemic animals adopt uniform mechanisms during adaptation to different elevational environments remains unknown, especially with respect to extreme high elevation environments. To explore this, we analysed the phenotypic and genomic data of seven populations of plateau zokor ( Myospalax baileyi ) along elevations ranging from 2,700 to 4,300 m. Based on whole‐genome sequencing data and demographic reconstruction of the evolutionary history, we show that two populations of plateau zokor living at elevations exceeding 3,700 m diverged from other populations nearly 10,000 years ago. Further, phenotypic comparisons reveal stress‐dependent adaptation, as two populations living at elevations exceeding 3,700 m have elevated ratios of heart mass to body mass relative to other populations, and the highest population (4,300 m) displays alterations in erythrocytes. Correspondingly, genomic analysis of selective sweeps indicates that positive selection might contribute to the observed phenotypic alterations in these two extremely high elevation populations, with the adaptive cardiovascular phenotypes of both populations possibly evolving under the functional constrains of their common ancestral population. Taken together, phenotypic and genomic evidence demonstrates that heterogeneous stressors impact adaptations to extreme elevations and reveals stress‐dependent and genetically constrained adaptation to hypoxia, collectively providing new insights into the high elevation adaptation.

Degraded polysaccharides from Porphyra haitanensis: purification, physico-chemical properties, antioxidant and immunomodulatory activities - Yun-Feng Huo; Yin-Ting Li; Wei Xia; Chong Wang; Yuan-Yuan Xie; Yan-Bo Wang; Tao Zhou; Ling-Lin Fu (Glycoconjugate Journal, 2021)

Cross‐phytogroup assessment of foliar epiphytic mycobiomes - Ting Zhu; Jia Yao; Hao Liu; Chen‐Hao Zhou; Yuan‐Zhan Liu; Zheng‐Wei Wang; Zhe‐Xue Quan; Bo Li; Ji Yang; Wei‐Chang Huang; Ming Nie (Environmental Microbiology, 2021)
Summary The foliar surface forms one of the largest aboveground habitats on Earth and maintains plant‐fungus relationships that greatly affect ecosystem functioning. Despite many studies with particular plant species, the foliar epiphytic mycobiome has not been studied across a large number of plant species from different taxa. Using high‐throughput sequencing, we assessed epiphytic mycobiomes on leaf surfaces of 592 plant species in a botanical garden. Plants of angiosperms, gymnosperms, and pteridophytes were involved. Plant taxonomy, leaf side, growing environment, and evolutionary relationships were considered. We found that pteridophytes showed the higher fungal species diversity, stronger mutualistic fungal interactions, and a greater percentage of putative pathogens than gymnosperms and angiosperms. Plant taxonomic group, leaf side, and growing environment were significantly associated with the foliar epiphytic mycobiome, but the similarity of the mycobiomes among plants was not directly related to the distance of the host evolutionary tree. Our results provide a general understanding of the foliar fungal mycobiomes from pteridophytes to angiosperms. These findings will facilitate our understanding of foliar fungal epiphytes and their roles in plant communities and ecosystems.

Urinary phenols and parabens metabolites associated with cardiovascular disease among adults in the United States - Ting Yin; Xu Zhu; Iokfai Cheang; Yufei Zhou; Shengen Liao; Xinyi Lu; Yanli Zhou; Wenming Yao; Xinli Li; Haifeng Zhang (Environmental Science and Pollution Research, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

OsGSTU6 Contributes to Cadmium Stress Tolerance in Rice by Involving in Intracellular ROS Homeostasis - Xiu-Qing Jing; Meng-Ru Zhou; Xiu-Min Nie; Lu Zhang; Peng-Tao Shi; Abdullah Shalmani; Hai Miao; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2021)

Analysis of variation patterns in rice milled quality in the offspring of indica–japonica hybridization - Ting Mao; Zhan Zhang; Shan-Jun Ni; Yi-Zhou Zhao; Xin Li; Li-Li Zhang; Yan Liu; Xu Li (Genetic Resources and Crop Evolution, 2021)

Two new dihydroisocoumarins with antimicrobial activities from the fungus Penicillium sp. XR046 collected from Xinren coal area - Guo-Bo Xu; Fei-Yu Yang; Xin-Yu Wu; Rui Li; Meng Zhou; Bing Wang; Xiao-Sheng Yang; Ting-Ting Zhang; Shang-Gao Liao (Natural Product Research, 2021)

Emergent chikungunya fever and vertical transmission in Yunnan Province, China, 2019 - XiaoXiong Yin; Ting-Song Hu; HaiLin Zhang; YongHua Liu; ZhiJian Zhou; LeBin Liu; Ping Li; YiYin Wang; ZhaoLan Yang; Jing Yu; SiYu Chen; Fu-Qiang Zhang (Archives of Virology, 2021)

Recent advances on aptamer-based biosensors for detection of pathogenic bacteria - Danliang Li; Luyao Liu; Qiaoling Huang; Ting Tong; You Zhou; Zhongyu Li; Qinqin Bai; Hao Liang; Lili Chen (World Journal of Microbiology and Biotechnology, 2021)

Assisted selection of eating quality progeny of indica (O. sativa L. ssp. indica) and japonica (O. sativa L. ssp. japonica) hybrids using rice starch properties - Ting Mao; Zhan Zhang; Shan Jun Ni; Yi Zhou Zhao; Xin Li; Li Li Zhang; Yan Liu; Cheng Shun Zhong; He Huang; Shao Lin Wang; Xu Li (Genetic Resources and Crop Evolution, 2021)

Warming leads to more closed nitrogen cycling in nitrogen‐rich tropical forests - Zhiyang Lie; Wenjuan Huang; Xujun Liu; Guoyi Zhou; Junhua Yan; Yuelin Li; Chumin Huang; Ting Wu; Xiong Fang; Mengdi Zhao; Shizhong Liu; Guowei Chu; et al. (Global Change Biology, 2021)
Warming may have profound effects on nitrogen (N) cycling by changing plant N demand and underground N supply. However, large uncertainty exists regarding how warming affects the integrated N dynamic in tropical forests. We translocated model plant‐soil ecosystems from a high‐altitude site (600 m) to low‐altitude sites at 300 and 30 m to simulate warming by 1.0°C and 2.1°C, respectively, in tropical China. The effects of experimental warming on N components in plant, soil, leaching, and gas were studied over 6 years. Our results showed that foliar δ 15 N values and inorganic N (NH 4 ‐N and NO 3 ‐N) leaching were decreased under warming, with greater decreases under 2.1°C of warming than under 1.0°C of warming. The 2.1°C of warming enhanced plant growth, plant N uptake, N resorption, and fine root biomass, suggesting higher plant N demand. Soil total N concentrations, NO 3 ‐N concentrations, microbial biomass N and arbuscular mycorrhizal fungal abundance were decreased under 2.1°C of warming, which probably restricted bioavailable N supply and arbuscular mycorrhizal contribution of N supply to plants. These changes in plants, soils and leaching indicated more closed N cycling under warming, the magnitude of which varied over time. The closed N cycling became pronounced during the first 3 years of warming where the sustained reductions in soil inorganic N could not meet plant N demand. Subsequently, the closed N cycling gradually mitigated, as observed by attenuated positive responses of plant growth and less negative responses of microbial biomass N to warming during the last 3 years. Overall, the more closed N cycling under warming could facilitate ecosystem N retention and affect production in these tropical forests, but these effects would be eventually mitigated with long‐term warming probably due to the restricted plant growth and microbial acclimation.

Transcription factor MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene MoAUH1 to govern infectious growth via mitochondrial fusion/fission balance in Magnaporthe oryzae - Yuhan Xiao; Luping Liu; Ting Zhang; Ruiwen Zhou; Yuan Ren; Xinrui Li; Haidong Shu; Wenwu Ye; Xiaobo Zheng; Zhengguang Zhang; Haifeng Zhang (Environmental Microbiology, 2021)
Summary Mitochondrial quality and quantity are essential for a cell to maintain normal cellular functions. Our previous study revealed that the transcription factor MoMsn2 plays important roles in the development and virulence of Magnaporthe oryzae . However, to date, no study has reported its underlying regulatory mechanism in phytopathogens. Here, we explored the downstream target genes of MoMsn2 using a chromatin immunoprecipitation sequencing (ChIP‐Seq) approach. In total, 332 target genes and five putative MoMsn2‐binding sites were identified. The 332 genes exhibited a diverse array of functions and the highly represented were genes involved in metabolic and catalytic processes. Based on the ChIP‐Seq data, we found that MoMsn2 plays a role in maintaining mitochondrial morphology, likely by targeting a number of mitochondria‐related genes. Further investigation revealed that MoMsn2 targets the putative 3‐methylglutaconyl‐CoA hydratase‐encoding gene ( MoAUH1 ) to control mitochondrial morphology and mitophagy, which are critical for the infectious growth of the pathogen. Meanwhile, the deletion of MoAUH1 resulted in phenotypes similar to the Δ Momsn2 mutant in mitochondrial morphology, mitophagy and virulence. Overall, our results provide evidence for the regulatory mechanisms of MoMsn2, which targets MoAUH1 to modulate its transcript levels, thereby disturbing the mitochondrial fusion/fission balance. This ultimately affects the development and virulence of M . oryzae .

Epidemiological and clinical analysis of the outbreak of dengue fever in Zhangshu City, Jiangxi Province, in 2019 - Jingen Wang; Qiubo Chen; Zhongbao Jiang; Xiaoju Li; Huiping Kuang; Ting Chen; Feng Liu; Wujuan Zhou; Yanxia Huang; Yong Luo; Jianfeng Rao; Weihua Ju; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Image-Forming Visual Basis of Empathy for Pain in Mice - Kai-Wen Geng; Rui Du; Na Wei; Chun-Li Li; Yan Wang; Wei Sun; Tao Chen; Dong-Yu Wei; Yang Yu; Ting He; Wen-Jun Luo; Rui-Rui Wang; et al. (Neuroscience Bulletin, 2020)

A novel high-performance CeO2-CuMn2O4 catalyst for toluene degradation - Ting Zhou; Aijuan Xie; Qing Wang; Xiang Li; Zerui Zhu; Wanqi Zhang; Yuwei Tao; Shiping Luo (Environmental Science and Pollution Research, 2020)

Long‐term effects of 7‐year warming experiment in the field on leaf hydraulic and economic traits of subtropical tree species - Ting Wu; David T. Tissue; Xu Li; Shizhong Liu; Guowei Chu; Guoyi Zhou; Yuelin Li; Mianhai Zheng; Ze Meng; Juxiu Liu (Global Change Biology, 2020)
Rising temperature associated with climate change may have substantial impacts on forest tree functions. We conducted a 7‐year warming experiment in subtropical China by translocating important native forest tree species ( Machilas breviflora , Syzygium rehderianum , Schima superba and Itea chinensis ) from cooler high‐elevation sites (600 m) to 1–2°C warmer low‐elevation sites (300 and 30 m) to investigate warming effects on leaf hydraulic and economic traits. Here, we report data from the last 3 years (Years 5–7) of the experiment. Warming increased leaf hydraulic conductance of S. superba to meet the higher evaporative demand. M. breviflora (300 m), S. rehderianum , S. superba and I. chinensis (300 and 30 m) exhibited higher area‐based and mass‐based maximum photosynthetic rates ( A a and A m , respectively) related to increasing stomatal conductance ( g s ) and stomatal density in the wet season, which led to rapid growth; however, we observed decreased growth of M. breviflora at 30 m due to lower stomatal density and decreased A a in the wet season. Warming increased photosynthetic nitrogen‐use efficiency and photosynthetic phosphorus‐use efficiency, but reduced leaf dry mass per unit area due to lower leaf thickness, suggesting that these tree species allocated more resources into upregulating photosynthesis rather than into structural investment. Our findings highlight that there was trait variation in the capacity of trees to acclimate to warmer temperatures such that I. chinensis may benefit from warming, but S. superba may be negatively influenced by warming in future climates.

The effect of blastomere loss during frozen embryo transfer on the transcriptome of offspring’s umbilical cord blood - Yan-Ting Wu; Ze-Han Dong; Cheng Li; Dai-Zhan Zhou; Jun-Yu Zhang; Yan Wu; Jing-Jing Xu; Yu Wang; Xiao-Qun Ye; Jian-Zhong Sheng; Li Wang; He-Feng Huang (Molecular Biology Reports, 2020)

Puerarin Alleviates Lipopolysaccharide-Induced Myocardial Fibrosis by Inhibiting PARP-1 to Prevent HMGB1-Mediated TLR4-NF-κB Signaling Pathway - Shu-Yuan Ni; Xing-Long Zhong; Ze-Hua Li; Dong-Jian Huang; Wen-Ting Xu; Yan Zhou; Cai-Wen Ou; Min-Sheng Chen (Cardiovascular Toxicology, 2020)

Constraints of salinity- and sediment-induced stratification on the turbidity maximum in a tidal estuary - Ting Lu; Hao Wu; Fan Zhang; Jiasheng Li; Liang Zhou; Jianjun Jia; Zhanhai Li; Ya Ping Wang (Geo-Marine Letters, 2020)

Chemical composition of Erycibe schmidtii and antiproliferative activity of scopoletin on immature dendritic cells - Wang Ren; Yantang Wang; Qinhui He; Yue Zhou; Chunxin Li; Wenling Wang; Xiao Leng; Ting Zeng; Qiang Zou; Limei Li (Natural Product Research, 2020)

Chemical characterization of constituents from Polygonatum cyrtonema Hua and their cytotoxic and antioxidant evaluation - Ting Zeng; Yan-Ran Tang; Bin Li; Shumaila Tasneem; Han-Wen Yuan; Yan-Zhe Jia; Muhammad Daniyal; Nusrat Hussain; Wen-Miao Wang; Da-Lei Zuo; Li-Min Gong; Bin Liu; et al. (Natural Product Research, 2020)

SARS-CoV-2-encoded nucleocapsid protein acts as a viral suppressor of RNA interference in cells - Jingfang Mu; Jiuyue Xu; Leike Zhang; Ting Shu; Di Wu; Muhan Huang; Yujie Ren; Xufang Li; Qing Geng; Yi Xu; Yang Qiu; Xi Zhou (Science China Life Sciences, 2020)

Gastrointestinal involvement of COVID-19 and potential faecal transmission of SARS-CoV-2 - Min Song; Zong-lin Li; Ye-jiang Zhou; Gang Tian; Ting Ye; Zhang-rui Zeng; Jian Deng; Hong Wan; Qing Li; Jin-bo Liu (Journal of Zhejiang University-SCIENCE B, 2020)

The relation of structure and metal-support interaction with three-way catalytic performance of Rh/(Ce,Zr,La)O2 catalysts - Ting Wang; Yan Li; Ren-xian Zhou (Environmental Science and Pollution Research, 2020)

Species-Specific Identification of Streptococcus based on DNA Marker in 16S–23S rDNA Internal Transcribed Spacer - Jia Yu; Ting Zhou; Baojie Zhu; Yuxi Wei; Xuerui Li; Yin Liu (Current Microbiology, 2020)

A new triterpenoid glucoside from Leucas zeylanica - Guang-Ying Chen; Bin Zhang; Ting Zhao; Najat Nidhal; Wang Jia-Li; Xue-Ming Zhou; Dai Chun-Yan (Natural Product Research, 2020)

Bergaptol, a mechanism-based inactivator of CYP2C9 - Tingting Jiang; Ting Cheng; Jing Li; Mengyue Zhou; Rong Tan; Xiaojing Yang; Yang Wang; Weiwei Li; Jiang Zheng (Medicinal Chemistry Research, 2020)

Design, synthesis and cholinesterase inhibitory activity of α -mangostin derivatives - Xiao-Qian Chi; Bo Hou; Liu Yang; Cheng-Ting Zi; Yong-Feng Lv; Jin-Yu Li; Fu-Cai Ren; Ming-Yan Yuan; Jiang-Miao Hu; Jun Zhou (Natural Product Research, 2020)

Chemical constituents from the deep sea-derived Streptomyces xiamenensis MCCC 1A01570 and their effects on RXRα transcriptional regulation - Wei-Xiang Lin; Chun-Lan Xie; Mi Zhou; Man-Li Xia; Ting-Ting Zhou; Hai-Feng Chen; Xian-Wen Yang; Quan Yang (Natural Product Research, 2020)

Transcriptome analysis revealed cadmium accumulation mechanisms in hyperaccumulator Siegesbeckia orientalis L. - Xiaoxun Xu; Shirong Zhang; Zhang Cheng; Ting Li; Yongxia Jia; Guiyin Wang; Zhanbiao Yang; Junren Xian; Yuanxiang Yang; Wei Zhou (Environmental Science and Pollution Research, 2020)

Optimal error analysis of MJO prediction associated with uncertainties in sea surface temperature over Indian Ocean - Xiaojing Li; Youmin Tang; Lei Zhou; Zhixiong Yao; Zheqi Shen; Junde Li; Ting Liu (Climate Dynamics, 2020)
In this study, the predictability of the Madden–Julian Oscillation (MJO) is investigated using the coupled Community Earth System Model (CESM) and the climatically relevant singular vector (CSV) method. The CSV method is an ensemble-based strategy to calculate the optimal growth of the initial error on the climate scale. We focus on the CSV analysis of MJO initialized at phase II, facilitating the investigation of the effect of the initial errors of the sea surface temperature (SST) in the Indian Ocean on it. Six different MJO events are chosen as the study cases to ensure the robustness of the results. The results indicate that for all the study cases, the optimal perturbation structure of the SST, denoted by the leading mode of the singular vectors (SVs), is a meridional dipole-like pattern between the Bay of Bengal and the southern central Indian Ocean. The MJO signal tends to be more converged and significant in the Eastern Hemisphere while the model is perturbed by leading SV. The moist static energy analysis results indicate that the eastward propagation is much more evident in the terms of vertical advection and radiation flux than others. Therefore, the SV perturbation can strengthen and converge the MJO signal mostly by increasing the vertical advection of the moist static energy. Further, the sensitivity studies indicate that the structure of the leading SV is not sensitive to the initial states, which suggests that we might not need to calculate SVs for each initial time in constructing the ensemble prediction, significantly saving computational time in the operational forecast systems.

Field survey study on the difference in Cd accumulation capacity of rice and wheat in rice-wheat rotation area - Jiang-li Yang; Long Cang; Xia Wang; Hong-ting Xu; Dong-mei Zhou (Journal of Soils and Sediments, 2020)

VC++ Software Development and Stability Analysis of a Slope Based on the Slice-Free Method - Wenfeng Tu; Liping Li; Shucai Li; Zongqing Zhou; Ting Lei; Shangqu Sun (Geotechnical and Geological Engineering, 2020)

Identification and characterization of mRNAs and lncRNAs of a barley shrunken endosperm mutant using RNA-seq - Yaya Zou; Huaping Tang; Ting Li; Min Sun; Xiangru Qu; Jieguang Zhou; Congcong Yang; Yang Mu; Qiantao Jiang; Yaxi Liu; Guoyue Chen; Guangdeng Chen; et al. (Genetica, 2020)

Correction to: endoplasmic reticulum stress may activate NLRP3 inflammasomes via TXNIP in preeclampsia - Yong Yang; Jianxin Li; Ting-Li Han; Xianbo Zhou; Hongbo Qi; Philip N. Baker; Wei Zhou; Hua Zhang (Cell and Tissue Research, 2020)

Sources and ore-forming fluid pathways of carbonate-hosted Pb–Zn deposits in Southwest China: implications of Pb–Zn–S–Cd isotopic compositions - Chong Xu; Hong Zhong; Rui-Zhong Hu; Han-Jie Wen; Wei-Guang Zhu; Zhong-Jie Bai; Hai-Feng Fan; Fang-Fang Li; Ting Zhou (Mineralium Deposita, 2020)

Genome-Wide Identification of Malectin/Malectin-Like Domain Containing Protein Family Genes in Rice and Their Expression Regulation Under Various Hormones, Abiotic Stresses, and Heavy Metal Treatments - Xiu-Qing Jing; Abdullah Shalmani; Meng-Ru Zhou; Peng-Tao Shi; Izhar Muhammad; Yi Shi; Rahat Sharif; Wen-Qiang Li; Wen-Ting Liu; Kun-Ming Chen (Journal of Plant Growth Regulation, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Endoplasmic reticulum stress may activate NLRP3 inflammasomes via TXNIP in preeclampsia - Yong Yang; Jianxin Li; Ting-Li Han; Xianbo Zhou; Hongbo Qi; Philip N. Baker; Wei Zhou; Hua Zhang (Cell and Tissue Research, 2020)

Physical Model Experimental Study on Spalling Failure Around a Tunnel in Synthetic Marble - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Lian-Jie Fu; Yong-Run Xiong (Rock Mechanics and Rock Engineering, 2020)

Oral Administration of Strontium Gluconate Effectively Reduces Articular Cartilage Degeneration Through Enhanced Anabolic Activity of Chondrocytes and Chondrogenetic Differentiation of Mesenchymal Stromal Cells - Peilin Hu; Jie Du; Shuai Zhang; Ting Wang; Jun Li; Gang Chen; Guangqian Zhou (Biological Trace Element Research, 2020)

Altered sucrose metabolism and plant growth in transgenic Populus tomentosa with altered sucrose synthase PtSS3 - Juan Li; Kai Gao; Bingqi Lei; Jing Zhou; Ting Guo; Xinmin An (Transgenic Research, 2020)

Metabolomics and physiological analyses reveal β-sitosterol as an important plant growth regulator inducing tolerance to water stress in white clover - Zhou Li; Bizhen Cheng; Bin Yong; Ting Liu; Yan Peng; Xinquan Zhang; Xiao Ma; Linkai Huang; Wei Liu; Gang Nie (Planta, 2019)

A Neuronal Pathway that Commands Deceleration in Drosophila Larval Light-Avoidance - Caixia Gong; Zhenhuan Ouyang; Weiqiao Zhao; Jie Wang; Kun Li; Peipei Zhou; Ting Zhao; Nenggan Zheng; Zhefeng Gong (Neuroscience Bulletin, 2019)

Direct Z-scheme La1-xCexMnO3 catalyst for photothermal degradation of toluene - Yiran Tang; Yuwei Tao; Ting Zhou; Baozhu Yang; Qing Wang; Zerui Zhu; Aijuan Xie; Shiping Luo; Chao Yao; Xiazhang Li (Environmental Science and Pollution Research, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Fusarium oxysporum KB-3 from Bletilla striata: an orchid mycorrhizal fungus - Jianwei Jiang; Ke Zhang; Sheng Cheng; Qianwen Nie; Shen-xian Zhou; Qingqing Chen; Jinglong Zhou; Xiao Zhen; Xue ting Li; Tong wen Zhen; Mingyue Xu; Tom Hsiang; et al. (Mycorrhiza, 2019)

Cholesterol transport through the peroxisome-ER membrane contacts tethered by PI(4,5)P2 and extended synaptotagmins - Jian Xiao; Jie Luo; Ao Hu; Ting Xiao; Meixin Li; Zekai Kong; Luyi Jiang; Zimu Zhou; Yacheng Liao; Chang Xie; Beibei Chu; Honghua Miao; et al. (Science China Life Sciences, 2019)

Correction to: Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2019)

Warming effects on leaf nutrients and plant growth in tropical forests - Ting Wu; Chao Qu; Yiyong Li; Xu Li; Guoyi Zhou; Shizhong Liu; Guowei Chu; Ze Meng; Zhiyang Lie; Juxiu Liu (Plant Ecology, 2019)

Association of Genetic Polymorphisms with Age at Onset in Han Chinese Patients with Bipolar Disorder - Shao-Hua Hu; Yu-Qing Han; Ting-Ting Mou; Man-Li Huang; Jian-Bo Lai; Chee H Ng; Jing Lu; Qiao-Qiao Lu; Qiu-Yan Lin; Yu-Zhi Zhang; Jian-Bo Hu; Ning Wei; et al. (Neuroscience Bulletin, 2019)

The effects of conditioning startling acoustic stimulation (SAS) on the corticospinal motor system: a SAS–TMS study - Yen-Ting Chen; Shengai Li; Ping Zhou; Sheng Li (Experimental Brain Research, 2019)

Crystal Transformation of β-CD-MOF Facilitates Loading of Dimercaptosuccinic Acid - Yuehuai Xiong; Li Wu; Tao Guo; Caifen Wang; Wenting Wu; Yan Tang; Ting Xiong; Yong Zhou; Weifeng Zhu; Jiwen Zhang (AAPS PharmSciTech, 2019)

The 3D-Printing Technology of Geological Models Using Rock-Like Materials - Xia-Ting Feng; Yan-Hua Gong; Yang-Yi Zhou; Zheng-Wei Li; Xu-Feng Liu (Rock Mechanics and Rock Engineering, 2019)

Experimental Study to Design an Analog Material for Jinping Marble with High Strength, High Brittleness and High Unit Weight and Ductility - Guo-Qiang Zhu; Xia-Ting Feng; Yang-Yi Zhou; Zheng-Wei Li; Cheng-Xiang Yang; Yao-Hui Gao (Rock Mechanics and Rock Engineering, 2019)

Neural Differentiation of Mouse Neural Stem Cells as a Tool to Assess Developmental Neurotoxicity of Drinking Water in Taihu Lake - Yang Zhou; Yu Fu; Zhendong Bai; Peixin Li; Bo Zhao; Yuehua Han; Ting Xu; Ningyan Zhang; Lin Lin; Jian Cheng; Jun Zhang; Jing Zhang (Biological Trace Element Research, 2019)

Combined expression and prognostic significance of PPFIA1 and ALG3 in head and neck squamous cell carcinoma - Hong Zhou; Ting Cao; Wen Ping Li; Gang Wu (Molecular Biology Reports, 2019)

Emission of nitrous oxide from plain multi-ditch system and its impact factors - Ouping Deng; Xi Li; Yinlong Xiao; Shirong Zhang; Liangji Deng; Ting Lan; Ling Luo; Xuesong Gao; Wei Zhou; Jing Zhang; Jing Ling (Environmental Science and Pollution Research, 2019)

An Outbreak of Gastroenteritis Associated with GII.17 Norovirus-Contaminated Secondary Water Supply System in Wuhan, China, 2017 - Xuan Zhou; De-Guang Kong; Jing Li; Bei-Bei Pang; Ying Zhao; Jun-Bo Zhou; Ting Zhang; Jun-Qiang Xu; Nobumichi Kobayashi; Yuan-Hong Wang (Food and Environmental Virology, 2019)

Characterization of the complete mitochondrial genome of an endangered fish Semilabeo obscurus (Cyprinidae; Labeoninae; Semilabeo) - Wei Wang; Shikai Li; Ting Liu; Xue Wang; Sheng Zeng; Wenwu Min; Lu Zhou (Conservation Genetics Resources, 2019)

Water requirement of summer maize at different growth stages and the spatiotemporal characteristics of agricultural drought in the Huaihe River Basin, China - Chao Gao; Xuewen Li; Yanwei Sun; Ting Zhou; Gang Luo; Cai Chen (Theoretical and Applied Climatology, 2019)

Characteristics of single atmospheric particles in a heavily polluted urban area of China: size distributions and mixing states - Li Li; Qiyuan Wang; Xu Zhang; Yuanyuan She; Jiamao Zhou; Yang Chen; Ping Wang; Suixin Liu; Ting Zhang; Wenting Dai; Yongming Han; Junji Cao (Environmental Science and Pollution Research, 2019)

Dynamic monitoring of resuspension in the multiple eco-types of the littoral zone of a shallow wind-disturbed lake - Chuang Qi; Yang Zhou; Xiao-guang Xu; Li-min Zhang; Hui Lin; Xin-ting Wu; Kuan Shi; Guo-xiang Wang (Aquatic Sciences, 2019)

In situ resuspension rate monitoring method in the littoral zone with multi-ecotypes of a shallow wind-disturbed lake - Chuang Qi; Xiao-guang Xu; Kuan Shi; Li-min Zhang; Yang Zhou; Hui Lin; Xin-ting Wu; Guo-xiang Wang; Han Meng (Environmental Science and Pollution Research, 2019)

Different CO2 acclimation strategies in juvenile and mature leaves of Ottelia alismoides - Wen Min Huang; Hui Shao; Si Ning Zhou; Qin Zhou; Wen Long Fu; Ting Zhang; Hong Sheng Jiang; Wei Li; Brigitte Gontero; Stephen C. Maberly (Photosynthesis Research, 2018)

Immune Cells After Ischemic Stroke Onset: Roles, Migration, and Target Intervention - Lu-yao Ao; Yun-Yi Yan; Lin Zhou; Cheng-yuan Li; Wan-Ting Li; Wei-rong Fang; Yun-man Li (Journal of Molecular Neuroscience, 2018)

Sucrose signaling function on the formation and swelling of bulblets of Lilium sargentiae E.H. Wilson - Suping Gao; Yuan Zhu; Lingyun Zhou; Xiaofeng Fu; Ting Lei; Qibing Chen; Xiaofang Yu; Yonghong Zhou; Wenji Li; Ju Hu; Di Hu; Wenhui Si (Plant Cell, Tissue and Organ Culture (PCTOC), 2018)

Constitutive and Chloroplast Targeted Expression of Acetyl-CoA Carboxylase in Oleaginous Microalgae Elevates Fatty Acid Biosynthesis - Da-Wei Li; Wei-Hong Xie; Ting-Bin Hao; Jia-Xi Cai; Tian-Bao Zhou; Srinivasan Balamurugan; Wei-Dong Yang; Jie-Sheng Liu; Hong-Ye Li (Marine Biotechnology, 2018)

Soil microbes regulate forest succession in a subtropical ecosystem in China: evidence from a mesocosm experiment - Huixuan Liao; Fangfang Huang; Daijiang Li; Luyao Kang; Baoming Chen; Ting Zhou; Shaolin Peng (Plant and Soil, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

Occurrence and health risk assessment of organotins in waterworks and the source water of the Three Gorges Reservoir Region, China - Ting Deng; Lei Wu; Jun-Min Gao; Bin Zhou; Ya-Li Zhang; Wen-Nan Wu; Zhuo-Heng Tang; Wen-Chao Jiang; Wei-Lin Huang (Environmental Science and Pollution Research, 2018)

Intrinsic renal cells induce lymphocytosis of Th22 cells from IgA nephropathy patients through B7–CTLA-4 and CCL-CCR pathways - Lu Gan; Qiaoling Zhou; Xiaozhao Li; Chen Chen; Ting Meng; Jiaxi Pu; Mengyuan Zhu; Chenggen Xiao (Molecular and Cellular Biochemistry, 2018)

Isolation and identification of bovine nasopharyngeal mucosal epithelial cells and establishment of cell models of acute infection by foot-and-mouth disease virus - Wan-fu Bai; Lu Li; Ting Zhang; Xiao-hu Su; Yong-wei Wang; Bing-wu Zhao; Tao Zhang; Huan-min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2018)

Cross-cultural adaption and psychometric properties of the Chinese version of the Diabetes Behavior Rating Scale: a pilot study - Jing Zhu; Jingjing Xu; Yang Chen; Yong Gu; Li Ji; Yufeng Zhou; Min Zhu; Hsiang-Ting Hsu; Xiaoping Huang; Cuiping Yuan; Yun Shi; Dan Yan; et al. (Science China Life Sciences, 2018)

Neural Stem Cell Transplantation Promotes Functional Recovery from Traumatic Brain Injury via Brain Derived Neurotrophic Factor-Mediated Neuroplasticity - Liu-Lin Xiong; Yue Hu; Piao Zhang; Zhuo Zhang; Li-Hong Li; Guo-Dong Gao; Xin-Fu Zhou; Ting-Hua Wang (Molecular Neurobiology, 2018)

Draft Genome Sequence of Cyclohexylamine-Degrading Strain Acinetobacter sp. YT-02 Isolated - Da-Zhong Yan; Ya-Ting Gan; Hui Zhou; Jun Liu; Xin Li (Current Microbiology, 2018)

Molecular characterization and tissue expression profiles of insulin-like growth factor binding protein-1 (IGFBP-1) in Chinese alligator Alligator sinensis during the active and hibernating periods - Mengyun Li; Ting Meng; Fei Peng; Shengzhou Zhang; Yongkang Zhou; Xiaobing Wu (Biologia, 2018)

Significance of temperature and water availability for soil phosphorus transformation and microbial community composition as affected by fertilizer sources - Dasheng Sun; Qingfang Bi; Kejie Li; Peibin Dai; Yan Yu; Weiwei Zhou; Ting Lv; Xipeng Liu; Jun Zhu; Qichun Zhang; Chongwei Jin; Lingli Lu; et al. (Biology and Fertility of Soils, 2018)

Simulating and mapping the spatial and seasonal effects of future climate and land -use changes on ecosystem services in the Yanhe watershed, China - Dengshuai Chen; Jing Li; Zixiang Zhou; Yan Liu; Ting Li; Jingya Liu (Environmental Science and Pollution Research, 2018)

Down-regulation of Noggin and miR-138 coordinately promote osteogenesis of mesenchymal stem cells - Xing-Kun Sun; Jin Zhou; Lei Zhang; Tian Ma; Yu-Han Wang; Yan-Mei Yang; Yan-Ting Tang; Hong Li; Li-Jun Wang (Journal of Molecular Histology, 2017)

Estimating cadmium concentration in the edible part of Capsicum annuum using hyperspectral models - Ting Wang; Hong Wei; Cui Zhou; Yanwen Gu; Rui Li; Hongchun Chen; Wenchao Ma (Environmental Monitoring and Assessment, 2017)

20(S)-25-methoxyl-dammarane-3β, 12β, 20-triol negatively regulates activation of STAT3 and ERK pathways and exhibits anti-cancer effects in HepG2 cells - Hui-Han Ai; Zi-Long Zhou; Lu-Guo Sun; Mei-Ting Yang; Wei Li; Chun-Lei Yu; Zhen-Bo Song; Yan-Xin Huang; Yin Wu; Lei Liu; Xiao-Guang Yang; Yu-Qing Zhao; et al. (Apoptosis, 2017)

Deep Fracturing of the Hard Rock Surrounding a Large Underground Cavern Subjected to High Geostress: In Situ Observation and Mechanism Analysis - Xia-Ting Feng; Shu-Feng Pei; Quan Jiang; Yang-Yi Zhou; Shao-Jun Li; Zhi-Bin Yao (Rock Mechanics and Rock Engineering, 2017)

Altered functional connectivity within and between the default model network and the visual network in primary open-angle glaucoma: a resting-state fMRI study - Jieqiong Wang; Ting Li; Peng Zhou; Ningli Wang; Junfang Xian; Huiguang He (Brain Imaging and Behavior, 2017)

Cancer risk from gaseous carbonyl compounds in indoor environment generated from household coal combustion in Xuanwei, China - Ka-Hei Lui; Wen-Ting Dai; Chi-Sing Chan; Linwei Tian; Bo-Fu Ning; Yiping Zhou; Xiaolin Song; Bei Wang; Jinwen Li; Jun-Ji Cao; Shun-Cheng Lee; Kin-Fai Ho (Environmental Science and Pollution Research, 2017)

A population association study of vitamin D receptor gene polymorphisms and haplotypes with the risk of systemic lupus erythematosus in a Chinese population - Xu-E Chen; Pu Chen; Shan-Shan Chen; Jin Lu; Ting Ma; Guang Shi; Ya Zhou; Ji Li; Liang Sheng (Immunologic Research, 2017)

An Effective Method for Cadmium Removal from Scallop By-product Enzymatic Hydrolysate - Kai-Lun Hu; Lan-Yi Zhang; Li Su; Wen-Gang Jin; Jing Liu; Ting Zhou; Jing-Feng Yang (Journal of Aquatic Food Product Technology, 2017)

Taking climate, land use, and social economy into estimation of carbon budget in the Guanzhong-Tianshui Economic Region of China - Ting Li; Jing Li; Zixiang Zhou; Yanze Wang; Xiaonan Yang; Keyu Qin; Jingya Liu (Environmental Science and Pollution Research, 2017)

Analgesic Effects of Danggui-Shaoyao-San on Various “Phenotypes” of Nociception and Inflammation in a Formalin Pain Model - Jun-Bin Yin; Ke-Cheng Zhou; Huang-Hui Wu; Wei Hu; Tan Ding; Ting Zhang; Li-Ying Wang; Jun-Ping Kou; Alan David Kaye; Wen Wang (Molecular Neurobiology, 2016)

Estimation of the inland extending length of the freshwater–saltwater interface in coastal unconfined aquifers - Xun Zhou; Chao Song; Ting Li (Hydrological Sciences Journal, 2016)

Transgenesis of Agrobacterium rhizogenes K599 orf3 into plant alters plant phenotype to dwarf and branch - Shasha Wang; Yaling Song; Taihe Xiang; Pan Wu; Ting Zhang; Daze Wu; Shuyu Zhou; Yafei Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Trade-offs between carbon sequestration, soil retention and water yield in the Guanzhong-Tianshui Economic Region of China - Xiaonan Yang; Zixiang Zhou; Jing Li; Xin Fu; Xingmin Mu; Ting Li (Journal of Geographical Sciences, 2016)

Synergistic antitumor activity of triple-regulated oncolytic adenovirus with VSTM1 and daunorubicin in leukemic cells - Jiao Zhou; Qiu-Mei Yao; Jin-Lan Li; Yan Chang; Ting Li; Wen-Ling Han; Hong-Ping Wu; Lin-Fang Li; Qi-Jun Qian; Guo-Rui Ruan (Apoptosis, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Acne-Like Subcutaneous Phaeohyphomycosis Caused by Cladosporium cladosporioides: A Rare Case Report and Review of Published Literatures - Ya Bin Zhou; Ping Chen; Ting Ting Sun; Xing Jia Wang; Dong Ming Li (Mycopathologia, 2016)

Degradation of carbamazepine by UV/chlorine advanced oxidation process and formation of disinfection by-products - Shiqing Zhou; Ying Xia; Ting Li; Tian Yao; Zhou Shi; Shumin Zhu; Naiyun Gao (Environmental Science and Pollution Research, 2016)

Evaluating the fraction of electrically associated cations on surfaces of soil particles by extrapolation of strong-field Wien effect measurements in dilute suspensions - Ting-Ting Fan; Yu-Jun Wang; Cheng-Bao Li; Juan Gao; Dong-Mei Zhou; Shmulik P. Friedman (Journal of Soils and Sediments, 2016)

Detection of novel adenoviruses in fecal specimens from rodents and shrews in southern China - Xue-yan Zheng; Min Qiu; Xue-mei Ke; Wei-jie Guan; Jin-ming Li; Shu-ting Huo; Shao-wei Chen; Xue-shan Zhong; Wen Zhou; Yi-quan Xiong; Jing Ge; Qing Chen (Virus Genes, 2016)

Meiofauna distribution in intertidal sandy beaches along China shoreline (18°–40°N) - Er Hua; Zhinan Zhang; Hong Zhou; Fanghong Mu; Jia Li; Ting Zhang; Bingqing Cong; Xiaoshou Liu (Journal of Ocean University of China, 2016)

High prevalence and diversity of viruses of the subfamily Gammaherpesvirinae, family Herpesviridae, in fecal specimens from bats of different species in southern China - Xue-yan Zheng; Min Qiu; Shao-wei Chen; Jian-peng Xiao; Li-zhen Ma; Shan Liu; Jun-hua Zhou; Qiong-hua Zhang; Xing Li; Zhong Chen; Yi Wu; Hui-fang Chen; et al. (Archives of Virology, 2016)

Protective Effect of Porcine Cerebral Hydrolysate Peptides on Learning and Memory Deficits and Oxidative Stress in Lead-Exposed Mice - Ye Zou; Weiwei Feng; Wei Wang; Yao Chen; Zhaoxiang Zhou; Qian Li; Ting Zhao; Guanghua Mao; Xiangyang Wu; Liuqing Yang (Biological Trace Element Research, 2015)

Evaluation of 90-day Repeated Dose Oral Toxicity, Glycometabolism, Learning and Memory Ability, and Related Enzyme of Chromium Malate Supplementation in Sprague-Dawley Rats - Weiwei Feng; Huiyu Wu; Qian Li; Zhaoxiang Zhou; Yao Chen; Ting Zhao; Yun Feng; Guanghua Mao; Fang Li; Liuqing Yang; Xiangyang Wu (Biological Trace Element Research, 2015)

Multi-residue analysis of pesticides in traditional Chinese medicines using gas chromatography-negative chemical ionisation tandem mass spectrometry - Jing Nie; Shui Miao; Steven J. Lehotay; Wen-Ting Li; Heng Zhou; Xiu-Hong Mao; Ji-Wei Lu; Lan Lan; Shen Ji (Food Additives & Contaminants: Part A, 2015)

Effects of cold acclimation on sugar metabolism and sugar-related gene expression in tea plant during the winter season - Chuan Yue; Hong-Li Cao; Lu Wang; Yan-Hua Zhou; Yu-Ting Huang; Xin-Yuan Hao; Yu-Chun Wang; Bo Wang; Ya-Jun Yang; Xin-Chao Wang (Plant Molecular Biology, 2015)

Upregulation and Diverse Roles of TRPC3 and TRPC6 in Synaptic Reorganization of the Mossy Fiber Pathway in Temporal Lobe Epilepsy - Chang Zeng; Pinting Zhou; Ting Jiang; Chunyun Yuan; Yan Ma; Li Feng; Renkai Liu; Weiting Tang; Xiaoyan Long; Bo Xiao; Fafa Tian (Molecular Neurobiology, 2015)

Biodegradation of a biochar-modified waterborne polyacrylate membrane coating for controlled-release fertilizer and its effects on soil bacterial community profiles - Zijun Zhou; Changwen Du; Ting Li; Yazhen Shen; Yin Zeng; Jie Du; Jianmin Zhou (Environmental Science and Pollution Research, 2015)

Risk assessment of water inrush in karst tunnels and software development - Liping Li; Ting Lei; Shucai Li; Qianqing Zhang; Zhenhao Xu; Shaoshuai Shi; Zongqing Zhou (Arabian Journal of Geosciences, 2015)

Rock Burst Intensity Classification Based on the Radiated Energy with Damage Intensity at Jinping II Hydropower Station, China - Bing-Rui Chen; Xia-Ting Feng; Qing-Peng Li; Ru-Zhou Luo; Shaojun Li (Rock Mechanics and Rock Engineering, 2015)

Activation of Extracellular Signal-Regulated Kinase1/2 in the Medial Prefrontal Cortex Contributes to Stress-Induced Hyperalgesia - Jian Qi; Chen Chen; Ya-Cheng Lu; Ting Zhang; Hao Xu; Yuan-Yuan Cui; Yan-Zhou Chen; Wen Wang; Yu-Lin Dong; Yun-Qing Li (Molecular Neurobiology, 2014)

The effects of different crossing-linking conditions of genipin on type I collagen scaffolds: an in vitro evaluation - Xiujie Zhang; Xueying Chen; Ting Yang; Naili Zhang; Li Dong; Shaoying Ma; Xiaoming Liu; Mo Zhou; Baoxing Li (Cell and Tissue Banking, 2014)

Potent in vitro synergism of fusidic acid (FA) and berberine chloride (BBR) against clinical isolates of methicillin-resistant Staphylococcus aureus (MRSA) - Rong-mei Liang; Xiao-lan Yong; Yu-qin Duan; Yong-hong Tan; Ping Zeng; Zi-ying Zhou; Yan Jiang; Shi-hua Wang; Yun-ping Jiang; Xiao-chun Huang; Zhao-hui Dong; Ting-ting Hu; et al. (World Journal of Microbiology and Biotechnology, 2014)

IL-17A promotes ventricular remodeling after myocardial infarction - Su-Feng Zhou; Jing Yuan; Meng-Yang Liao; Ni Xia; Ting-Ting Tang; Jing-Jing Li; Jiao Jiao; Wen-Yong Dong; Shao-Fang Nie; Zheng-Feng Zhu; Wen-Cai Zhang; Bing-Jie Lv; et al. (Journal of Molecular Medicine, 2014)

Modeling of Friedreich ataxia-related iron overloading cardiomyopathy using patient-specific-induced pluripotent stem cells - Yee-Ki Lee; Philip Wing-Lok Ho; Revital Schick; Yee-Man Lau; Wing-Hon Lai; Ting Zhou; Yanhua Li; Kwong-Man Ng; Shu-Leung HO; Miguel Angel Esteban; Ofer Binah; Hung-Fat Tse; et al. (Pflügers Archiv - European Journal of Physiology, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Molecular cloning and differential expression analysis of a squalene synthase gene from Dioscorea zingiberensis, an important pharmaceutical plant - Yun Ye; Runfa Wang; Liang Jin; Junhao Shen; Xiaotong Li; Ting Yang; Mengzhuo Zhou; Zhifan Yang; Yongqin Chen (Molecular Biology Reports, 2014)

Erratum to: Chemical Characteristics and Utilization of Coal Mine Drainage in China - Qiyan Feng; Ting Li; Bin Qian; Lai Zhou; Bo Gao; Tao Yuan (Mine Water and the Environment, 2014)

Chemical Characteristics and Utilization of Coal Mine Drainage in China - Qiyan Feng; Ting Li; Bin Qian; Lai Zhou; Bo Gao; Tao Yuan (Mine Water and the Environment, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Porcine bone grafts defatted by lipase: efficacy of defatting and assessment of cytocompatibility - Naili Zhang; Mo Zhou; Yumin Zhang; Xusheng Wang; Shaoying Ma; Li Dong; Ting Yang; Lina Ma; Baoxing Li (Cell and Tissue Banking, 2014)

An updated view on the differentiation of stem cells into endothelial cells - YiJiang Zhou; Feng Yang; Ting Chen; YuTao Wu; Mei Yang; JianHua Zhu; Li Zhang (Science China Life Sciences, 2014)

Geochronology of magmatism and mineralization of the Daheishan giant porphyry molybdenum deposit, Jilin Province, Northeast China: constraints on ore genesis and implications for geodynamic setting - Ling-Li Zhou; Qing-Dong Zeng; Jian-Ming Liu; Henrik Friis; Zuo-Lun Zhang; Xiao-Xia Duan; Ting-Guang Lan (International Geology Review, 2014)

A Proteomic Analysis of Placental Trophoblastic Cells in Preeclampsia–Eclampsia - Kaidong Ma; Hong Jin; Rong Hu; Yu Xiong; Shufeng Zhou; Peng Ting; Yan Cheng; Yan Yang; Pengyuan Yang; Xiaotian Li (Cell Biochemistry and Biophysics, 2014)

Genetic variation analysis of apple chlorotic leaf spot virus coat protein reveals a new phylogenetic type and two recombinants in China - Shanyi Chen; Ying Zhou; Ting Ye; Lu Hao; Liyun Guo; Zaifeng Fan; Shifang Li; Tao Zhou (Archives of Virology, 2014)

Uric formaldehyde levels are negatively correlated with cognitive abilities in healthy older adults - Jing Yu; Tao Su; Ting Zhou; Yingge He; Jing Lu; Juan Li; Rongqiao He (Neuroscience Bulletin, 2014)

Chondrogenic differentiation and three dimensional chondrogenesis of human adipose-derived stem cells induced by engineered cartilage-derived conditional media - Hengyun Sun; Yu Liu; Ting Jiang; Xia Liu; Aijuan He; Jie Li; Wenjie Zhang; Wei Liu; Yilin Cao; Guangdong Zhou (Tissue Engineering and Regenerative Medicine, 2014)

Molecular characterization and tissue localization of sensory neuron membrane protein from Chinese honey bee, Apis cerana cerana (Hymenoptera: Apidae) - Ying-Ying Hu; Shu-Fa Xu; Abebe Jenberie Wubie; Wei Li; Jia-Xing Huang; Zhan-Bao Guo; Ting Zhou (Applied Entomology and Zoology, 2013)

Response of ecosystem respiration to experimental warming and clipping at daily time scale in an alpine meadow of tibet - Gang Fu; Zhen-xi Shen; Xian-zhou Zhang; Cheng-qun Yu; Yu-ting Zhou; Yun-long Li; Peng-wan Yang (Journal of Mountain Science, 2013)

Polymorphisms of the Interleukin 6 gene contribute to cervical cancer susceptibility in Eastern Chinese women - Ting-Yan Shi; Mei-Ling Zhu; Jing He; Meng-Yun Wang; Qiao-Xin Li; Xiao-Yan Zhou; Meng-Hong Sun; Zhi-Ming Shao; Ke-Da Yu; Xi Cheng; Xiaohua Wu; Qingyi Wei (Human Genetics, 2013)

Ectopic overexpression of porcine DGAT1 increases intramuscular fat content in mouse skeletal muscle - Ting Li; Dequan Xu; Bo Zuo; Minggang Lei; Yuanzhu Xiong; Hongxing Chen; Yanhong Zhou; Xiaojie Wu (Transgenic Research, 2013)

Characterization of malleability and immunological properties of human adenovirus type 3 hexon hypervariable region 1 - Tianhua Zhong; Xiao Li; Zhichao Zhou; Ting Li; Xingui Tian; Rong Zhou (Archives of Virology, 2012)

SPM43.1 Contributes to Acid-Resistance of Non-Symplasmata-Forming Cells in Pantoea agglomerans YS19 - Qianqian Li; Yuxuan Miao; Ting Yi; Jia Zhou; Zhenyue Lu; Yongjun Feng (Current Microbiology, 2012)

Chelating–Ultrafiltration Treatment of Some Heavy Metal Ions in Aqueous Solutions by Crosslinking Carboxymethyl Modified Cornstarch - Ting Wang; Ye Song; Bin Li; Xiaoguang Zhou (Water, Air, & Soil Pollution, 2012)

The distribution of IGF2 and IMP3 in osteosarcoma and its relationship with angiogenesis - Peng Chen; Shao-jin Wang; Hong-bo Wang; Peng Ren; Xi-qian Wang; Wen-guang Liu; Wan-li Gu; Dong-qing Li; Ting-guo Zhang; Cheng-jun Zhou (Journal of Molecular Histology, 2012)

Effect of long-term administration of dietary β-1,3-glucan on growth, physiological, and immune responses in Litopenaeus vannamei (Boone, 1931) - Hong-Xia Zhao; Jun-Ming Cao; An-Li Wang; Zhen-Yu Du; Chao-Xia Ye; Yan-Hua Huang; Han-Bing Lan; Ting-Ting Zhou; Guo-Li Li (Aquaculture International, 2012)

Response of Soybean Seed Germination to Cadmium and Acid Rain - Ting Ting Liu; Peng Wu; Li Hong Wang; Qing Zhou (Biological Trace Element Research, 2011)

Prevalence, intensity and associated factor analysis of Tropilaelaps mercedesae infesting Apis mellifera in China - Qi Hua Luo; Ting Zhou; Ping Li Dai; Huai Lei Song; Yan Yan Wu; Qiang Wang (Experimental and Applied Acarology, 2011)

Organochlorine Pesticides in Muscle of Wild Seabass and Chinese Prawn from the Bohai Sea and Yellow Sea, China - Shuangxin Shi; Yeru Huang; Lifei Zhang; Xiulan Zhang; Li Zhou; Ting Zhang; Liang Dong (Bulletin of Environmental Contamination and Toxicology, 2011)

G1 cell cycle arrest signaling in hepatic injury after intraperitoneal sepsis in rats - Quan-hui Yang; Da-wei Liu; Xiao-ting Wang; Rong-li Yang; Yan Shi; Yun Long; Hong-zhong Liu; Huai-wu He; Xiang Zhou; Bo Tang (Inflammation Research, 2011)

Levels, Seasonal Patterns, and Potential Sources of Organochlorine Pesticides in the Urban Atmosphere of Beijing, China - Lifei Zhang; Yeru Huang; Liang Dong; Shuangxin Shi; Li Zhou; Ting Zhang; Fangzhuo Mi; Liangzi Zeng; Dingding Shao (Archives of Environmental Contamination and Toxicology, 2011)

Overexpression of a 10-deacetylbaccatin III-10 β-O-acetyltransferase gene leads to increased taxol yield in cells of Taxus chinensis - Peng Zhang; Shu-Tao Li; Ting-Ting Liu; Chun-Hua Fu; Peng-Peng Zhou; Chun-Fang Zhao; Long-Jiang Yu (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Agrobacterium tumefaciens-mediated Transformation of A Taxol-Producing Endophytic Fungus, Cladosporium cladosporioides MD2 - Peng Zhang; Ting-Ting Liu; Peng-Peng Zhou; Shu-Tao Li; Long-Jiang Yu (Current Microbiology, 2011)

Enhanced biodesulfurization by magnetic immobilized Rhodococcus erythropolis LSSE8-1-vgb assembled with nano-γ-Al2O3 - Ting Zhang; Wang-Liang Li; Xiao-Xin Chen; Huang Tang; Qiang Li; Jian-Min Xing; Hui-Zhou Liu (World Journal of Microbiology and Biotechnology, 2011)

Depressed Biofilm Production in Bacillus amyloliquefaciens C06 Causes γ-Polyglutamic Acid (γ-PGA) Overproduction - Jun Liu; Xin Ma; Yu Wang; Fang Liu; Junqing Qiao; Xiu-zhen Li; Xuewen Gao; Ting Zhou (Current Microbiology, 2011)

Molecular cloning and functional analysis of an organ-specific expressing gene coding for farnesyl diphosphate synthase from Michelia chapensis Dandy - Ting Yin; Xiaoying Cao; Qian Miao; Changgen Li; Xianhui Chen; Min Zhou; Jihong Jiang (Acta Physiologiae Plantarum, 2011)

Mutations of the GATA4 and NKX2.5 genes in Chinese pediatric patients with non-familial congenital heart disease - Ting Peng; Li Wang; Shu-Feng Zhou; Xiaotian Li (Genetica, 2010)

AMP-activated protein kinase supports the NGF-induced viability of human HeLa cells to glucose starvation - Luo Ting; Wan Bo; Ruwei Li; Xinya Chen; Yingli Wang; Zhou Jun; Long Yu (Molecular Biology Reports, 2010)

Concentration and Gas-particle Partitioning of Hexachlorobenzene in the Ambient Air Before and After the Beijing Olympic Games - Lifei Zhang; Yeru Huang; Shuangxin Shi; Li Zhou; Ting Zhang; Liang Dong; Dingding Shao (Bulletin of Environmental Contamination and Toxicology, 2010)

Polybrominated diphenyl ethers in background surface soils from the Yangtze River Delta (YRD), China: occurrence, sources, and inventory - Yan-Ping Duan; Xiang-Zhou Meng; Chao Yang; Zhao-Yu Pan; Ling Chen; Ran Yu; Feng-Ting Li (Environmental Science and Pollution Research, 2010)

Rapid generation of dendritic cell specific transgenic mice by lentiviral vectors - Jinyu Zhang; Liyun Zou; Qin Liu; Jingyi Li; Jingran Zhou; Yong Wang; Na Li; Ting Liu; Hong Wei; Min Wu; Ying Wan; Yuzhang Wu (Transgenic Research, 2009)

Prevalence, genetic diversity, and antimicrobial susceptibility profiles of Staphylococcus aureus isolated from bovine mastitis in Zhejiang Province, China - Jian-ping Li; Hai-jian Zhou; Lin Yuan; Ting He; Song-hua Hu (Journal of Zhejiang University-SCIENCE B, 2009)

The influence of leptin on the activity of lung lymphocytes under simulated microgravity - Xu Li; Chang-Ting Liu; Hong Zhou (European Journal of Applied Physiology, 2009)

Sample clean-up methods, immunoaffinity chromatography and solid phase extraction, for determination of deoxynivalenol and deepoxy deoxynivalenol in swine serum - Jianwei He; Xiu-Zhen Li; Ting Zhou (Mycotoxin Research, 2009)

Effects of allicin on CYP2C19 and CYP3A4 activity in healthy volunteers with different CYP2C19 genotypes - Li-Jun Yang; Lan Fan; Zhao-Qian Liu; Yan-Mei Mao; Dong Guo; Li-Hui Liu; Zhi-Rong Tan; Liang Peng; Chun-Ting Han; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Nuclear translocation of dihydrofolate reductase is not a pre-requisite for DNA damage induced apoptosis - Ting-Ting Yuan; Ying Huang; Ci-Xiang Zhou; Yun Yu; Li-Shun Wang; Han-Yi Zhuang; Guo-Qiang Chen (Apoptosis, 2009)

Kinetic and Equilibrium Studies of Cr(VI) Biosorption by Dead Bacillus licheniformis Biomass - Ming Zhou; Yunguo Liu; Guangming Zeng; Xin Li; Weihua Xu; Ting Fan (World Journal of Microbiology and Biotechnology, 2007)

Dissociation (Ds) constructs, mapped Ds launch pads and a transiently-expressed transposase system suitable for localized insertional mutagenesis in rice - Narayana M. Upadhyaya; Qian-Hao Zhu; Xue-Rong Zhou; Andrew L. Eamens; Mohammad S. Hoque; Kerrie Ramm; Ramannee Shivakkumar; Kathryn F. Smith; Shu-Ting Pan; Suzhi Li; Kefan Peng; Song J. Kim; et al. (Theoretical and Applied Genetics, 2006)

Optimization of technological conditions for one-pot synthesis of (S)-α-cyano-3-phenoxybenzyl acetate in organic media - Ting-zhou Zhang; Li-rong Yang; Zi-qiang Zhu (Journal of Zhejiang University-SCIENCE B, 2005)

Deviations in brain early serotonergic development as a result of fetal alcohol exposure - Feng C. Zhou; Youssef Sari; Ting-Kai Li; Charles Goodlett; Efrain C. Azmitia (Neurotoxicity Research, 2002)